Techno-economic performance of an advanced process for synergistic removal of NO/SO2/CO2 via H2O2 pre-oxidation coupled with ammonia scrubbing - Jiaxing Du; Qingqing Liang; Yifan Wang; Hui Xu; Linlin Xu; Yan Liang; Guangying Wang; Lei Bei; Chuanwei Li; Zewei Zhang; Lushi Sun (Fuel, 2027)

Prevalence of Klebsiella pneumoniae in raw milk and biocontrol potential of phage vB_Kpn_18-1 - Ting Qin; Xinyan Yao; Dai Peng; Chaoxiang Jia; Linlin Huang; Yingqian Han; Yanbin Yang; Yang Liu; Guoyu Yang; Juan Geng; Yueying Wang; Heping Li (International Dairy Journal, 2026)

Single-cell transcriptomics reveals cellular heterogeneity and cell–cell communication networks in free gossypol-induced enteritis in juvenile largemouth bass (Micropterus salmoides) - Xinpeng Wang; Wanying Jiang; Linlin Li; Jun Wen; Limeng Wang; Shimei Lin; Yongjun Chen; Li Luo; Xinghua Zhou; Yuanfa He (Fish & Shellfish Immunology, 2026)

The impact of energy structure on sectoral carbon emissions: Evidence from China - Lei Bei; Chaolong Duan; Yongkui Du; Chao Wu; Wentao Li; Hanping Mao; Wu Yang; Ben Wang; Linlin Xu; Ruisi Wang; Xiao Liu; Lushi Sun; et al. (Energy and Climate Change, 2026)

SND1 regulates the androgen signaling axis by stabilizing EIF3B mRNA to facilitate the deterioration of prostate cancer - Ying Li; Chengru Yang; Guoli Cui; Shiliang Gui; Linlin Jia; Yu Chen; Honglin Niu; Hua Xin (Molecular Genetics and Genomics, 2026)

Improving soil quality and wheat yield via conservation tillage in a semiarid region: A long-term field study integrating microorganisms and ecoenzymatic stoichiometry - Linlin Wang; Lingling Li; Zhuzhu Luo; Junhong Xie (Soil and Tillage Research, 2026)

Effect of surface water-groundwater exchange on heavy metal transport in the vegetated rivers - Linlin Li; Jiahao Zou; Hang Li; Jiadong He; Hao Zhang; Canyong Li (Journal of Contaminant Hydrology, 2026)

The spatial divergence mechanism in the ecological resilience of Qinghai spruce to compound dry-hot extremes across the northeastern Qinghai-Tibet Plateau - Xuan Li; Xiaohua Gou; Dingcai Yin; Linlin Gao; Wenhuo Liu; Dingyun Zhang; Zibo Wang; Jianye Yu (Forest Ecology and Management, 2026)

Integrated computational and in vivo evidence prioritizes MYH6 as a candidate node in PFOS-associated HCM-like cardiac remodeling - Hao Gao; Li Ma; Shiyi Tan; Xulei Zuo; Wei Wang; Linlin Zhang; Qin Ding; Rongli Sun; Yuepu Pu; Juan Zhang (Environmental Pollution, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Hollow Zr-MOF/Bi NPs@MXene heterojunction-based ECL amplification strategy for detection of childhood asthma-related miRNA-143-3p - Yang Gao; Zhenrun Li; Wenyan Li; Fangru Jia; Linlin Ma; Qiang Ma; Yanan Li (Chemical Engineering Journal, 2026)

Effects of evidence-based perineal massage on maternal and neonatal physiological outcomes and childbirth experience in primiparous women: A quasi-experimental study - Yuxuan Li; Linlin Cao; Hongxiao He; Haishan Wei; Hong Lu; Shenglian Ni; Jie Lu; Ruiqing Dong; Mengting Wang; Xiaoding Zhou (Next Research, 2026)

Physics-informed machine learning of hyporheic exchange driven by channel blockage and riverbed morphodynamics - Hang Li; Linlin Li; Defu Liu; Genguang Zhang; Jiahao Zou; Yu Lei; Canyong Li (Journal of Hydrology, 2026)

Development of low-ammonia MICP technology based on Mg2 +-enhanced nitrogen assimilation and biomineralization - Linlin Zhang; Yue Zhao; Hongyu Han; Ruoxi Li; Zhaofeng Liu; Yuqing Li; Shenghui Yang; Wen Nie (Journal of Environmental Chemical Engineering, 2026)

Boosting CO₂ sequestration and lipid production in microalgae via a dual-ligand MOF bio-hybrid strategy - Longfei Yuan; Mengwei Li; Xinqing Gao; Manrong Wu; Yitong Wu; Yiming Li; Jianjun Liao; Ping Zhang; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

Ultramicroporous N-doped carbons prepared by KHC2O4 activation for CO2 adsorption - Yujia Yin; Yingyi Wang; Ziyun Li; Ya Liu; Leihong Zhao; Muslum Demir; Aseel Zaid; Linlin Wang; Xin Hu (Journal of Environmental Chemical Engineering, 2026)

Characteristics of overpressure and thermal effects of methane–air explosions in tunnels - Linlin Gu; Zhenjing Nie; Yi Li; Zhen Wang; Chuyuan Huang; Xianfeng Chen (Fuel, 2026)

Corrigendum to “Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China” [Food Res. Int. 242 (2026) 120014] - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Isolation and characterization of broad-host-range bacteriophages and their alleviation of liver and kidney injury in a mouse model of S. aureus infection - Xinyan Yao; Linlin Huang; Chaoxiang Jia; Dai Peng; Rui Cao; Xiangshun Sun; Yingqian Han; Yang Liu; Yanbin Yang; Guoyu Yang; Yueying Wang; Heping Li (Food Research International, 2026)

Comparative metabolomics reveals distinct metabolic profiles and in vitro activities of fermented noni juice from Samoa and China's Hainan - Qianjin Ni; Meimei Nie; Linlin Han; Mingfei Gu; Lingming Xiong; Yayuan Xu; Lei Feng; Liying Niu; Runqiang Yang; Dajing Li; Zhuqing Dai (Food Chemistry, 2026)

Building damage-matched ground motion generation method using physics-guided generative adversarial networks - Qingle Cheng; Haotian Ren; Hongyu Zhao; Aiqun Li; Linlin Xie (Engineering Structures, 2026)

Role of intraseasonal and interannual processes in ocean heat content anomalies east of Mindanao - Zhen Li; Linlin Zhang; Mengmeng Li; Weiqi Song; Xiaoluan Yan; Tangdong Qu (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Plasma-based biomimetic antigen outpost synergizes with immune checkpoint blockade to enhance antitumor immunity via dual inhibition of SOCS1 and PD-L1 pathways in dendritic cells - Siyuan Meng; Fangnan Lv; Jieqing Chen; Linlin Tao; Hao Guo; Danhui Wang; Jie Sun; Jian Li; Ning Liu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

The Ecosystem Health Assessment of the Intertidal Zone in the Yellow River Delta - Shaoyu Jiang; Baoquan Li; Jiao Wang; Jing Chen; Linlin Chen (Wetlands, 2026)

A novel Chaphamaparvovirus detected in breeding Muscovy Ducks with hepatitis - Yadong Gao; Jiawen Dong; Ouyang Peng; Zhuanqiang Yan; Meiting Chen; Yingshan Yin; Minhua Sun; Junqin Zhang; Yunzhen Huang; Yong Xiang; Zhai Qi; Junwei Ge; et al. (Veterinary Research Communications, 2026)

LCE-Net: A Lightweight Attention-Enhanced EfficientNet for Potato Leaf Disease Classification - Shuoqiu Li; Famiao Mou; Linlin Teng (Potato Research, 2026)

Synergistic interaction between lead and cadmium via metal-transporter gene upregulation in mice - Tingting Zhang; Weiqin Xing; James A. Ippolito; Shuangshuang Shao; Xinjun Huang; Yongqiang Yang; Linlin Zhao; Yongxia Cheng; Liping Li (BioMetals, 2026)
This study investigated the potential synergistic interactions between Pb and Cd, and assessed the contribution of transporter gene expression to the synergism. Mice were administered varying doses of Pb (15, 30 and 108 mg kg −1 ) or Cd (1, 2 and 3 mg kg −1 ), or a combination of both in the feed. Liver, kidney and bone samples were analyzed for Cd, Pb, Cu, Mn, Zn and Fe concentrations. For treatments exhibiting synergistic effects, the relative expression levels of the divalent metal transporter 1 ( Dmt1 ), ZRT-IRE-like protein 8 ( Zip8 ) and Zip14 were quantified in the liver and kidney using Quantitative Real-Time Reverse Transcription Polymerase Chain Reaction (qRT-PCR). At 108 mg kg −1 Pb , increasing Cd doses from 0 to 1 mg kg −1 significantly increased Pb concentrations in the kidney, liver and bone by 10.6, 60.2 and 19.6%, respectively; concurrently, the relative expression of the Zip8 in the kidney increased by 69.5%, while Dmt1 and Zip14 expression in the liver increased by 79.0 and 85.6%, respectively. At Cd doses ≥ 1 mg kg −1 , increasing Pb rate resulted in elevated Cd concentrations in the kidney, liver and bone; however, no significant changes in transporter expression levels were observed in the kidney under these treatments, possibly due to the upregulation of transporter genes in the intestines. Results demonstrate that interactions between Pb and Cd can be synergistic, and upregulation of certain transporter genes were responsible for such synergism. These findings offer important insights for mitigating the health risks associated with heavy metal exposure in animal and humans.

A pilot-scale study on continuous wastewater treatment based on microalgae-bacterial consortium: Nutrient removal and microbial community stability - Yaqi Tian; Ronghao Qiao; Kuixiao Li; Jiang Chang; Linlin Wei; Ming Li (Algal Research, 2026)

Nonlinear abiotic transformation of a representative organic micropollutant in a deep stratified reservoir: Critical roles of iron and dissolved organic matter - Linlin Wang; Yi Li; Longfei Wang; Li Lin (Water Research, 2026)

Representation of western boundary currents under different climatologies with varying horizontal resolutions - Hong Li; Guihua Wang; Fanghua Xu; Lijing Cheng; Junde Li; LinLin Zhang; Yuntao Wang; Wei Li; Haiqing Yu; Zenghong Liu; Zhijin Li (Progress in Oceanography, 2026)

UM-RTDETR: An adaptive detection model for underwater heterogeneous targets - Lipeng Ji; Linlin Li; Daqi Zhu (Ocean Engineering, 2026)

Comparative precipitation forecasting in the Northeastern Tibetan Plateau: Tree-ring reconstruction and future projections using machine learning and CMIP6 models - Longyun Ma; Haoyuan Xu; Jinjian Li; Zeyu Zheng; Linlin Cui; Caihong Liu; Shanlei Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Moisture transport patterns over the Northeastern Tibetan Plateau revealed by tree-ring δ18O records - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Jiangzhou Feng; Linlin Gao; Tao Wang; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; et al. (Journal of Hydrology, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

Glycated walnut protein linseed gum conjugates for HIPE-based dressing - Bin Zhang; Li Yang; Xia Chen; Ziyi Liao; Linlin Hou; Kai Zheng; Congfang Li; Juan Dong (Journal of Food Engineering, 2026)

Fungal necromass dominates soil organic carbon accrual after decadal active restoration of alpine grassland - Shijie Zhou; Jinchao Gong; Keqi Fan; Abraham Allan Degen; Jingjing Wu; Xiongkui Lin; Tahmina Kausar; Yue Xiu; Linlin Li; Liang Tie; Ziwei Yang; Congyu Ma; et al. (Journal of Environmental Management, 2026)

A hierarchical Bayesian approach to estimate the most probable number (MPN) concentration of Salmonella in raw chicken from qualitative data - Tianmei Sun; Yangtai Liu; Yixuan Li; Linlin Xiao; Xiaojie Qin; Qingli Dong (International Journal of Food Microbiology, 2026)

Plasma-treated biomass carbon/zinc-manganese dual metal organic frameworks (MOFs) composite electrode for high-performance supercapacitors - Linlin Tai; Gaigai Duan; Qian Wei; Xiaoshuai Han; Weijun Li; Yong Huang; Bin He; Shuijian He; Shaohua Jiang (Fuel, 2026)

Unique coordination of four-metal-atom clusters on C5N2H2 boosts nitrogen reduction reaction performance: a DFT study - Linlin Li; Shaopeng Xu; Yan Yan; Mengmeng Wang; Yan Chen; Jiaojiao Chen; Wei Li; Xunlei Ding (Fuel, 2026)

Urea–NaHCO3 co-activated biochar enhances biohydrogen production via microbial community restructuring and metabolic pathway redirection - Tao Sheng; Jiaxing Meng; Chengwei Song; Changxing Yu; Caiyu Sun; Linlin Huang; Lixin Li; Chunxue Yang; Zhiwei Song (Environmental Research, 2026)

Atomic-level regulation of peroxymonosulfate activation on coal gangue: Toward controllable catalytic pathways and enhanced environmental resilience - Lixin Li; Peijiang Han; Tao Qin; Bo Zhang; Linlin Huang; Xue Dong; Qingju Tang; Xin Zhao; Fengxia Deng (Environmental Research, 2026)

Engineered extracellular vesicle-based microneedle patch via nose-to-brain delivery for enhanced treatment of Alzheimer's disease - Chengxue Pan; Sha Liu; Yue Zhang; Yunxia Li; Linlin Cao; Junli Zhang (Chemical Engineering Journal, 2026)

CH4 displacement and migration during the enrichment of low-concentration coalbed methane by CO2 displacement-assisted vacuum pressure swing adsorption (VPSA) process - Hua Shang; Xiaomin Li; Yang Zhou; Linlin Liu; Jinping Li; Jiangfeng Yang (Chemical Engineering Journal, 2026)

Metagenomic insights into the distribution and potential influencing factors of antibiotic resistance genes in historically polluted lake sediments - Jinyang Fu; Zhunjie Li; Caixi Hu; Linlin Yao; Mengxi Cao; Yiran Dong; Pu Wang; Yong Liang; Lei Tong; Jianbo Shi (Aquatic Toxicology, 2026)

Spatial heterogeneity of ice phenology in large lakes of Xinjiang, China - Kangzheng Zhong; Jiaxin Hao; Puzhe Huo; Chunpeng Chen; Linlin Cui; Liping Xu; Zhijun Li; Jiang Li; Guanghui Wei (Regional Environmental Change, 2026)

UniPept: A Universal Model for Predicting Peptide Properties Based on Atom-Residue Dual-Scale Integration - Haoshuang Wu; Yu Deng; Zhen Li; Mingming Qi; Yanshi Wei; Linlin Zhuo; Quan Zou; Wenqian Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Aurantio-Obtusin Attenuates Aβ-Induced Cognitive Impairment and Synaptic Dysfunction by Suppressing Neuroinflammation in Mice - Xueying Feng; Wei Yu; Song Guo; Yanyan Ji; Junhua Li; Ling Wang; Guolu Zhong; Shiyi Li; Linlin Niu; Danxin Zhu; Kan Zhou; Yehong Du (Journal of Neuroimmune Pharmacology, 2026)

Retraction notice to “Study on the effect of SDBS and SDS on deep coal seam water injection” [Sci. Total Environ. 856 (2023) 158930] - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2026)

Activating Na4 site via crystalline-phase-engineering enables charge redistribution and stress mitigation in Na4Fe3(PO4)2P2O7 cathodes - Linlin Zhou; Danjing Yang; Shuting Wen; Ling Chen; Chenwei Li; Haifeng Yu; Hao Jiang; Chunzhong Li (Science Bulletin, 2026)

Biodegradable piezoelectric suture for real-time biomechanical sensing and therapeutic intervention - Quanhong Hu; Chuyu Tang; Zhirong Liu; Shaobo Wang; Zhuo Wang; Genglin Chen; Shuncheng Yao; Zhuoheng Jiang; Songjing Zhong; Yuxuan Zhang; Linlin Li (Science Bulletin, 2026)

Unveiling urban process-dependent hydrological responses via rainfall “fingerprints” - Ting Liu; Lina Yuan; Yuying Li; Zijiang Song; Linlin Ye; Ao Xu; Tsering Namgyal; Chao Li; Min Liu (Journal of Hydrology, 2026)

Wave-driven core-shell structured cathode SMESs for remediation of phenanthrene and pyrene-contaminated offshore sediments - Haobo Yu; Boyue Liu; Hongying Yuan; Yankai Huang; Yinghao Huang; Tengfei Yuan; Linlin Li; Qi Deng; Jie Li (Journal of Hazardous Materials, 2026)

Hydrothermal response to changes in snow and vegetation cover in Xinjiang, China - Huimin Yang; Yuehong Ran; Yichi Xu; Lihong Wang; Linlin Cui; Xiangqian Li; Mengwen Peng (Journal of Environmental Management, 2026)

Gel-based fascia analogs from soy lipophilic protein and 11S globulin for connective tissue simulation in plant-based meat - Jiyuan Liu; Yixin Zhang; Linlin Liu; Ying Zhu; Yang Li; Mingshou Lv; Bingyu Sun; Xiuqing Zhu; Lianzhou Jiang; Yuyang Huang (Food Bioscience, 2026)

Transforming waste derived phosphate sources into resources for fluoride immobilization by microbially induced phosphate precipitation - Linlin Cui; Jianxing Sun; Min Huang; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Bioresource Technology, 2026)

Exploring Co-occurrence Patterns of Macrobenthic Communities Across Intertidal and Offshore Zones in the Yellow River Delta, China - Jiao Wang; Shaoyu Jiang; Debin Sun; Jing Chen; Baoquan Li; Linlin Chen (Wetlands, 2026)

Understanding eco-hydrological processes in winter wheat croplands through physically consistent modelling - Linlin Li; Yunfei Wang; Aofan Cui; Xinyu Mao; Wenjun Zhao; Wei Li (Theoretical and Applied Climatology, 2026)

2-Methoxyestradiol Suppresses Stemness and Epithelial-Mesenchymal Transition in Drug-Resistant Esophageal Squamous Cell Carcinoma by Targeting the Snail Signaling Pathway in Cancer Stem Cells - Jie Yan; Shuhua Han; Keqi Zhang; Linlin Li; Mingjing He; Haoqing Cao; Meiru Zhu; Bingjie Bi; Qiang Xu; Cong Wang (Stem Cell Reviews and Reports, 2026)

Role of M1 macrophage-derived exosomes in infantile hemangioma regression via AMPK/SIRT1/PGC1α pathway - LinLin Yue; XiuWen Zheng; XiaoQiang Wen; Yong Zeng; Wei Peng; QianDuo Li; LinShan Zeng; JinPing Liu; Yu Wang; WenQing Fu; HaiJin Liu; Feng Chen (Molecular & Cellular Toxicology, 2026)

Benthic Fauna of Foraminifera and Their Distribution Pattern in Sishili Bay, Northern Yellow Sea, China - Tatyana S. Tarasova; Baoquan Li; Yulia A. Trebukhova; Ilia A. Shcherbakov; Aleksandra V. Romanova; Konstantin A. Lutaenko; Jiao Wang; Jing Chen; Linlin Chen (Journal of Ocean University of China, 2026)

Performance and wastewater treatment efficiency of artificially prepared aerobic granular sludge - Xuanzhe Yan; Jinlong Wang; Kailong Liu; Hao Wu; Wei He; Yongmei Zhang; Linlin Tong; Su Li; Zhaoyang You (Biodegradation, 2026)

GAC-YOLO: A Pomegranate Disease Rapid Detection Method with Multi-Scale Feature Enhancement for an Orchard Inspection Robot - Shenghui Fu; Yongchang Deng; Shuangxi Liu; Rongwei Li; Yuefeng Du; Linlin Sun; Hongjian Zhang; Tao Xu; Wen Zhang (Applied Fruit Science, 2026)

Microbiological safety of dehydrated foods: risk analysis, technology evaluation, and synergistic strategies for next-generation processing - Yu Wang; Wenchao Liu; Linlin Li; Weiwei Cao; Junliang Chen; Chung Lim Law; Guangyue Ren; Xu Duan (Critical Reviews in Food Science and Nutrition, 2026)

5-FU chemotherapy induces functional CD7+ and IL7R+ CTLs infiltration to suppress colorectal tumor progression - Yanmin Wu; Yan Li; Xufeng Yao; Yiyang Pan; Linlin Chen; Jian Zhang; Boyu Luo; Yue Teng; Mingqing Zhang; Chunwan Lu (Science China Life Sciences, 2026)

Modified grafted starch flocculant for the treatment of coal chemical gasification gray water: Synergistic turbidity and hardness removal - Lixin Li; Sinan Liu; Fan Yang; Mingyu Han; Zilong Dong; Caiyu Sun; Linlin Huang; Zhichao Feng; Miyi Luo; Lizhi Tian (Journal of Water Process Engineering, 2026)

Photothermal-enhanced capillary/siphon-driven self-priming pump for highly efficient recovery of various oils - Feilong Liu; Linlin Yan; Yingjie Zhang; Jun Ma; Pengcheng Liu; Longjun Wang; Da long Li; Xiquan Cheng (Journal of Hazardous Materials, 2026)

Ecoenzymatic stoichiometry reveals higher microbial nitrogen limitation in active than passive restored alpine wetlands - Tahmina Kausar; Jingjing Wu; Saraj Bahadur; Abraham Allan Degen; Akash Tariq; Feida Sun; Jinchao Gong; Shijie Zhou; Yue Xiu; Linlin Li; Liang Tie; Jordi Sardans; et al. (Journal of Environmental Management, 2026)

Spatial heterogeneity of wildfires in Southern China during the Last Glacial Maximum - Binxu Liu; Jia Liu; Xingyuan Qin; Linlin Chen; Jiaxi Zhou; Zhiyun Lu; Robert A. Spicer; Shufeng Li; Tao Su (Global and Planetary Change, 2026)

Lactobacillus paracasei PC18 fermentation enhances the functional and hypoglycemic properties of soluble dietary fiber from lotus root residue. - Hongzhi Zhang; Lingyu Li; Anthony Pius Bassey; Zhiwei Fu; Yongsheng Zhu; Kaiyan Liu; Linlin Fan; Xiaoli Liu (Food Research International, 2026)

Lymph node–targeting GM-CSF vesicles produced in situ by ultrasound-activated bacterial factories for enhanced immunotherapy - Yue Yuan; Beibei Zhang; Shaobo Duan; Ruiqing Liu; Juan Zhang; Rui Zhang; Qi Zhou; Linlin Zhang; Xiaoxia Xu; Zesheng Li; Yuanyuan Liu; Xiaoxiao Li; et al. (Chemical Engineering Journal, 2026)

A barnacle-inspired hydrogel enables external-internal synergistic modulation of NF-κB/Nrf2 signaling for diabetic wound healing - Xuetong Ji; Junyao Li; Xintao Gao; Jiqing Dong; Linlin Ma; Yu Han; Xiangyan Chen; Yantao Li (Chemical Engineering Journal, 2026)

A bioinspired chitosan-polymer facilitated CO2 utilization under mild reaction conditions - Linlin Li; Jiang Zhao; Qingmei Ge; Yin-Hui Huang; Hang Cong; Wenfeng Zhao (Biomass and Bioenergy, 2026)

Extreme warming and pulsed volcanism during the Paleocene-Eocene Thermal Maximum - Abdelhamid M. Salman; Xue-Ting Wang; Zuoling Chen; Linlin Cui; Hongwei Li; Xu Wang (Science China Earth Sciences, 2026)

Prenatal Cerium Exposure and Neural Tube Defect Risk: A Case-control Study in Shanxi, China - Jing Wei; Fuyuan Yin; Zuqun Jin; Ning Kang; Dezheng Fu; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Aiguo Ren; Shengju Yin (Biological Trace Element Research, 2026)

Mechanistic study of wheat straw-enhanced sulfur release and denitrification in a pyrite-based bioretention system: Iron–sulfur–carbon synergistic interactions - Zhaoyang You; Jinlong Wang; Tao Wang; Xi Chen; Yongmei Zhang; Su Li; Linlin Tong; Kinjal J. Shah (Chemosphere, 2026)

Rupture characteristics and liquefaction-induced mudflow mechanisms of the 2023 Jishishan Ms. 6.2 earthquake on the northeastern Tibetan Plateau margin - Junyi Wang; Weimin Wang; Linlin Li; Chao Wang; Jiankun He; Lin Ding (Tectonophysics, 2026)

Fouling and retention behavior of micro- and nano-plastics in gravity-driven membrane filtration - Xueying Chen; Dongwei Lu; Tongyu Li; Qingcan Zhou; Yinkun Sun; Linlin Zang; Jun Ma (Journal of Water Process Engineering, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Lactiplantibacillus plantarum enables metal recovery from spent LiNi0.33Co0.33Mn0.33O2 cathode via EPS-mediated synergistic bioleaching - Min Li; Hong Wang; Danni Zhang; Zhong Li; Qiuli Xia; Xianjun Guan; Yaojie Yu; Linlin Tong; Junting Tong; Yongqiang Fan; Fuhui Wang; Dake Xu (Journal of Hazardous Materials, 2026)

Genomic and functional characterization of a novel urease-producing bacterium Sulfitobacter sp. IGS-18 for simultaneous coal dust suppression and ammonia nitrogen removal during microbially induced calcite precipitation - Wen Nie; Ruoxi Li; Yue Zhao; Gang Li; Wenjin Niu; Qifan Tian; Jin Shi; Linlin Zhang (Journal of Environmental Chemical Engineering, 2026)

Nitrogen cycle suppression and enhanced carbon burial during the Paleocene-Eocene thermal maximum, recorded from Tarfa section, Egypt (Tethys Ocean) - Abdelhamid M. Salman; Xueting Wang; Zuoling Chen; Hongwei Li; Linlin Cui; Nageh A. Obaidalla; Xu Wang (Global and Planetary Change, 2026)

Mechanism of texture formation in dried fruits and vegetables: from macroscopic to the molecular level - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Food Control, 2026)

3-mercaptopropyltriethoxysilane modified zein electrospun membrane for ethylene removal and its application to banana preservation - Feng Xiao; Yimeng Zhang; Haoran Wang; Ji Wei; Linlin Li; Hualin Wang (Food Packaging and Shelf Life, 2026)

Impacts of different physics schemes on hurricane forecasting in the unified forecast system (UFS) - Linlin Pan; Kathryn Newman; Mrinal Biswas; Brianne Nelson; Bin Liu; Zhan Zhang; Xuejin Zhang; Shuanglong Jin; Zongpeng Song; Rui Hu; Shuanglei Feng; Bo Wang; et al. (Atmospheric Research, 2026)

When did the Ancient Fen River Dry up? Timing and Mechanisms of River Abandonment in the Yuncheng Basin (Southern North China Craton) Based on Sedimentary and Paleoclimatic Evidence - Zhenhong Li; Xiaopeng Dong; Lijie Wei; Mingxing Shi; Debin Nan; Linlin Kou; Jiawei Cui; Ting Huang (Journal of Earth Science, 2026)

Comparison of Turbulent Transport Dissimilarity and the Role of Coherent Structures in the Unstable Surface Layer Between Urban and Rural Areas - Qiyue Sun; Lu Zhang; Jiesheng Xue; Linlin Wang; Yubin Li; Yuanjian Yang (Boundary-Layer Meteorology, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Dose- and time-dependent cardioprotection of liproxstatin-1 via sequential modulation of ferroptosis pathways after myocardial ischemia-reperfusion - Ziwei Huang; Xixi Chen; Junyi Ren; Linlin Wan; Miao Li; Xiaowu Ma; Jing Dong; Hong Ran (Molecular and Cellular Biochemistry, 2026)

Coupling MICP with hydroxypropyl trimethyl ammonium chloride chitosan-loaded zeolite for cleaner dust consolidation: Enhanced mineralization and ammonium mitigation mechanisms - Ruoxi Li; Wen Nie; Linlin Zhang; Gang Li; Wenjin Niu; Qifan Tian; Jin Shi (Process Safety and Environmental Protection, 2026)

Pore-expanded core-shell adsorbent for high Cu(II) adsorption: Performance and DFT mechanism - Yintao Li; Jianwen Wei; Linlin Geng; Dongling Zhao; Xiaobin Zhou (Journal of Water Process Engineering, 2026)

PCBs exposure and renal injury: comprehensive assessment strategy based upon TRAEC strategy - Zhiyuan Chen; Changqian Liu; Linlin Zhang; Jianrong Han; Xiaoyan Ding; Changshun Han; Sihao Zhu; Jiabao Cao; Jiaxin Song; Fucong Zhang; Jian Li; Zhenghong Zuo; et al. (Journal of Environmental Management, 2026)

Polyphenol oxidase-mediated browning during storage of Pinus elliottii oleoresin: characterization of pine-needle PPO and antibrowning action of L-cysteine - Siheng Zhang; Hanxiao Liu; Jingcong Liu; Lu Qin; Xin Li; Xuanrou Wei; Xiaopeng Chen; Linlin Wang (Food Bioscience, 2026)

In-situ synergistic mechanism of wetting and biomineralization in a polymeric surfactant-based microbial composite dust suppressant for dust control in open-pit mines - Ruoxi Li; Wen Nie; Linlin Zhang; Wenjin Niu; Qifan Tian; Jin Shi (Environmental Research, 2026)

Unlocking iron-chromium flow batteries: Conquering kinetics and crossover for affordable grid storage - Jiaxin Meng; Guozhen Zhang; Weizhai Bao; He Liu; Cong Guo; Jingfa Li; Feng Yu; Linlin Yang; Aishui Yu (Chemical Engineering Journal, 2026)

Spatiotemporal distribution, source apportionment, and ecological risks of polycyclic aromatic hydrocarbons in surface water of the Southern Ocean - Tao Yang; Linlin Shi; Saizhang Tan; Bangping Deng; Yu Ke; Shengming Cheng; Yubin Li; Shuangcheng Zhang; Jingwei Wu; Lichen Zhao; Jun Shi (Frontiers in Marine Science, 2026)
In Antarctica, low temperatures favor the trapping and deposition of polycyclic aromatic hydrocarbons (PAHs), whereas the biogeochemical cycling of PAHs on the Southern Ocean adjacent to Antarctica is highly sensitive to climate change. However, very little environmental and ecological information is available on interannual PAHs variations in the surface of the Southern Ocean. From 2022 to 2024, we employed the 38 th , 39 th , and 40 th Chinese National Antarctic Research Expeditions (CHINARE) to collect surface water samples and conduct analyses of the spatio-temporal distribution patterns, source apportionment, and probabilistic ecological risk assessment of the 16 USEPA priority PAHs. We found that ∑PAH concentration in the study area ranged from 427 to 5782 pg/L, with median values of 1795, 1736, and 2559 pg/L for the 38 th , 39 th , and 40 th expeditions, respectively, showing a latitudinal gradient pattern of higher concentrations at lower latitudes and lower concentrations at higher latitudes. A significant concentration rebound was observed in the 40th expedition. Integrated analysis using molecular diagnostic ratios, PCA, and PMF revealed that this rebound was driven by a distinct “dual-pressure pattern”: intensified logistical traffic emissions (combustion sources) and the persistent release of fresh, unweathered PAHs. Source apportionment indicated an evolutionary trend from mixed petrogenic and ship-related liquid fuel combustion (38th) to episodic fresh local inputs (39th), culminating in the complex superposition of sources in the 40th survey. Probabilistic risk assessment using Monte Carlo simulations confirmed that acute risks to plankton remain low (the 95th percentile of ∑RQ MPC was 0.077); However, a structural shift towards hydrophobic high-molecular-weight PAHs (increasing to ~18% in 2024) signals a rising hidden potential for biomagnification in keystone species like Euphausia superba . These findings provide a critical scientific baseline for identifying pollution sources and supporting Antarctic ecosystem management under changing environmental conditions.

Advances in bacterial synthesis pathways of bioflocculants and their applications in mine wastewater treatment - Linlin Zhang; Zhaofeng Liu; Qiang Guo; Jiawei Tang; Xiaoduan Li; Qun Wang (World Journal of Microbiology and Biotechnology, 2026)

Penicinoid A, an undescribed sesterterpenoid with cytotoxic activity from Penicillium herquei - Mengyi Deng; Enrui Zhang; Fengtai Qiu; Yingying Fei; Yuyan Liu; Linlin Li; Yiyang Xiong; Xianli Zhou (Natural Product Research, 2026)

FAdV-4-induced secondary Pasteurella multocida infection potentiates bacterial adherence and aggravates pathological damage in SPF chickens - Yuxin Chen; Guizhen Yi; Yunzhen Huang; Linlin Li; Jiawen Dong; Yong Xiang; Minhua Sun; Junqin Zhang; Bin Wu (Veterinary Microbiology, 2026)

Hydrogeochemical properties and health risks of high-fluoride groundwater in southern Jiaolai Basin - Menghan Tan; Zongjun Gao; Jiutan Liu; Bing Jiang; Linlin Lin; Qiang Li; Yiru Niu (Process Safety and Environmental Protection, 2026)

LDH-based avermectin nanopesticide modulates bioaccumulation, antioxidant responses, and microbiota stability in earthworms' gut - Shuting Yang; Yiqiong Li; Chao Zong; Xinglu Pan; Haonan Wang; Qingkui Fang; Linlin Shi; Fengshou Dong; Haiqun Cao (Pesticide Biochemistry and Physiology, 2026)

Built-in electric field constructed by asymmetric electron cloud distribution for facilitating photocatalytic H2O2 production in covalent organic frameworks - Chuanxue You; Yue Zhou; Meiting Yang; Jingyang Li; Bo Hu; Yunchao Ma; Linlin Liu; Chunbo Liu; Guangbo Che (Journal of Environmental Chemical Engineering, 2026)

The biotransformation and toxicity of sulfamethoxazole in phycosphere indicates potential in-situ removal of antibiotics by microalgae - Qing Wang; Linlin Geng; Yanbin Ma; Jie Wang; Ka Zhang; Jiao He; Shang Ren; Yan Sun; Xuli Li; Shaojing Sun; Yi Luo (Journal of Environmental Chemical Engineering, 2026)

Association of prenatal exposure to polychlorinated biphenyls with cleft lip and/or palate risk in offspring: A case-control study - Sainan Li; Shujian Lin; Yongyan Chen; Yiqi Ding; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Environmental Sciences, 2026)

Seven neonicotinoids and twenty-two metabolites in seven food matrices by optimized QuEChERS-HPLC-MS/MS and dietary risk assessment - Zhenzhen Zhou; Xueyan Zhao; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie; Fajun Tian (Food Chemistry, 2026)

Multifunctional nanoemulsion co-delivering Lactobacillus plantarum supernatant and Litsea cubeba essential oil: Construction and application in fiddlehead fern preservation - Jiayue Song; Dengyi Ye; Wenjia Li; Qiao Guo; Yanan Zhang; Xiyu Wang; Ping Tang; Ping Chen; Linlin Xu (Food Bioscience, 2026)

Characterization of a novel lytic Mooglevirus phage to control Salmonella Senftenberg and its application in foods - Jiayi Xue; Tingyu Liu; Linlin Xiao; Jiuchao Zhu; Yi Hong; Xiang Wang; Jinghang Zhang; Hengyi Hu; Zhuosi Li; Qingli Dong; Xiaojie Qin (Food Control, 2026)

Study on the Separation of Co(II) Ions by Triethylenetetramine-Modified Polyacrylonitrile Nanofibers - Yang Luo; Shuyuan Liu; Weiwei Li; Guangchuan He; Guangfu Chen; Xianchen Huang; Xiangyang Niu; Jiahui Ruan; Linlin Huang; Guoyuan Yuan (Water, Air, & Soil Pollution, 2026)

Advances in the understanding of spatiotemporal distribution and hazard assessment of volcanic tsunamis - Kan Zhang; Linlin Li; Peng Du; Tingting Fan; Weitao Wang; Peizhen Zhang (Science China Earth Sciences, 2026)

Proteostasis Collapse Drives Effector Memory T Cells Re-expressing CD45RA (TEMRA) Generation in the Tumor Microenvironment - Linlin Li; Shuo Kan; Qiang Huang; Shiwen Wang; Yuchen Han; Liang Chen; Jun Jin (Phenomics, 2026)

Mediating Effect of Self-Efficacy Between Self-Perceived Burden and End-of-Life Communication Difficulties in Cancer Patients - Yalin Zhu; Linlin Shi; Yuanyuan Jiang; Yuyan Fan; Huixian Zhang; Shouxia Chai; Yan Li (Journal of Cancer Education, 2026)

Association Between Maternal Exposure to Eight Metals at Everyday or Low Levels During the Periconceptional Period and Risk for Fetal Congenital Heart Defects: A Case-Control Study in China - Xin Pi; Chunyi Liu; Xiaoqian Jia; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2026)

Comparison of PM2.5 Pollution during Heating and Non-Heating Periods in Northwest China: Chemical Characteristics, Secondary Contribution, and Regional Transport - Linlin Liang; Xinze Geng; Feng Lin; Xiaoru Liu; Liping Ma; Kun Li; Leixiang Wu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu (Journal of Meteorological Research, 2026)

Resilient-based seismic design of a seismically isolated multitower-connected building - Xinyu Wang; Linlin Xie; Demin Zeng; Tao Wang; Aiqun Li (Earthquake Engineering and Engineering Vibration, 2026)

Soil bacterial community assembly and driving factors in wetlands along the southern margin of the Tarim Basin - Linlin Zhang; Peishan Zhao; Guanglei Gao; Guodong Ding; Ying Zhang; Qiyan Li; Yilin Liu (Applied Soil Ecology, 2026)

Ultrastructural Evidence of Altered Dendritic Morphology in the Prefrontal Cortex of Alzheimer's Model Rats - Jinyue Guo; Jing Liu; Yanchao Zhang; Jiazheng Liu; Hao Zhai; Linlin Li; Hua Han (Neuroscience Bulletin, 2026)

Climate and vegetation-driven variations, ecological thresholds and mechanisms of ecosystem services in China’s drylands - Baolong Ma; Linlin Gao; Yanjun Xu; Xinyue Li; Yang Deng; Haijiang Yang (Environment, Development and Sustainability, 2026)

Hominin occupation of the Western Qinling Mountains as early as ∼900 ka - Zaijun Li; Jian Wang; Chongwen Luo; Yongbo Quan; Linlin Yan; Yuanxin Li; Linxueyi Wang; Shengli Yang; Jia Jia; Ziwei Tao; Tingjiang Peng; Zhenzhong Tian; et al. (Science Bulletin, 2026)

Integrating SDGSAT-1 glimmer imagery with Sentinel-1/2 data for high-resolution building height estimation - Zilu Li; Huadong Guo; Linlin Lu; Yifang Ban; Qi Zhu; Dong Liang (Remote Sensing of Environment, 2026)

Microstructural changes, water migration, and oil release in Camellia oleifera seeds during microwave vacuum drying - Jianan Gao; Guangfei Zhu; Guangyue Ren; Jian Li; Yongli Zhang; Jianfang Shi; Wenchao Liu; Linlin Li; Xu Duan (Journal of Stored Products Research, 2026)

Leveraging butter-whey protein interactions to engineer starch-based inks for high-fidelity 3D food printing - Xinyu Wei; Limin Cheng; Wenchao Liu; Zhenbin Liu; Chaofan Guo; Linlin Li; Weiwei Cao; Xu Duan; Guangyue Ren; Weihua Guo; Wei Chen; Lifeng Pan (Journal of Food Engineering, 2026)

Pretreatment-driven shrinkage regulation in Chinese yam during multiphase microwave drying - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Selective separation of rare earth from acetatesolution containing aluminum by nonequilibrium extraction - Linlin Chang; Jian Li; Dongyue Xie; Xudong Liu; Yaobin Lai; Jiayi Zan; Chenjiahui Wang; Yangyang Xie; Xuxia Zhang; Hui Zhang; Tao Qi; Rongde Li; et al. (Journal of Environmental Management, 2026)

Source and accumulation of helium in the Dongsheng gas Field, Ordos Basin, China: Insights from noble gas isotopes - Yu Gao; Shuangjian Li; Xiaoqi Wu; Dongya Zhu; Pengpeng Li; Linlin Wang; Guangxiang Liu; Jiahao Lv; Jiarun Liu; Quanyou Liu (Journal of Asian Earth Sciences, 2026)

Multi-proxy provenance records from the Yanyuan Basin reveal the Cenozoic tectonic evolution along the southeastern Tibetan Plateau - Yuquan Jiang; Linlin Li; Xiangjiang Yu; Zhongtai He; Dewen Li; Yingying Li (Journal of Asian Earth Sciences, 2026)

Tailoring monoglyceride oleogel crystallization by eutectic and crystal nucleation disturbance: functional frozen specialty fat for use in croissants - Yanxia An; Yi Han; Ziwei Liu; Jingyuan Su; Jian Zhang; Keke Liu; Linlin Li (Food Research International, 2026)

Unlocking the anatomical code of flavor and lipids in grass carp (Ctenopharyngodon idellus) fish oil from different tissue parts by SPME-GC–MS, molecular docking, and lipidomics - Huijuan Zhou; Linchuan Xu; Junru Bai; Linlin Weng; Chengwei Yu; Mingming Hu; Bizhen Zhong; Jinlin Li; Zongcai Tu; Bin Peng (Food Chemistry, 2026)

Oleogels in flour-based foods: an overview from the perspective of crystalline structure and functional performance - Yi Han; Linlin Li; Lukai Ma; Jingyuan Su; Yang Zhao; Jian Zhang; Yanxia An (Food Chemistry, 2026)

Chemical and sensory characteristics of Baiye No.1 (BY1H) yellow tea: Insights into flavoring mechanism and quality valuation - Shiyu Zhang; Xinzhuan Yao; Yanxia Wang; Muhammad Safiullah Virk; Shiyu Tian; Zhenkedai Yuan; Qihong Zou; Linlin Li; Shenyuan Ye; Hu Tang; Litang Lu (Food Bioscience, 2026)

Potential folate-depleting effect of organochlorine pesticide exposure in elevating homocysteine levels - Tian Tian; Ning Kang; Dezheng Fu; Linlin Wang; Lei Jin; Zhiwen Li; Jun Zhang; Jie Qiao; Aiguo Ren; Shengju Yin (Environmental Pollution, 2026)

Electronic structure tuning of Mn-based high-entropy spinel boosts benzene catalytic oxidation - Jiarui Chen; Xiaotong Li; Junjie Feng; Linlin Deng; Mingtai Li; Baojuan Dou; Feng Bin (Chemical Engineering Journal, 2026)

An overview of GNSS for tsunami early warning: From lithosphere to ionosphere - Kejie Chen; Haishan Chai; Jiafeng Li; Guoguang Wei; Mingzhe Lyu; Wenfeng Cui; Chuang Shi; Linlin Li; Peitao Wang; Wei Lu; Jian Lin (Science China Earth Sciences, 2026)

Ecological niche shapes the composition and function of microbial communities in Astragalus membranaceus - Xiao Chen; Zhengyan Li; Yaogong Zhang; Chao Yao; Yuanshuai Yu; Feifei Ding; Jingyi Xu; Yuan Li; Linlin Dong; Guangfei Wei (Plant and Soil, 2026)

Spatio-temporal pattern and driving mechanism of the coupling coordination of human settlements systems - Xueming Li; Meishuo Du; Linlin Feng; Shenzhen Tian; Jun Yang (Journal of Geographical Sciences, 2026)

The intra-annual tree-ring δ18O records from the northeastern Tibetan Plateau can reflect seasonal variations of relative humidity and the intra-annual distribution of precipitation - Kai Wang; Xiaohua Gou; Takeshi Nakatsuka; Yiran Zhang; Tao Wang; Linlin Gao; Yang Deng; Zhen Li; Kaixuan Yang; Xuan Li; Chongshan Wang; Zibo Wang (Agricultural and Forest Meteorology, 2026)

Tidal irrigation-based rice cultivation enhances coastal blue carbon and decreases GHG emissions in brackish mudflats - Lang Zhang; Linlin Li; Hualei Yang; Wenbang Tang; Ji Chen; Hongkai Zhou; Ying Huang; Xuechu Chen; Xiuzhen Li; Ming Luo; Xingyun Huang; Faming Wang; et al. (Agricultural and Forest Meteorology, 2026)

Mechanism of liver fibrosis induced by life-long triclosan exposure in offspring rats: an adverse outcome pathway framework validated by in vivo and in vitro experiments - Fu Liu; Jianing Shang; Linlin Zheng; Xiaoyu Zhang; Anqi Cui; Xue Dou; Yunwei Li; Jieyu Liu (Archives of Toxicology, 2026)

Exploring the necessity of low-carbon transition of power dispatching: a perspective of environmental efficiency assessment - Jingliang Jin; Linlin Li; Wei Ben; Chenxi Li; Tingting Liu; Jizhe Zheng (Environment, Development and Sustainability, 2026)

A Deep-Sea Multi-Sequence Sampling System Integrating In Situ Microbial Filtration with Rapid RNA Stabilization - Wei Bu; Yuan-Jie Chen; Jinhai Luo; Linlin Sun; Xiang Li; Xinyuan Gao; Yuanli Fang; Leisheng Tang; Jiaying Zhao; Jingchun Feng; Haocai Huang (Journal of Marine Science and Engineering, 2026)
Rapid depressurization and warming during recovery can trigger stress in deep-sea microbes and accelerate RNA degradation. We developed a remotely operated vehicle (ROV)-oriented multi-sequence microbial sampler for 2000 m sampling (20 MPa, 2 °C) that integrates in situ filtration with immediate RNAlater injection (an RNA stabilization reagent), collecting up to 12 samples per dive. A Dirichlet sampling–B-spline–SVM framework was used to optimize the cam profile of the sequence trigger for robust actuation under geometric constraints and realistic tolerances in both manufacturing and assembly. Relative to the baseline 3-4-5 motion law, the optimized design reduces nominal peak driving torque by ~18–20% and lowers the maximum torque under tolerance perturbations; tests show a further ~10–25% reduction using a SiC ball–ZrO2 block pair versus a MoS2-lubricated titanium pushrod–ZrO2 block pair. A Darcy–Forchheimer porous-media computational fluid dynamics (CFD) model predicts earlier clogging on the lower membrane and a fast-to-slow RNAlater displacement process; greater membrane resistance mismatch delays 95% displacement and increases RNAlater loss. Simulations and Rhodamine B tests suggest an RNAlater consumption of 0.9 L per parallel filter (one membrane per side), and 20 MPa chamber tests confirm stable operation and membrane retrieval.

Insights into low temperature adaptation in Epinephelus awoara through integrated genome and transcriptome analysis - Linna Wang; Shuai Chen; Zhentong Li; Yang Liu; Shihao Wang; Tangtang Ding; Fengfan Yang; Chunbai Zhang; Linlin Li; Wensheng Li; Qingbin Wang; Xia Zhao; et al. (Aquaculture, 2026)

Machine learning based prediction of mechanical properties in carbon fiber recovered through pyrolysis - Xiang Guo; Tian Li; Chunting Liu; Meng Zhang; Hao Li; Jinrui Li; Yihua Zhang; Chunmei Zeng; Shuwu Wei; Linlin Pei; Fang Liu; Da Chen (Waste Management, 2026)

Endophytic fungi-mediated drought tolerance in spring wheat under no-tillage with straw cover on the Loess Plateau, China - Changliang Du; Lingling Li; Junhong Xie; Khuram Shehzad Khan; Linlin Wang; Zhuzhu Luo; Lingzhi Li; Zechariah Effah; Muhammad Zahid Mumtaz (Soil and Tillage Research, 2026)

Cadmium exposure is associated with impaired ovarian function: Potential role of cadmium-induced ferroptosis in granulosa cells - Jing Li; Yutong Wang; Yali Huang; Nidong Li; Yingxin Zhu; Shengli Lin; Linlin Wang; Wei Guo; Lailai Yan; Chan Tian; Ying Wang (Journal of Hazardous Materials, 2026)

Analysis of shrinkage deformation behavior in microwave vacuum drying of Chinese yam based on evolution of physical properties - Qian Zhou; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Tongxiang Yang; Junliang Chen; Guangyue Ren; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Adsorption mechanism of hydrogen bromide and 2-bromophenol on CuO, Cu2O, α-Fe2O3, and NiO catalysts: A density functional theory study - Lushi Sun; Jiaxing Du; Tao Chen; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Chemical Engineering, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

Cultured meat protein has significantly higher digestibility and more potential bioactive peptides than traditional animal and plant proteins - Yunting Xie; Shijie Ding; Jie Wang; Chong Wang; Linlin Cai; Xiufeng Li; Guanghong Zhou; Chunbao Li (Food Chemistry, 2026)

Mechanism of physicochemical changes in potato starch gel induced by citric acid-autoclaving for texture improvement and resistant starch formation - Linlin Cui; Xinzhu Wang; Shuhan Ge; Xia Li; Yu Wang; Bo Nan; Zhicheng Zhang; Yuhua Wang (Food Chemistry, 2026)

Development and application of a numerical model of an asynchronized parallel double-stage fluid viscous damper for seismic responses control based on OpenSees - Linlin Xie; Haoxiang Wang; Cantian Yang; Aiqun Li; Yue Chen (Engineering Structures, 2026)

Integrated multi-energy hybrid systems for net-zero buildings: Dynamic simulation, lifecycle 4E assessment, and multi-objective optimization - Manfeng Li; Mengke Liu; Guofeng Zhou; Linlin Zhang; Panpan Li; Yiji Lu (Energy and Buildings, 2026)

Enhanced selectivity for the removal of Al3+ from the simulated rare earth leachate via a 3D electrochemical hydrolysis process - Chenjiahui Wang; Jian Li; Dongyue Xie; Xudong Liu; Jiayi Zan; Linlin Chang; Yaobin Lai; Yangyang Xie; Xuxia Zhang; Hui Zhang; Tao Qi; Rongde Li; et al. (Desalination, 2026)

Black phosphorus with enhanced stability via palladium induced electronic structure modulation and its application in portable breath acetone sensing - Guangliang Li; Yunzhu Liu; Lei Ma; Hang Zhang; Jinlong Ma; Linlin Hou; Jian Duan; Guanglan Liao; Hu Long; Tielin Shi (Chemical Engineering Journal, 2026)

Black phosphorus quantum dots regulate inflammation and neural stem cells differentiation via Notch1 signaling through cell adhesion - Lu Chen; Yongyuan Guo; Lusen Shi; Shiji Zhang; Linlin Jiang; Yong Chang; Haoran Liu; Zihang Wang; Na Li; Shiqing Feng (Chemical Engineering Journal, 2026)

Consolidated bio-saccharification (CBS) enhanced hydrogen production via bioaugmentation to eliminate cellobiose inhibition: Investigation on hydrogen production performance and microbial community - Sheng Tao; Song Chengwei; Liu Qianchi; Song Zhiwei; Yang Chunxue; Sun Caiyu; Li Lixin; Huang Linlin; Wang Miao (Biocatalysis and Agricultural Biotechnology, 2026)

Meso–Neoproterozoic rift system along the southwestern North China Craton: evidence from recent drilling and seismic data - Zhenhong Li; Xiaopeng Dong; Haifeng Bai; Yijun Zhou; Jiawei Cui; Linlin Kou; Fang Wu (International Geology Review, 2026)

An integrated multiscale computational study of nephrotoxicity mechanism of citrinin and its metabolites (CIMs)：density functional theory, network toxicology, and molecular dynamics simulation - Jiaxing Li; Furong Xue; Linlin Xu; Huijing Zhang; Xizi Zhang; Chenchen Qi; Chengtao Wang; Wei Chen; Di Zhang (Mycotoxin Research, 2026)

Bone mesenchymal stem cells attenuate axonopathy in spinal cord of rats exposed to 2,5-hexanedione via NGF-dependent and -independent pathways - Qiufang Bai; Zhe Li; Jing Chen; Man Liu; Xiaodan Shao; Xiaochi Chen; Fengyuan Piao; Linlin Fang (Molecular and Cellular Biochemistry, 2026)

CsNAC73 promotes cold-induced theanine biosynthesis by activating CsAlaDC expression in albino Camellia sinensis cv. Baiye 1 - Dandan Li; Ying Sun; Xin He; Xin Cheng; Maoyin Fu; Xuchun Zhang; Qi Chen; Xiaochun Wan; Linlin Liu (Plant Science, 2026)

Interactive effect of children’s copper exposure and socioeconomic status on preschoolers’ cognitive development - Hualong Zhen; Linlin Zhu; Xuemei Hao; Jingru Lu; Yufan Guo; Chunmei Liang; Juan Tong; Fangbiao Tao; Jiong Li; Kun Huang (NeuroToxicology, 2026)

Tracing nitrate sources and transformations using nitrogen and oxygen isotopes in the second largest freshwater lake of China - Zhengjie Li; Guitao Shi; Yilan Li; Linlin Song; Yanhua Zhang; Yi Shi; Wei Zhang; Shuguang Liu; Weizhi Lu (Journal of Hydrology, 2026)

From association to mechanism: Prenatal PFAS Co-exposures induces fetal neural tube defects via autophagy-mediated ferroptosis - Yongyan Chen; Qianhui Cheng; Chen Yang; Sainan Li; Hai Lin; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2026)

Bias-aware learning for unbiased scene graph generation in remote sensing imagery - Tingzhu Wang; Linlin Wang; Junwei Luo; Kang Wu; Yansheng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Comparative metabolomic analysis of spray- and freeze-dried Cornus officinalis microcapsules reveals temperature-dependent flavonoid retention and optimal encapsulation conditions - Wenchao Liu; Xinyu Wei; Lijuan Wang; Linlin Li; Weiwei Cao; Yilin Huang; Junliang Chen; Chung Lim Law; Qing Sun; Guangyue Ren; Xu Duan (Innovative Food Science & Emerging Technologies, 2026)

Thermal performance assessment of coupled soil stratification and groundwater advection effects on vertical borehole heat exchanger - Linlin Zhang; Dongyang Fan; Yanbin Li; Tianhao Yuan; Jun Chen (Geothermics, 2026)

Inactivation of Penicillium ochrochloron spores by pulsed light: Mechanism and preservation efficacy in strawberries - Xiaozhen Cui; Anthony Pius Bassey; Fan Wang; Shudong Xie; Dongnan Li; Linlin Fan; Yongsheng Zhu; Li Bin; Xiaoli Liu (Food Control, 2026)

The effect of yeaZ on formation and resuscitation of viable but nonculturable (VBNC) Salmonella enteritidis serovar enteritidis - Yuyang Jiao; Aiqi Yang; Xin Yu; Jiayu Yu; Jianlong Zhang; Linlin Jiang; Yao Li; Yang Liu; Hongwei Zhu; Xingxiao Zhang (Food Microbiology, 2026)

Humidity-regulating antibacterial trilayer Janus membrane of polyacrylonitrile/gelatin-potato starch/polycaprolactone-cinnamon essential oil for cherry tomato preservation - Mingyi Tian; Chenlong Liu; Zhiyuan Ge; Wei Ji; Yimeng Zhang; Linlin Li; Hualin Wang (Food Packaging and Shelf Life, 2026)

Widespread vegetation damage in Asian Interior due to the 2022 extreme drought - Yu Luo; Linlin Gao; Xiyue Fu; Linhan Si; Xinyue Li; Na Du; Yiyun Yuan; Xiang Zhang; Yang Deng (Environmental Research, 2026)

Inhalable tetrahedral DNA nanoplatforms for dual-barrier penetration and sustained deep-lung delivery of small-molecule drugs - Fenglin Jiang; Qi Han; Hao Deng; Jiaqi Li; Alimire Alifu; Zhuo Chen; Linlin Deng; Xiaoxiao Cai; Yu Chen; Yunfeng Lin (Chemical Engineering Journal, 2026)

Preparation and application of ceramic membranes incorporating graphite tailings for oil wastewater treatment - Lixin Li; Pengyu Yan; Linlin Huang; Zhaoshun Zhan; Jun Zhang; Xinyu Li; Wei Chai; Qingju Tang; Zhurui Shen (Chemical Engineering Journal, 2026)

Bisphenol S and Neurological Health: An Integrated Overview of Neurotoxicity and Underlying Mechanisms - Xing Zhang; Linlin Wu; Dingqi Hua; Bin Zhang; Xi Wang; Linchang Li; Yi Wang; Jiangbo Zhu (Molecular Neurobiology, 2026)

Ptbp2 Alleviates Neuroinflammation and Blood–brain Barrier Disruption via Modulating Microglial Polarization in Ischemic Stroke - Wenting Xu; Linlin Li; Mengjia Zhou; Cong Zhang; Xiangjian Zhang (Molecular Neurobiology, 2026)

Biodiversity and biogeographic patterns of Nereididae (Annelida) across the Indo-Pacific Convergence Zone - Jieyang Weng; Xuwen Wu; Tiantian Wang; Chenrui Li; Linlin Zhang (Journal of Oceanology and Limnology, 2026)

Bioorthogonally activatable methylene blue platform for selective prodrug activation and fluorescent imaging in living systems - Linlin Yang; Shiqiong Bai; Yuqing Nie; Yixuan Li; Fei Xin; Panpan Song; Na Gao; Liguo Ji; Lili Li; Guangjie He (Analytica Chimica Acta, 2026)

Preparation of a Near-infrared Probe Based on Triphenylamine Thiophene and its Use for the Fluorescence Imaging of H2S in Living Cells - Lu Yang; Huan Li; Miaomiao Li; Aoxiang Fu; Shiqiong Bai; Jing Li; Linlin Yang; Guangjie He (Journal of Fluorescence, 2025)

LARS1 knockdown suppresses the biological activities of thyroid cancer cells by stimulating autophagy - Congwen Jin; Chuanhong Li; Linlin Chen; Hao Liu; Yousheng Yu; Benxin Chen (Tissue and Cell, 2025)

Learning to reason over multi-granularity knowledge graph for zero-shot urban land-use mapping - Yansheng Li; Yu Wang; Lei Yu; Bo Dang; Gang Xu; Zhenyu Zhong; Yuning Wu; Xin Guo; Kang Wu; Zheng Li; Linlin Wang; Jian Wang; et al. (Remote Sensing of Environment, 2025)

A LiDAR-based approach for real-time bulk coal extraction in cargo holds - Xinyi Yu; Dachuan Shi; Yuanlong Li; Kuiguang Jiao; Changrui Chen; Linlin Ou (Ocean Engineering, 2025)

June–September mean temperature variability in the eastern Qinghai-Tibet Plateau over the past 225 years based on high quality tree-ring records - Xinyue Li; Linlin Gao; Baolong Ma; Kai Wang; Yang Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Filamentous cyanobacterium Spirulina platensis mediates phosphate biomineralization for efficient fluoride immobilization and drives metabolic shift toward stress resistance and biomineralization - Linlin Cui; Zhilian Liu; Jun Suo; Yun Liu; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Journal of Hazardous Materials, 2025)

The gold, palladium, silver, copper, and silicon were synergistically recovered from the waste chips through the phase reconstruction and stepwise recovery methods - Shuo Liu; Yaobin Lai; Xin Chen; Jian Li; Hui Zhang; Linlin Chang; Tianyi Chen; Xuxia Zhang; Yangyang Xie; Liuyimei Yang; Tao Qi (Journal of Environmental Chemical Engineering, 2025)

Zein/eugenol electrospun mats on gelatin/laponite substrate for developing bilayer functional food packaging - Minmin Chen; Linlin Li; Wei Ji; Wensheng Lu; Xiaochao Tang; Suwei Jiang; Hualin Wang (Food Research International, 2025)

Tracking Browning mechanistic pathway of postharvest pine resin using comparative metabolomics - Xin Li; Junsheng Lu; Junmei Ye; Yibin Qin; Xiaopeng Chen; Jiezhen Liang; Linlin Wang (Food Chemistry, 2025)

Effect of salt stress-induced germination technology on the phenolic composition, antioxidant capacity, and metabolic pathways of highland barley (Hordeum vulgare L.): A metabolomics insight - Shuyao Wen; Disheng Xiao; Linlin Ye; Shimin Liu; Miao Liu; Xiaoyi Hou; Hui Li; Na Deng; Jianhui Wang (Food Bioscience, 2025)

Engineering yeast expression platforms: Advanced strategies for heterologous protein production and glycosylation modification - Hao Li; Taichi Chen; Zikun Zhang; Qiyi Jiang; Weigang Yuwen; Linlin Qu; Rongzhan Fu; Chenhui Zhu; Huan Lei; Daidi Fan (Chemical Engineering Journal, 2025)

Construction of temperature-responsive helical carbon nanofibers-based composites toward switchable microwave absorption - Yudi Li; Linlin Zhao; Wei Feng; Rongling Zhang; Xialong Cai; Zhiyong Chen; Hanjun Wei; Xulin Yang; Pan Wang; Giulio Cerullo; Nabil Kadhim Taieh; Fanbin Meng; et al. (Chemical Engineering Journal, 2025)

Pilot-scale investigation of polyhydroxyalkanoates synthesis using mixed microbial cultures from fermented thermally hydrolyzed sludge - Yun He; Kuixiao Li; Yu Zhang; Gang Wang; Jing Chang; Shan Hao; Linlin Wei; Xu Xing (Bioresource Technology, 2025)

Highly efficient amino-functionalized ionic liquid membrane contactor coupled system for low-concentration carbon dioxide absorption and desorption - Rui Chen; Jiayi Xu; Zhuoran Chen; Nuo Cheng; Jing Wu; Linlin Sun; Junjie Li (Bioresource Technology, 2025)

Identification for Fertility in Multigerm Sugar Beet Germplasm Resources of Molecular Markers - Jinghao Li; Linlin Sun; Zhi Pi; Shengnan Li; Zedong Wu (Sugar Tech, 2025)

Impact of drought and root excision on root regeneration, xylem hydraulics and leaf physiological characteristics in Robinia pseudoacacia - Haoyan Wei; Xiaoyun Ding; Kechen Cao; Hengjian Lai; LinLin Wang; Min Li (Plant and Soil, 2025)

CUR-PDT induces ferroptosis of RA-FLS via the Nrf2/xCT/GPX4 pathway to inhibit proliferation in rheumatoid arthritis - Lihua Sun; Yajuan Niu; Bo Liao; Linlin Liu; Yi Peng; Kaiting Li; Xinhua Chen; Qing Chen; Dingqun Bai (Inflammation Research, 2025)

Alginate-polylysine-alginate (APA) microencapsulated transgenic human amniotic epithelial cells ameliorate fibrosis in hypertrophic scars - Linlin Su; Yanhui Jia; Yan Li; Jihong Shi (Inflammation Research, 2025)

Cross-modal alignment and fusion of EEG-visual based on mixed attention mechanism for emotion recognition - Linlin Li; Wanzhong Chen (Cognitive Neurodynamics, 2025)

Evaluation of FY-4A/4B GIIRS Atmospheric Temperature Profile Products Using Radiosonde Observations through a Per-Level Collocation Method - Xiaoyue Zhang; Yuanyuan Wang; Qiang Gong; Ying Wang; Yudi Shi; Linlin Li; Guochun Li (Journal of Meteorological Research, 2025)

OWTDNet: A Novel CNN-Mamba Fusion Network for Offshore Wind Turbine Detection in High-Resolution Remote Sensing Images - Pengcheng Sha; Sujie Lu; Zongjie Xu; Jianhai Yu; Lei Li; Yibo Zou; Linlin Zhao (Journal of Marine Science and Engineering, 2025)
Real-time monitoring of offshore wind turbines (OWTs) through satellite remote sensing imagery is considered an essential process for large-scale infrastructure surveillance in ocean engineering. Current detection systems, however, are constrained by persistent technical limitations, including prohibitive deployment costs, insufficient discriminative power for learned features, and susceptibility to environmental interference. To address these challenges, a dual-branch architecture named OWTDNet is proposed, which integrates global contextual modeling via State Space Models (SSMs) with CNN-based local feature extraction for high-resolution OWTs detection. The primary branch utilizes a Mamba-structured encoder with linear computational complexity to establish long-range spatial dependencies, while an auxiliary Blurring-MobileNetv3 (B-Mv3) branch is designed to compensate for the local feature extraction deficiencies inherent in SSMs. Additionally, a novel Feature Alignment Module (FAM) is introduced to systematically coordinate cross-modal feature fusion between Mamba and CNN branches through channel-wise recalibration and position-aware alignment mechanisms. This module not only enables complementary feature integration but also enhances turbine-specific responses through attention-driven feature modulation. Comprehensive experimental validation demonstrated the superiority of the proposed framework, achieving a mean average precision (AP) of 47.1% on 40,000 × 40,000-pixel satellite imagery, while maintaining practical computational efficiency (127.7 s per image processing time).

Multi-parameter input damage limit prediction for bare reinforced concrete frames using XGBoost - Chen Xiong; Yuchao Cao; Jingfeng Zheng; Linlin Xie; Liu Mei; Lixiao Li; Wujian Long (Soil Dynamics and Earthquake Engineering, 2025)

Does soil compaction affect the mobility and transformation behavior of Arsenic -A case study of an Alfisol - Xinjun Huang; Lanting Liu; Yali Wang; Yongqiang Yang; Linlin Zhao; Rainer Horn; Liping Li (Soil and Tillage Research, 2025)

Gaussian Building Mesh (GBM): Extract a building’s 3D mesh with Google Earth and Gaussian Splatting - Kyle Gao; Dening Lu; Hongjie He; Liangzhi Li; Linlin Xu; Michael A. Chapman; Jonathan Li (Remote Sensing Applications: Society and Environment, 2025)

Terpenoids from Aglaia edulis and their lung epithelial cells protective activity - Ling Li; Qianqian Yin; Yanping Zhang; Linlin Yang; Yue Gao; Jinle Hao; Bin Lin; Di Zhou; Ning Li (Phytochemistry, 2025)

Nonlinear trajectory tracking control of UVMS with compositing fuzzy disturbance observer and robust state-dependent Riccati equation - Qirong Tang; Yuanjie Di; Tong Li; Yuanzhe Cui; Zongwu Xie; Linlin Feng; Min Yu (Ocean Engineering, 2025)

Earlywood blue intensity of Picea purpurea reveals June minimum temperature variability in Eastern Tibetan Plateau since 1671CE - Na Du; Shuhua Qiao; Baolong Ma; Xinyue Li; Linhan Si; Linlin Gao; Yang Deng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

The influence of different emulsifiers on dotted gizzard Shad (Konosirus punctatus) oil emulsions - Ying Guo; Linlin Wang; Kaiyi Wang; Li Li; Mengting Wei; Xin Wang; Zhen Wang; Baojie Jiang; Juanjuan Shao; Jilu Sun (Food Chemistry, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

Edible beeswax-flaxseed oil nanostructured lipid carriers for improved β-sitosterol bioaccessibility: structural advantages and controlled release in dynamic digestion - Lukai Ma; Zijian Li; Linjing Li; Xianhong Bi; Gengsheng Xiao; Linlin Li (Food Chemistry, 2025)

Cornus officinalis polysaccharides nano-selenium exhibits anti-fatigue effects by regulating gut microbiota in mice - Jianrui Sun; Ruirui Ren; Jinglan Li; Jiaqi Fan; Linlin Yao; Shanshan Tie; Jie Zhang; Dahong Wang; Shaobin Gu (Food Bioscience, 2025)

Consumption of fermented Cd and Pb contaminated wheat flour increases potential health risk - Weiqin Xing; Zhexu Si; James A. Ippolito; Guobing Lin; Farzana Kastury; Sen Ma; Kunyan Qiu; Linlin Zhao; Lena Q. Ma; Liping Li (Food and Chemical Toxicology, 2025)

Experimental study on mechanical properties of a new duplex stainless steel for structures under different temperature-stress combination paths - Shuobiao Li; Zhen Wang; Wenqi Ding; Qingzhao Zhang; Linlin Gu (Engineering Structures, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Preparation of MUF/α-ZrP@MnHP@APP composite nanolayered flame retardant coating for application on expanded polystyrene (EPS) foam - Wei Zhang; Yifu Xiang; Wantong Jiang; Zhixin Yang; Linlin Zhang; Bin Li (Chemical Engineering Journal, 2025)

Spin-polarization-enhanced photoreforming of plastic waste - Nan Zhou; Mai Zhang; Shiwei Lin; Linlin Zhang; Jianjun Liao; Chen Li; Wei Zhou (Chemical Engineering Journal, 2025)

Photocatalytic chitosan/hydroxypropyl methylcellulose-based multifunctional film incorporated with chlorophyll-TiO2@carbon sphere dual heterojunction and L-arginine for banana preservation - Haoran Wang; Wei Ji; Feng Xiao; Yewen Xiao; Linlin Li; Xia Shu; Hualin Wang; Jun Yin (Chemical Engineering Journal, 2025)

Chemical composition and mixing states of individual atmospheric particles in summer and winter: a micro-Raman spectroscopy study - Yan Huang; Qingcheng Li; Linlin Ye; Jingjing Wang; Yidan Zhang; Tong Zhu; Chengzhu Zhu; Mingjin Wang (Atmospheric Environment, 2025)

Mbnl1 Protects Against Cerebral Ischemia–Reperfusion Injury by Modulating Microglia/Macrophage Polarization via NF-κB Pathway - Wenting Xu; Mengjia Zhou; Linlin Li; Yuqing Zhang; Tianya Zhang; Xiangjian Zhang (Molecular Neurobiology, 2025)

An MA-film platform designed for high-throughput synthesis of calcium phosphates screening amino acid on collagen film - Xiaoyu Li; Xiran Yang; Xinkun Chen; Changxia Liu; Linlin Wu; Dazhuo Qiu; Xueye Chen; Xuetao Shi (Analytica Chimica Acta, 2025)

Topographical differentiation characteristics of double high pollution of PM2.5 and ozone in the Beijing-Tianjin-Hebei region - Huan Zhang; Xiaohong Wang; Yiheng Liang; Liyi Qin; Jinlong Li; Linlin Jiao (Air Quality, Atmosphere & Health, 2025)

Facile One-Pot Synthesis of Folic Acid-Derived Carbon Dots for Selective “on-off-on” Fluorescence Detection of Ag+ and Glutathione with High Sensitivity - Lijuan Chen; Yuting Ding; Changchang Chen; Xiaoyan Jiang; Danni Yang; Jingwen Li; Hong Liu; Linlin Yang (Journal of Fluorescence, 2025)

Coupled effects of riverbed topography and entrainment probability on bedload transport in the Middle Yangtze River - Linlin Li; Yu Lei; Junqiang Xia; Meirong Zhou; Shanshan Deng; Yao Xiao; Hang Li; Maohua Le (Acta Geophysica, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

A probabilistic formula for sediment incipient motion on combined sloping beds by considering the hiding-exposure effect - Linlin Li; Hang Li; Genguang Zhang; Yao Xiao; Defu Liu; Yu Lei; Maohua Le (Hydrological Sciences Journal, 2025)

Predicting seasonal distribution and inter-seasonal migration corridors for three subspecies of common minke whales - Linjie Li; Linlin Zhao; Shiji Xu; Changdong Liu; Yanli Tang (Ocean & Coastal Management, 2025)

Spatial planning for dugong conservation: Assessing habitat suitability and conservation gaps in Indo-Pacific Convergence Zone - Bei Wang; Kaiyu Liu; Watchara Sakornwimon; Wenhao Huang; Tingting Li; Xianshui Lai; Chengcheng Li; Linlin Zhao; Bailin Cong; Shenghao Liu (Marine Policy, 2025)

Reduced Cytochrome c: Exploring Its Promoting Function in Synergistic Denitrification by Pseudomonas sp. JM-7 and Thiobacillus denitrificans - Bobo Xing; Ji Li; Linlin Li; Nigel J.D. Graham; Xian Li; Wenzheng Yu (Water Research, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Tetraether-based temperature record from Lake Xingyun in southwestern China since late MIS3 and implication for regional differences in temperature reconstruction - Haiyang Yu; Xu Wang; Ming Ji; Shihao Zhang; Gaochao Pan; Licheng Guo; Linlin Cui; Xueyun Ma; Wubiao Li; Dongsheng Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Land use carbon emission projections in shared socioeconomic and representative concentration pathways: Relationship with urbanization in Chinese megacities - Yu Yao; Linlin Lu; Zongtang Fu; Fang Chen; Ran Wang; Qingting Li (Land Use Policy, 2025)

In silico profiling of bisphenol compounds for estrogenic effects via pharmacophore modeling, molecular docking, and dynamics simulations - Lifeng Wang; Ning Li; Linlin Wang; Zengfeng Li; Qiang Li; Jiaqi Tian; Lin Zhang (Journal of Hazardous Materials, 2025)

Superhydrophilic adsorptive nanofiber membranes for ultrafast and highly-efficient waterborne nanoplastic removal - Jingwen Zhou; Mi Zhou; Longjun Wang; Jiayu Tong; Xinhao Li; Jingru Zhou; Yuqian He; Linlin Yan; Xiquan Cheng (Journal of Hazardous Materials, 2025)

Green methanol synthesis from renewable energy integrated with compressed CO2 energy storage and waste-based systems: Thermodynamic, economic and environmental assessment - Manfeng Li; Shipeng Yin; Guofeng Zhou; Suping Li; Bo Peng; Linlin Zhang; Tianbiao He (Journal of Cleaner Production, 2025)

Simultaneous accelerating H2O2 generation and activation via construction of CuS/NiS2 heterostructures in heterogeneous electro-Fenton for sulfamerazine degradation - Chenlin Wang; Chunhui Yu; Yuhan Ma; Fan Yang; Xinyang Sun; Kexin Wei; Junpu An; Li Li; Linlin Han; Kuobo Wang; Yongfeng Li (Journal of Environmental Chemical Engineering, 2025)

Boosting dynamic NH3 adsorption performance of UiO-66 via amino-induced local polarization - Zimu Liu; Mingtai Li; Zitong Zhao; Yulong Yang; Linlin Deng; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

Simultaneous fluoride, calcium, and phosphorus removal by bacterial phosphate mineralization: Reaction pathways, mechanisms, and process optimization - Linlin Cui; Zhilian Liu; Jun Suo; Jue Kang; Yun Liu; Guanzhou Qiu; Hongbo Zhao; Li Shen (Journal of Environmental Chemical Engineering, 2025)

Hematopoietic responses to metal-organic frameworks in adult mice following pulmonary exposure - Min Li; Linlin Yao; Yuanyuan Wang; Jie Gao; Junjie Ma; Yaquan Liu; Yun Ding; Xuehan Zheng; Liqun Chen; Runzeng Liu; Li Zeng; Guangbo Qu; et al. (Journal of Environmental Sciences, 2025)

Amphiphilic Janus nanoparticles for effective foam fractionation of perfluorooctanoic acid (PFOA): Effect of modifier type - Yanfei Li; Zhuoxuan Zhang; Yanyan Lv; Yazhu Pei; Linlin Ding; Zhijun Zhang; Nan Hu (Environmental Research, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Microseismic criterion for dynamic risk assessment and warning of roadway rockburst induced by coal mine seismicity - Lianpeng Dai; Xin Zhao; Yishan Pan; Hao Luo; Yanan Gao; Aiwen Wang; Linlin Ding; Peng Li (Engineering Geology, 2025)

Sponge-like PNIPAM/Fe3O4/PPy composite hydrogel actuator with rapid response, self-sensing and multiple manipulating manners for complex application scenarios - Xingchen Cui; Bing Zhang; Pingzhi Shao; Linlin Li; Shunsheng Ye; Fuqiang Fan; Yu Fu; Fanbao Meng; Tieqiang Wang (Chemical Engineering Journal, 2025)

Waste asphalt-derived hard carbon assisted by biomass templating for sodium-ion batteries - Danqing Li; Xin He; Linlin Wang; Yinghao Zhang; Xingqiao Wu; Mei Ding; Chunhui Gao; Yang Gao; Chuankun Jia (Chemical Engineering Journal, 2025)

Bioleaching of valuable metals from spent lithium iron phosphate batteries using food-grade Lactobacillus acidophilus - Qiuli Xia; Danni Zhang; Zhong Li; Chuanwei Yang; Pan Liu; Hong Wang; Yuting Jin; Min Li; Jia Dong; Xianjun Guan; Linlin Tong; Yongqiang Fan; et al. (Chemical Engineering Journal, 2025)

Atmospheric boundary layer heat budget and its urban-rural differences in Beijing during a heatwave event - Qianyue Huang; Yuanjie Zhang; Jialing Xin; Yubin Li; Yue Qin; Linlin Wang (Atmospheric Research, 2025)

Temporin-GHaR Peptide Alleviates LPS-Induced Cognitive Impairment and Microglial Activation by Modulating Endoplasmic Reticulum Stress - Da-Qi Zhang; Xiaoqian Dong; Simin Su; Linlin Zhang; Jiayu Zhang; Wenjing Yang; Wenting Hu; Lushuang Li; Yanting Song; Xi Xie; Qifu Li; Rong Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Advances in preclinical studies of ginsenoside Rh2 in antitumor therapy - Zheng Xu; Guanghuan Shen; Zhihua Xing; Jianghan Luo; Yu Zhu; Xuan Liu; ShiHao Li; Hao Wang; Linlin Cui (Medicinal Chemistry Research, 2025)

Embryonic and Larval Development of an Interspecific Grouper Backcross Between the Kelp Grouper (Epinephelus moara) ♀ and KGGG (E. moara ♀ × E. lanceolatus ♂) ♂ - Yidan Xu; Yongsheng Tian; Shihao Wang; Tangtang Ding; Linna Wang; Zhentong Li; Linlin Li; Yang Liu (Fishes, 2025)
Backcrossing serves as an effective tool for interspecific gene introgression, facilitating germplasm improvement. To develop superior grouper aquaculture varieties, in this study, a backcrossed breed was constructed by crossing a male hybrid grouper, KGGG (Epinephelus moara ♀ × E. lanceolatus ♂), with a female parent kelp grouper (KG; E. moara). Here, we observed embryonic, larval development, and morphological changes in KG × KGGG. Additionally, the total length and body weight of the backcrossed breed and maternal parent were compared at 160 d post hatching (dph). The results showed that fertilization and the hatching rate were 73.23 ± 4.23% and 51.74 ± 3.67%, respectively, and the egg size was 0.89 ± 0.03 mm. Hatching occurred 23:19 h after fertilization at 25 ± 1 °C, and the newly hatched larvae were 1.94 ± 0.13 mm in length. Furthermore, at 160 dph, the total length and body weight of the backcrossed breed were 1.2-fold and 1.9-fold greater, respectively, when compared with those of the maternal parent. Importantly, it is possible that backcrossed KG × KGGG could become a dominant strain in grouper aquaculture practices.

Assessing Intra-Annual Spatial Distribution of Amphioctopus fangsiao in the East China Sea and Southern Yellow Sea Using Ensemble Models - Yan Cui; Xiaodi Gao; Shaobo Yang; Shengfa Li; Linlin Yang (Journal of Marine Science and Engineering, 2025)
Understanding the distribution pattern and its drivers of species is crucial for developing effective and sustainable management strategies. Amphioctopus fangsiao is the octopus of significant commercial and ecological value along the coast of China, with multiple distinct populations. However, research on their ecological dynamics remains limited and requires further investigation. Here, ensemble models were constructed to examine the spatio-temporal distribution and inter-populational differentiation in environmental adaptability of A. fangsiao in the East China Sea (ECS) and the South Yellow Sea (SYS). Specifically, we generated the ensemble models by integrating Gradient Boosting Machine (GBM), Generalized Linear Models (GLMs), and Maximum Entropy Models (MaxEnt) for the different populations across four seasons, using fishery-independent data collected from 2015 to 2021. The results revealed two hotspots of A. fangsiao in the ECS and SYS: one is the area of SYS along the coastal waters, with latitudes 33° N–34° N and longitudes 120° E–122° E (northern population, NP); the other one is near the Kuroshio-adjacent area with latitudes 28.5° N–29° N and longitudes 123° E–124.5° E (southern population, SP). Both NP and SP exhibited distinct seasonal habitat preferences, with key environmental drivers showing seasonal variations. The NP tended to inhabit coastal waters with lower sea surface heights (SSHs), shallower water depth, and a narrower sea bottom salinity range (SBS). In contrast, SP preferred marine environments with a thicker mixed layer thickness (MLT) and higher concentrations of bottom chlorophyll-a (Chl_b). The environmental characterization of suitable habitats revealed distinct patterns in resource utilization and environmental adaptation strategies between the two populations. This study provides fundamental data for understanding A. fangsiao population dynamics and underscores the importance of considering population-specific habitat preferences within dynamic marine environments.

Characterization of TGFβ Signaling Components in Large Yellow Croaker (Larimichthys crocea) and Their Role in Growth and Body Shape Regulation - Xuyang Jiang; Lu Zhang; Xin Hu; Mingchao Cui; Jie Li; Huang Liu; Linlin Yao (Journal of Marine Science and Engineering, 2025)
The transforming growth factor β (TGFβ) signaling axis plays a pivotal role in orchestrating a wide array of biological functions, encompassing cellular growth, proliferation, and differentiation. The aim of the present study was to identify the members of TGFβ signaling pathway and their expression patterns in large yellow croaker (Larimichthys crocea) under different culture modes. TGFβ signaling pathway and their expression patterns in fish reared under two different culture modes: Group N (2400 fish in a 120 m3 cage) and Group V (168,000 fish in a 5600 m3 aquaculture vessel). After 120 days, we analyzed 15 fish from each group and found that Group V exhibited faster growth and a slender body shape compared to Group N. Bioinformatics analysis identified 48 TGFβ superfamily members in L. crocea, including 21 ligands, 10 receptors, and 3 Smads. mRNA expression levels indicated that these signaling molecules influence growth rate and body shape through five distinct ligand–receptor–R-Smad pathways, with the INHBB-, Nodal-, and GDF3-ACVR2A-ALK4-Smad2 axis playing a predominant role in regulating these traits.

OA-based photo-Fenton system generates oxidizing and reducing radicals for the simultaneous removal of 1-NA and Cr (VI) in surface waters - Linlin Liang; Li Sun; Qiuwen Wang; Fuqiang Zhang; Huixue Li; Guoquan Liu; Pengfei Wang; Sihui Zhan (Water Research, 2025)

Uranium immobilization by Brevundimonas vesicularis LWG1: A synergistic approach via biomineralization, biosorption, and bioreduction - Yanru Liang; Linlin Wang; Panpan Gao; Zichu Qiu; Zemin Qin; Risheng Xu; Yue Li; Wenjuan Shuai; Jimin Li; Xueqing Geng; Hailiang Dong; Yuheng Wang (Journal of Hazardous Materials, 2025)

Thermodynamic drivers of rice glutenin Assembly: Multiscale analysis of Hierarchical structure and intermolecular bonding - Wanshan Yang; Huining Zhang; Haoyu Li; Yuhan Jiang; Zhiqi Wang; Menglu Yang; Sitong Liu; Yinyuan He; Bing Wang; Linlin Liu; Yan Wang; Fenglian Chen; et al. (Journal of Cereal Science, 2025)

Deep learning for wildfire risk prediction: Integrating remote sensing and environmental data - Zhengsen Xu; Jonathan Li; Sibo Cheng; Xue Rui; Yu Zhao; Hongjie He; Haiyan Guan; Aryan Sharma; Matthew Erxleben; Ryan Chang; Lincoln Linlin Xu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Simultaneous N-methyl pyrrolidone and total-nitrogen removals in a single aerobic process - Fei Liu; Meng Huang; Chenyu Li; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2025)

Manipulating the wastewater's ion composition to assist in the adsorption of organophosphate esters (OPEs) - Zhiqiang Li; Rongyue Wang; Wenting Jia; Linlin Shen; Pengge Ning; Hongbin Cao (Chemical Engineering Journal, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

A coupled model of surface water-groundwater interaction with the effect of riverbed deformation in the alluvial channel - Linlin Li; Hang Li; Genguang Zhang; Defu Liu; Yao Xiao; Ying Liu; Jiahao Zou (CATENA, 2025)

Melatonin Promotes Cerebral Angiogenesis in Ischemic Mice via BMP6/Smad1/5/9 Pathway - Linlin Li; Yujia Yuan; Cong Zhang; Ying Li; Renhao Xu; Xiangjian Zhang; Wenyan Shang (Molecular Neurobiology, 2025)

Smartphone-assisted portable electrochemical sensing platform for point-of-care detection of thiocyanate using a laser-induced graphene composite electrode - Xiaoming Yuan; Linlin Chen; Ruwei Liu; Shilin Li; Xiu-wen Wu; Yunhan Ling (Analytica Chimica Acta, 2025)

Identifying spatially targeted organic fertilizer subsidies for water pollution control: An interactive hydro-economic model - Shuping Wang; Pan Yang; Qian Tan; Linlin Yao; Cangbai Li (Water Research, 2025)

Preclinical models in the study of lymph node metastasis - Liya Wei; Zizhan Li; Niannian Zhong; Leiming Cao; Guangrui Wang; Yao Xiao; Bo Cai; Bing Liu; Linlin Bu (Journal of Zhejiang University-SCIENCE B, 2025)

Holocene seismically induced soft-sediment deformation structures in the Qingshuihe Basin, northeastern Tibetan Plateau - Ting Huang; Zhenhong Li; Xiaopeng Dong; Zhonghai Wu; Linlin Kou; Fang Wu (Sedimentary Geology, 2025)

Crassula perforata structured Ni3S2/NiTe electrodes enable efficient and robust seawater electrolysis at industrial-level current density - Xueling Wei; Xiangyu Zou; Qiguan Wang; Qiannan Liang; Youjun Huang; Taotao Ai; Wenhu Li; Linlin Dang; Sumin Wang (Fuel, 2025)

Synergistic effects on microstructural, rheological and functional properties of starch-enhanced processed mozzarella cheese - Linlin Tang; Jialin Liu; Ke Li; Yumeng Zhang; Shaomeng Luan; Tietao Chen; Hongjuan Li; Jinghua Yu (Food Structure, 2025)

Understanding the seasonal variation of the microplastics occurrence and source in the water source: upstream of the Huangpu River in Shanghai as an example - Zhengwen Li; Linlin Qiu; Zhaofeng Song; Kailin Gong; Xinya Gan; Cheng Peng; Xiaoyong Qian (Environmental Research, 2025)

Graphite-catalyzed carbonization of biowaste unlocks energy-dense, high-rate, and long-lifespan potassium-ion batteries - Jiale Chen; Lulu Tan; Chengye Lin; Yue Bai; Xiaogang Niu; Zhe Zhang; Nan Li; Linlin Wang; Ye Wang; Xiao Ji; Yujie Zhu (Chemical Engineering Journal, 2025)

Hesperidin-loaded self-assembled supramolecular hydrogel based on quaternized chitosan as efficient photothermal antibacterial dressing for MRSA-infected wound healing - Yamin Xiong; Yi Hao; Linlin Ding; Jinjin Li; Yuan Cao; Shuhui Fan; Fangxia Guan; Leiliang He (Carbohydrate Polymers, 2025)

Impacts of spatial resolutions of UAV-LiDAR-derived DEMs on erosion modelling in the hilly and gully Loess Plateau - Wenli Li; Pengfei Li; Lu Yan; Jinfei Hu; Leiqin Wang; Dou Li; Yang Dan; Linlin Huang; Guangju Zhao (CATENA, 2025)

Distribution of glucosinolates and antioxidants in different leaf-layers of Kale (Brassica oleracea var. acephala DC.) - Yafang Luo; Huixia Bai; Linlin Zhao; Qi Hu; Xinyuan Li; Zhenyu Fan; Yushu Wang (Physiology and Molecular Biology of Plants, 2025)

Fertilization type affects the genetic potential for phosphorus mineralization but not for phosphorus solubilization at the continental scale - Yanhong Yuan; María Belén Barquero; Yu Li; Shuiqing Zhang; Hongzhu Fan; Huimin Zhang; Qiang Li; Shutang Liu; Linlin Shi; Andong Cai; Chengjie Ren; Minggang Xu; et al. (Applied Soil Ecology, 2025)

One-step narrow-thermal-cycling strand exchange amplification for sensitive detection of porcine reproductive and respiratory syndrome virus - Linlin Zhuang; Chunlei Song; Li Sun; Haiqiang Xie; Liqun Wang; Qingxin Liu; Hongjing Shi; Jianbo Yang; Qiuping Shen (Archives of Microbiology, 2025)

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

Insight into peroxidase-mediated Pinus massoniana resin browning, and browning inhibition strategy - Hanxiao Liu; Xiaopeng Chen; Dandan Yu; Siheng Zhang; Jiezhen Liang; Xin Li; Xiaojie Wei; Linlin Wang (Sustainable Chemistry and Pharmacy, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

Mercury migration characteristics and the re-emission inhibition in seawater flue gas desulfurization system - Chuanwei Li; Gan Wan; Linlin Xu; Jiaxing Du; Lushi Sun; Li Lin (Journal of Environmental Chemical Engineering, 2025)

Phospholipids and phosphoprotein-encapsulated silver nanoparticles: An eco-friendly and green antibacterial agent for killing bacteria and promoting chronic wound healing - Qian Cai; Wenting Chen; Haoying Zhang; Chuyu Tang; Songjing Zhong; Qinyu Zhao; Zhuo Wang; Chao Wu; Liugen Zheng; Yuanyuan Cheng; Linlin Li (Journal of Environmental Chemical Engineering, 2025)

Promoting oxidation of high concentration CO via strong metal support interaction in unreduced Pt-based catalysts - Yulong Yang; Xiaokun Yi; Linlin Deng; Zitong Zhao; Zimu Liu; Mingtai Li; Baojuan Dou; Feng Bin (Journal of Environmental Chemical Engineering, 2025)

Floated Bi4Ti3O12@MoS2 p-n heterojunction anti-fouling hydrogels for efficient seawater purification - Ying Liu; Bingyan Ni; Ruotong Ru; Linlin Zhang; Hongfei Sun; Jianjun Liao; Cheng Li; Dexin Wang; Xiaodong Zhang; Wei Zhou (Journal of Environmental Chemical Engineering, 2025)

Integration of lipidomics and flavoromics reveals the lipid-flavor transformation mechanism of fish oil from silver carp visceral with different enzymatic hydrolysis - Jinlin Li; Liping Yuan; Linlin Weng; Chengwei Yu; Mingming Hu; Bin Peng; Zongcai Tu (Food Chemistry, 2025)

Quantitative proteomic analysis reveals target proteins of benzyl isothiocyanate against multidrug-resistant Staphylococcus aureus - Xujia Ming; Hongbo Li; Na Li; Zhenbin Liu; Linlin Zhu; Haizhen Mo; Liangbin Hu (Food Bioscience, 2025)

Enhanced viability of Lactiplantibacillus plantarun by encapsulation with whey protein isolate fibrils and polysaccharides through layer-by-layer coating - Siyuan Li; Wei Su; Yu Zhang; Wanling Gan; Xiaoli Liu; Linlin Fan (Food Hydrocolloids, 2025)

Dual-responsive gelatin/fucoidan-based membrane with colorimetric and control-released performance for meat freshness monitoring and preservation - Linlin Li; Haoran Wang; Yimeng Zhang; Wei Ji; Minmin Chen; Baocai Xu; Hualin Wang (Food Packaging and Shelf Life, 2025)

Glycyrrhizic acid alleviates gefitinib-induced liver injury by regulating the p53/p21 pathway and releasing cell cycle arrest - Min Li; Shuaijun Peng; Jingjing Bu; Siqi Quan; Liming Liu; Zhouli Yue; Linlin Wang; Yucheng Li (Food and Chemical Toxicology, 2025)

Synergizing lattice matching and transient N–Li bonds to boost sulfur redox kinetics and regulate uniform lithium deposition in practical Li–S batteries - Yantao Wang; Huiqin Chen; Wenjuan Wu; Jinlong Li; Guangxin Zhang; Chunyan Wei; Shiyu Wang; Linlin Zhang; Yanping Zheng; Huanhuan Li (Chemical Engineering Journal, 2025)

Performance and mechanism of tris(2-chloropropyl) phosphate (TCPP) removal in an iron-carbon microelectrolysis constructed wetland system - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Chemical Engineering Journal, 2025)

Hydrological Connectivity Induces Changes in Macrobenthos Functional Feeding Groups in a Typical Tidal Creek System of the Yellow River Delta - Qinglu Fu; Li Chen; Debin Sun; Jiao Wang; Jing Chen; Baoquan Li; Linlin Chen (Wetlands, 2025)

Climate evolution and its driving factors in the Tethys Sea region during the Cenozoic - Jiangbo Meng; Jiagang Zhao; Linlin Chen; Paul J. Valdes; Alex Farnsworth; Svetlana Popova; Mine Sezgül Kayseri-Özer; Gaurav Srivastava; Jian Huang; Tao Su; Zhekun Zhou; Shufeng Li (Science China Earth Sciences, 2025)

Combined toxicity of decabromodiphenyl ethane and Pb on earthworms (Eisenia fetida) based on multiple biomarker responses - Meiqing Jin; Yuanchao Sun; Bing Chai; Minghu Wang; Yuping Wu; Weihong Wu; Qingwei Zhou; Linlin Qiu; Jia Du; Li Fu (Journal of Soils and Sediments, 2025)

Protective effects of resveratrol on honeybee health: Mitigating pesticide-induced oxidative stress and enhancing detoxification - Linlin Liu; Min Shi; Yanyan Wu; Jiali Hao; Junxiu Guo; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2025)

Changes in intergranular air properties and fatty acid profile of wheat bulk in a large warehouse with air-conditioned oversummering - Mengya Wang; Minghui Zhao; Xuhui Zhuang; Jianzhang Wu; Xingjun Li; Linlin Song; Yushan Jiang (Journal of Stored Products Research, 2025)

Optimized immobilization of lead and cadmium in soil using dithiocarboxy functionalized silica: A long-term effectiveness study - Mingming Lian; Chaoran Li; Longfei Wang; Liyong Niu; Linlin Zhao; Dongdong Wu; Zongsheng Zhao; Xiaohong Li; Zhijun Zhang (Journal of Hazardous Materials, 2025)

Planning conservation priority areas for marine mammals accounting for human impact, climate change and multidimensionality of biodiversity - Linjie Li; Yanli Tang; Hao Dong; Linlin Zhao; Changdong Liu (Journal of Environmental Management, 2025)

3D semantic segmentation: Cluster-based sampling and proximity hashing for novel class discovery - Jing Du; Linlin Xu; Lingfei Ma; Kyle Gao; John Zelek; Jonathan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Spatiotemporal variations of dissolved nitrous oxide concentrations in small water bodies in a typical urban landscape in eastern China - Xuebing Chen; Yuye Shen; Yihong Liu; Fangfang Zhang; Linlin Tian; Jing Wang; Yanjiang Cai; Yan Li; Scott X. Chang (Environmental Pollution, 2025)

Size-dependent internalization of gold nanoparticles in individual Tetrahymena thermophila characterized by single-cell mass cytometry - Junjie Ma; Yaquan Liu; Liu Zhang; Linlin Yao; Yun Ding; Hua Qin; Ziniu Wang; Xuehan Zheng; Xinyue Yang; Haijiang Tian; Li Zeng; Liqun Chen; et al. (Environmental Pollution, 2025)

Computational fluid dynamics and machine learning assisted Al-LDH adsorbent reactor design for lithium recovery from salt lakes - Jiangtao Yu; Minmeng Tang; Peng Cui; Jianquan Deng; Haiying Mi; Li Zhang; Linlin Chen; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2025)

Physiological and transcriptomic responses of the microalga Isochrysis galbana during exposure to Hg(II) stress - Linlin Zhang; Na Li; Xinfeng Xiao; Linke Guo; Wenfang Li; Yanjun Li; Fei Ling (World Journal of Microbiology and Biotechnology, 2025)

The role of immunoglobins in atherosclerosis development; friends or foe? - Linlin Zhang; Peize Li; Yuhui Li; Wantong Qu; Yanyu Shi; Tianyang Zhang; Ying Chen (Molecular and Cellular Biochemistry, 2025)

Source identification of polycyclic aromatic hydrocarbons (PAHs) in river sediments within a hilly agricultural watershed of Southwestern China: an integrated study based on Pb isotopes and PMF method - Fen Xu; Chunmei Jiang; Qiang Liu; Rui Yang; Weiwei Li; Yao Wei; Linlin Bao; Hongjin Tong (Environmental Geochemistry and Health, 2025)

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Seasonal and spatial distribution of AmphiOctopus fangsiao and Octopus variabilis in the southern Yellow and East China Seas: Fisheries management implications based on climate scenario predictions - Linlin Yang; Min Xu; Zunlei Liu; Yi Zhang; Yan Cui; Shengfa Li (Regional Studies in Marine Science, 2025)

Boosting catalytic performance of N doped porous carbon derived from coal tar pitch: The role of N species and the contribution of 1O2 - Linlin Huang; Xuwen Zhang; Lin Wang; Tingting Liu; Da Li; Tao Sheng; Caiyu Sun; Lixin Li (Journal of Water Process Engineering, 2025)

The dewatering performance of streptomycin mycelial residue promoted by the Fenton process synergistic with biochar - Lushi Sun; Jiaxing Du; Xingxing Zhou; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Management, 2025)

Dust removal process of the multi-filter cartridges and its optimization measures for coal dust pollution: Experimental and numerical investigations - Geng Fan; Li Linlin; Huang Ruoxi; Li Shihang; Shi Wentao; Chang Binbin; Peng Zhengbiao; Xia Yuyang (Journal of Environmental Chemical Engineering, 2025)

Pore structure-dependent adsorption of monochloramine by activated carbon - Xin Cheng; Xiaojun Miao; Linlin Li; Xueyan Xue; Xinqian Zhang; Jiao Yin (Journal of Environmental Chemical Engineering, 2025)

Evaluation of the virulence characteristics of ST11 Salmonella enterica from different sources using a 2D cell model - Linlin Xiao; Yulin Long; Binru Gao; Ying Hu; Tantao Zhang; Qian Xiao; Xiaojie Qin; Xuejuan Xia; Xiang Wang; Zhuosi Li; Qingli Dong (International Journal of Food Microbiology, 2025)

Correlation between the physicochemical and bacteriological qualities of pickled chili pepper (Paojiao) and its nitrite degradation study - Jianhui Wang; Miao Liu; Linlin Ye; Xiaoyi Hou; Zhenyu Li; Linzhi Tang; Na Deng; Hui Li (Food Bioscience, 2025)

Tanshinone IIA@β-cyclodextrin encapsulated with Eucommia ulmoides rubber/acetylated starch film as novel oral delivery system for therapy of orthotopic colon cancer - Rui Zhao; Haoyu Wang; Shuyao Li; Lingling Wang; Xiaopeng Lei; Pai Peng; Linlin Du; Juane Dong (Carbohydrate Polymers, 2025)

Modeling of sediment exchange process and channel evolution in the downstream reach below the Three Gorges Dam - Linlin Li; Junqiang Xia; Meirong Zhou; Shanshan Deng; Defu Liu; Hang Li; Yu Lei (CATENA, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Chaetocin inhibits the progression of neuroblastoma by targeting JAK2/STAT3 signaling pathway in SH-SY5Y cells - Ke Wang; Ye Li; Linlin Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Influence of ocean-atmosphere interactions on typhoon track and intensity: a case study for typhoon “Hato” (1713) - Yonghang Chen; Yu Wei; Yunxia Zheng; Xianwen Wu; Qiong Liu; Ruixue Li; Linlin Sun; Bingke Zhao; Sijie Yin; Haicheng Liu; Xiaoyu Li (Natural Hazards, 2025)

An adaptive session-incremental broad learning system for continuous motor imagery EEG classification - Yufei Yang; Mingai Li; Linlin Wang (Medical & Biological Engineering & Computing, 2025)

Environmental heterogeneity drives the spatial distribution of macrobenthos in the Yellow River Delta wetland - Qinglu Fu; Jiao Wang; Debin Sun; Jianyu Chi; Wenzheng Fan; Yu Li; Yilin Wang; Baoquan Li; Linlin Chen (Aquatic Sciences, 2025)

Exploring Boundary Layer Physics and Atmospheric Chemistry in Megacities: Insights from the Beijing 325 m Meteorological Tower - Yele Sun; Zifa Wang; Linlin Wang; Xueling Cheng; Weiqi Xu; Yu Shi; Wei Zhou; Yan Li; Fei Hu; Zhiqiu Gao; Zhongxiang Hong (Advances in Atmospheric Sciences, 2025)

An enhanced machine learning model for urban air quality forecasting under intense human activities - Yelin Wang; Feiyang Xia; Linlin Yao; Shunyu Zhao; Youjie Li; Yanpeng Cai (Urban Climate, 2025)

Host selection shapes structure and network of microbial community of Epimedium plants along the soil–rhizosphere–plant continuum - Zhaoyu Zhang; Ziying Huang; Xiao Chen; Guozhuang Zhang; Mengzhi Li; Anning Li; Xiaolin Lin; Yuxin Zhou; Yu Zhang; Shilin Chen; Linlin Dong; Guangfei Wei (Rhizosphere, 2025)

Antifungal activity and active compound identification of Myrothecium spp. against grape anthracnose and gray mold - Linlin Gao; Yijie Zhai; Jiajia Wu; Yuwei Li; Yanchun Fan; Junqiang Guo; Xiping Wang; Zhi Li (Pesticide Biochemistry and Physiology, 2025)

Mercury (II) adsorption and gaseous mercury re-emission inhibition from seawater flue gas desulfurization (SFGD) wastewater by Fe-Cu bimetallic modified activated carbon - Lushi Sun; Gan Wan; Ke Tang; Linlin Xu; Li Lin (Fuel, 2025)

Residual behaviors and health risk assessment of dinotefuran, flonicamid, and their metabolites during apple growth, storage, and processing - Fajun Tian; Zhenzhen Zhou; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Food Research International, 2025)

Enhancement of farinographic characteristics of rice dough and rice bread quality with combined chemical and enzymatic approaches - Huining Zhang; Wanshan Yang; Yuhan Jiang; Haoyu Li; Menglu Yang; Zhiqi Wang; Bing Wang; Linlin Liu; Hongchen Fan; Fenglian Chen; Ying Liu (Food Bioscience, 2025)

Butyrylated modification of corn starch alleviates autism-like behaviors by modulating 5-hydroxytryptamine metabolism and gut-brain neural activity - Wentian Li; Qingmin Kong; Min Guo; Linlin Wang; Peijun Tian; Jingyu Lu; Jianxin Zhao; Wei Chen; Gang Wang (Carbohydrate Polymers, 2025)

Bivariate Spatial Autocorrelation Analysis of Keshan Disease and Hair Selenium of Residents in Heilongjiang Province, China - Jiacheng Li; Guijin Li; Cheng Wang; Huixin Sun; Linlin Du; Shuxiu Hao; Qingyu Zeng; Cunqi Lv; Yu Zhang; Xinshu Wang; Zhifeng Xing; Tong Wang (Biological Trace Element Research, 2025)

Spatial Clusters of Low Serum Selenium: the Priorities of Selenium Supplementation to Residents of Keshan Disease Endemic Areas - Qingyu Zeng; Guijin Li; Ruixiang Wang; Cunqi Lv; Shuxiu Hao; Jiacheng Li; Huixin Sun; Linlin Du; Cheng Wang; Yu Zhang; Xinshu Wang; Yuehui Jia; et al. (Biological Trace Element Research, 2025)

A real-time vision guidance method for autonomous longan picking by the UAV - Hengxu Chen; Kaixuan Wu; Hengyi Lin; Haobo Zhou; Zhengqi Zhou; Yuju Mai; Linlin Shi; Meiqi Zhang; Zhe Ma; Peihan Lin; Jun Li (Computers and Electronics in Agriculture, 2025)

Rapid, green and semi-automated PT-μSPE for antidepressants analysis in urine and plasma using melt-blown polypropylene from disposable face masks as sorbent - Qianwei Li; Bowen Deng; Ru Feng; Di Chen; Linlin Hua (Sustainable Chemistry and Pharmacy, 2025)

Bacterial community composition and metabolic characteristics of three representative marine areas in northern China - Huameng Ge; Chengcheng Li; Conghui Huang; Linlin Zhao; Bailin Cong; Shenghao Liu (Marine Environmental Research, 2025)

Influence of atomic coordination on the activity of lattice oxygen and catalytic oxidation of toluene over regular Cu2O crystalline - Linlin Deng; Mingtai Li; Xin Gao; Xiaokun Yi; Yang Zhao; Yulong Yang; Zitong Zhao; Jiarui Chen; Baojuan Dou; Feng Bin (Journal of Hazardous Materials, 2025)

The role of telomere shortening in ambient ozone exposure-related insulin resistance - Ruiying Li; Gongbo Chen; Wei Liao; Yinghao Yuchi; Xiaohuan Yang; Ziyuan Zhang; Xiaotian Liu; Zhenxing Mao; Linlin Li; Jiahui Zhao; Huijun Li; Wenqian Huo; et al. (Journal of Hazardous Materials, 2025)

Improvement of 3D printing and subsequent microwave freeze-drying solidification accuracy of pineapple gel-based inks: Infill percentage control and internal models design - Yunfei Bao; Wenchao Liu; Linlin Li; Guangyue Ren; Chung Lim Law; Weiwei Cao; Jiayao Wang; Zhenjiang Luo; Junliang Chen; Xu Duan (Journal of Food Engineering, 2025)

Using the Forel-Ule index (FUI) to track the water quality of subsidence water bodies across the life cycle of coal mining in eastern China - Wenqi Chen; Lijuan Chen; Yongping Wei; Linlin Ruan; Yanhua Fu; Wei Li; Tingting He; Wu Xiao (Journal of Environmental Management, 2025)

About 868 cal. yr BP tsunami event at the northern South China Sea revealed from offshore sediments - Yuming Wang; Xiaohong Chen; Adam D. Switzer; Linlin Li; Yang Xu; Yukun Wang; Elaine Tan; Peizhen Zhang (Global and Planetary Change, 2025)

Electronic engineering induced ultrafine non-noble nanoparticles for high-performance hydrogen evolution from ammonia borane hydrolysis - Siyuan Tang; Linlin Xu; Xiang Ding; Quanjiang Lv; Haotian Qin; Aosong Li; Xinchun Yang; Jian Han; Fuzhan Song (Fuel, 2025)

Ecological restoration orientated application and modification of constructed wetland substrates - Jiapeng Yang; Shuiping Cheng; Yongqiang Wang; LinLin Li; Shaoyong Lu (Environmental Research, 2025)

Impact and mechanism of polyethylene terephthalate microplastics with different particle sizes on sludge anaerobic digestion - Qing Yang; Jiaxin Li; Linlin Ma; Xue Du (Environmental Pollution, 2025)

Improving forest gross primary productivity estimation through climate and trait integration - Hongge Ren; Li Zhang; Min Yan; Bo Zhang; Linlin Ruan (Ecological Modelling, 2025)

Earthquake-induced Submarine Landslides (EQISLs) and a comparison with their Terrestrial Counterparts: Insights from a New Database - Peng Du; Linlin Li; Achim Kopf; Dawei Wang; Kejie Chen; Huabin Shi; Weitao Wang; Xiaoyi Pan; Gui Hu; Peizhen Zhang (Earth-Science Reviews, 2025)

Compound heterozygous mutation of AFG3L2 causes autosomal recessive spinocerebellar ataxia through mitochondrial impairment and MICU1 mediated Ca2+ overload - Hongyu Li; Qingwen Ma; Yan Xue; Linlin Cai; Liwen Bao; Lei Hong; Yitao Zeng; Shu-Zhen Huang; Richard H. Finnell; Fanyi Zeng (Science China Life Sciences, 2025)

Ferroptosis-Related Gene Signatures in Epilepsy: Diagnostic and Immune Insights - Xueying Li; Lei Wu; Linlin Sun; Han Liu; Xuezhu Qiao; Na Mi; Shi Yan; Xinyu Zhang; Kun Wang; Pusheng Quan; Fan Yang; Lifen Yao (Molecular Neurobiology, 2025)

Protective effect of Apelin-13 on oxygen and glucose deprivation induced-damage in retinal ganglion cells cultured in vitro - Li Dai; Linlin Luo; Ya Zhang; Min Fu; Ling Yu (Journal of Molecular Histology, 2025)

A 219-year tree-ring evidence revealing the influence of the Atlantic Multi-decadal oscillation on annual mean temperature in the northern Western Sichuan Plateau - Xu Wu; Jinjian Li; Linlin Cui; Xiaofei Wu; Kaiqing Yang; Alma Lorelei de Jesus (Climate Dynamics, 2025)

Provincial localization framework for SDGs in China: Enhancing support for sustainable governance - Wen Song; Shisong Cao; Mingyi Du; Linlin Lu; Huadong Guo; Sirui Wang; Yue Liu; Xiaoxuan Li (Applied Geography, 2025)

RBM15 Knockdown Impairs the Malignancy of Cervical Cancer by Mediating m6A Modification of Decorin - Huimin Wang; Chun Li; Qiong Wei; Enjing Zhang; Yi Yang; Linlin Sha; Dan Wang (Biochemical Genetics, 2025)

Effect of Feeding Mice Soluble Metals and Heavy Metal Contaminated Soil on Feces Metal Concentrations - Ningning Xu; Liping Li; James A. Ippolito; Weiqin Xing; Yale Wang; Baozhong Zhang; Yongqiang Yang; Ling Bai; Linlin Zhao (Biological Trace Element Research, 2025)

A comprehensive review on iron‒carbon microelectrolysis constructed wetlands: Efficiency, mechanism and prospects - Yongqiang Wang; Linlin Li; Xiaochun Guo; Aiwen Wang; Yunhao Pan; Jun Ma; Shaoyong Lu; Dongmei Liu (Water Research, 2025)

Salmonella enterica serovar typhimurium effectors spiA and spiC promote replication by modulating iron metabolism and oxidative stress - Keyuan Chen; Jing Wang; Ting Hu; Yiqing Zhao; Yi Wu; Xue Wang; Wei Li; Guiyan Yang; Linlin Zhang; Jiufeng Wang; Yaohong Zhu (Veterinary Microbiology, 2025)

Cropping systems and ecological groups of soil animals jointly affect the transfer of root-derived carbon and mineral nitrogen into the soil food web - Linlin Zhong; Zhipeng Li; Lingling Shi; Thomas Larsen; Stefan Scheu; Melanie M. Pollierer (Soil Biology and Biochemistry, 2025)

Indian summer monsoon variations since late MIS3: A perspective from multiproxy evidence from Lake Xingyun in southwestern China - Haiyang Yu; Linlin Cui; Xu Wang; Xueyun Ma; Bing Xu; Wubiao Li; Xueting Wang (Quaternary International, 2025)

Corrigendum to “The latest activity of the slope fault zone (Pearl River Mouth) in northern South China Sea and implications for earthquake hazard assessments” [166 (2024) 106937] - Liangwei Lv; Zhigang Li; Dawei Wang; Weitao Wang; Xiangming Dai; Fanchang Zeng; Linlin Li; Hao Liang; Gege Hui; Weiwang Long; Peizhen Zhang (Marine and Petroleum Geology, 2025)

Metagenomics and metaproteomics reveal the effects of sludge types and inoculation modes on N,N-dimethylformamide degradation pathways and the microbial community involved - Yunchuan Xian; Linlin Cao; Yuxiang Lu; Qiuhong Li; Chengyuan Su; Yuan He; Guangrong Zhou; Shenglong Chen; Shu Gao (Journal of Hazardous Materials, 2025)

Efficient and low resistance multi-functional UV resistant polyphenylene sulfide non-woven hollow membrane - Mengen Zhang; Qiyang Xi; Linlin Wang; Qinxing Xie; Zhenhuan Li; Maliang Zhang (Journal of Environmental Management, 2025)

Optimization model for co-pyrolytic synergy: A case study in starch sludge with chicken manure and comprehensive investigation combining kinetics, bio-products characterization, and DFT-based decomposition pathways - Hairong Mo; Xiaopeng Chen; Tongxi Mo; Chenghong Wu; Wanbin Wei; Yuanjie Wu; Qinxin Li; Jiezhen Liang; Linlin Wang (Fuel, 2025)

Enhanced dechlorination for multi-source solid wastes using gas-pressurized torrefaction and its removal mechanism - Jia Fu; Linlin Yi; Kaiyuan Li; Yan Zhang; Tong Zhang; Aijun Li; Tianrun Wang; Yanyan Zou; Xian Li; Hong Yao (Chemical Engineering Journal, 2025)

Bimetallic RuCo anchored CoFe2O4 nanosheets to realize in-depth electronic modulation for boosted structural reconstruction and efficient seawater electrolysis - Xueling Wei; Youjun Huang; Qiguan Wang; Linlin Dang; Kai Zhang; Qing Guo; Wenhu Li; Taotao Ai; Sumin Wang (Chemical Engineering Journal, 2025)

2D manganese-doped calcium carbonate nanosheets as activable MRI/US imaging Guided enhanced calcium influx for Boosted regulatory cell death - Mingya Tan; Linlin Huo; Jie Zeng; Shiqi Zhu; Jianfeng Bao; Mengke Fan; Jiangyang Li; Meiling Liu; Jiayi Zhao; Zhenghuan Zhao (Chemical Engineering Journal, 2025)

Comprehensive host cell proteins profiling in biopharmaceuticals by a sensitivity enhanced mass spectrometry strategy using TMT-labeling and signal boosting - Andong Xue; Linlin Kong; Jialin Li; Yuxin Jiao; Zhishang Hu; Bin Fu; Guibin Wang; Wanjun Zhang; Jianheng Li; Weijie Qin (Analytica Chimica Acta, 2025)

Study on strengthened the Cd(II) adsorption based on co-culture of fungi and cyanobacteria - Linlin Cui; Junjun Wang; Xueling Wu; Jiaokun Li; Weimin Zeng; Guanzhou Qiu; Li Shen (Algal Research, 2025)

Towards a dialectical understanding of rural resilience and rural sustainability: bibliometric analysis and evidence from existing literature and China - Huan Li; Tao Xu; Chen Yang; Yang Fu; Changyan Wu; Linlin Zhang; Guoliang Xu; Wei Wang (Environment, Development and Sustainability, 2024)

Threshold of sediment incipient motion on a three-dimensional riverbed by considering the hiding-exposure effect with experimental investigations - Linlin Li; Yao Xiao; Genguang Zhang; Yu Lei; Hang Li; Defu Liu (Acta Geophysica, 2024)

Temperature related to the spatial heterogeneity of wetland soil total nitrogen content in a frozen zone - Linlin Wu; Mingchang Wang; Dehua Mao; Xiaoyan Li; Zongming Wang (Soil and Tillage Research, 2024)

Impact of chlorantraniliprole on honey bees: Differential sensitivity and biological responses in Apis mellifera and Apis cerana - Wenmin Li; Yikun Zan; Tong Wu; Sa Yang; Linlin Liu; Shanshan Li; Pingli Dai; Jing Gao (Science of The Total Environment, 2024)

Widespread presence of gut bacterium Glutamicibacter ectropisis sp. nov. confers enhanced resistance to the pesticide bifenthrin in tea pests - Xiayu Li; Ting Fang; Tian Gao; Hao Gui; Ying Chen; Linlin Zhou; Yong Zhang; Yunqiu Yang; Letian Xu; Yanhua Long (Science of The Total Environment, 2024)

Transfer dynamics of antimicrobial resistance among gram-negative bacteria - Bangjuan Wang; Muhammad Haris Raza Farhan; Linlin Yuan; Yuxin Sui; Jinhua Chu; Xiaohan Yang; Yuxin Li; Lingli Huang; Guyue Cheng (Science of The Total Environment, 2024)

Organotin exposure and DNA methylation in non-syndromic cleft lip and palate: Integrating findings from case-control studies and animal experiments - Yongyan Chen; Qianhui Cheng; Sainan Li; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Science of The Total Environment, 2024)

Individual tree species classification using low-density airborne multispectral LiDAR data via attribute-aware cross-branch transformer - Lanying Wang; Dening Lu; Linlin Xu; Derek T. Robinson; Weikai Tan; Qian Xie; Haiyan Guan; Michael A. Chapman; Jonathan Li (Remote Sensing of Environment, 2024)

NIR spectroscopy for quality assessment and shelf-life prediction of kiwifruit - Hongbo Li; Linlin Zhu; Na Li; Zhenbin Liu; Liheng Wang; Bimal Chitrakar; Dan Xu; Zhenkun Cui; Yanhua Tang; Liangbin Hu; Haizhen Mo (Postharvest Biology and Technology, 2024)

Numerical modeling of graded sediment transport with limited bed material supply – A case study in the Middle Yangtze River - Linlin Li; Junqiang Xia; Meirong Zhou; Shanshan Deng; Jie Li; Yao Xiao (Journal of Hydrology, 2024)

Electronic structure regulation of Cu-based Ruddlesden-Popper perovskites by cobalt doping for enhanced degradation of oilfield fracturing wastewater in electrocatalytic peroxymonosulfate system - Xin Liu; Jingyang Li; Yuexiang Li; Jian Fu; Chengzhi Liu; Linlin Yang (Journal of Environmental Chemical Engineering, 2024)

High mechanical property, hydrophobic and fire-retardant cellulose film derived from kenaf degumming wastewater - Shixing Wang; Xiaolong Qiao; Linlin Li; Hailong Lu; Yuanming Zhang; Guangting Han; Haoxi Ben; Wei Jiang (Journal of Environmental Chemical Engineering, 2024)

Elementomics of 32 elements in cord serum depicts the risk of orofacial clefts: A case-control study in Shanxi, China - Jing Wei; Dezheng Fu; Siyu Guo; Tian Tian; Yun Huang; Zhiwen Li; Linlin Wang; Lei Jin; Weiping Ye; Aiguo Ren; Shengju Yin (Environmental Pollution, 2024)

Prenatal co-exposure to phthalate metabolites and bisphenols among non-syndromic cleft lip and/or palate in offspring - Sainan Li; Haiyan Zhu; Chen Yang; Chengrong Wang; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Environmental Pollution, 2024)

Closed-loop recylcing of thermoset poly(vinylogous urethane) foams - Shihao Ji; Linlin Wang; Shengyu Feng; Lei Li (Chemical Engineering Journal, 2024)

Enhanced peracetic acid activation under Far-UVC Radiation: Micropollutant degradation and radical assessment - Tao Yang; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Chenlong Liu; Bin Zhang; Haochen Zhang; Linlin Zang; Minchao Liu; Jun Ma (Chemical Engineering Journal, 2024)

High efficient synthesis of benzyl lactate through waste PLA alcoholysis by protic ionic salt - Chenxi Zhu; Linlin Yang; Yueru Li; Yunbiao Qi; Guixiang Zeng; Wei Jiang (Chemical Engineering Journal, 2024)

Precise fabrication and superior combustion properties of n-B pomegranate microspheres based on a new dissolution-dispersion-coating method - Yushu Xiong; Baoxuan Li; Yinghong Wang; Linlin Liu; Jie Huang; Suhang Chen; Fengqi Zhao; Kangzhen Xu (Chemical Engineering Journal, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

Biocontrol potential of plant growth-promoting rhizobacteria against plant disease and insect pest - Qinhao Jian; Tongrui Zhang; Yingying Wang; Li Guan; Linlin Li; Longna Wu; Shiyan Chen; Yumei He; Hong Huang; Shugang Tian; Hu Tang; Litang Lu (Antonie van Leeuwenhoek, 2024)

Evaluation of Tembusu virus single-round infectious particle as vaccine vector in chickens - Yunzhen Huang; Zhe Liu; Junqin Zhang; Jiawen Dong; Linlin Li; Yong Xiang; Ruihuan Kuang; Shimin Gao; Minhua Sun; Yongjie Liu (Veterinary Microbiology, 2024)

ChatEV: Predicting electric vehicle charging demand as natural language processing - Haohao Qu; Han Li; Linlin You; Rui Zhu; Jinyue Yan; Paolo Santi; Carlo Ratti; Chau Yuen (Transportation Research Part D: Transport and Environment, 2024)

Unraveling the effect of electricity price on electric vehicle charging behavior: A case study in Shenzhen, China - Haoxuan Kuang; Xinyu Zhang; Haohao Qu; Linlin You; Rui Zhu; Jun Li (Sustainable Cities and Society, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Source identification of microplastics in highly urbanized river environments and its implications for watershed management - Huaihao Shao; Qiankun Wang; Linlin Wang; Xiaoyu Lei; Shuangliang Dai; Tian Li; Xiaoshan Zhu; Xian-zhong Mao (Science of The Total Environment, 2024)

Artificial river flow regulation triggered spatio-temporal changes in marine macrobenthos of the Yellow River Estuary - Debin Sun; Jiao Wang; Qinglu Fu; Linlin Chen; Jing Chen; Teng Sun; Baoquan Li (Marine Environmental Research, 2024)

Migration of depleted uranium from a corroded penetrator in soil vadose zone in Bosnia and Herzegovina - Cui Li; Yanru Liang; Yin Ye; Fan Chen; Markus Astner; David J. Paterson; Yanlong Chen; Linlin Wang; Paul Guagliardo; Matvei Aleshin; Mario Burger; Peter M. Kopittke; et al. (Journal of Hazardous Materials, 2024)

Insights of using microbial material in fluoride removal from wastewater: A review - Linlin Cui; Junjun Wang; Hao Zhou; Shiyu Shao; Jue Kang; Xinyi Yu; Hongbo Zhao; Li Shen (Journal of Environmental Management, 2024)

Molecular epidemiological investigation of Salmonella isolated from the environment, animals, foods and patients in China - Linlin Xiao; Xiaojie Qin; Hu Xiao; Yuehua Gao; Tanmei Sun; Xiaolu Dong; Yulin Long; Xuejuan Xia; Zhuosi Li; Xiang Wang; Qingli Dong (Food Research International, 2024)

Rational design of pulse-electrolysis protocols promotes molten-salt electrorefining - Leyang Li; Ruiyang Sun; Rui Yuan; Manpeng Lin; Linlin Wang; Qi Wang; Jiguo Tu; Handong Jiao; Shuqiang Jiao (Chemical Engineering Journal, 2024)

A metal-quercetin-histidine co-coordinated nanoparticle enhances cancer photothermal therapy via reshaping immunosuppressive tumor microenvironment - Shaobo Wang; Shuncheng Yao; Quanhong Hu; Zhuo Wang; Yunchao Zhao; Linlin Li (Chemical Engineering Journal, 2024)

Integrated proteome and pangenome analysis revealed the variation of microalga Isochrysis galbana and associated bacterial community to 2,6-Di-tert-butyl-p-cresol (BHT) stress - Linke Guo; Shuangwei Li; Dongle Cheng; Xiao Lu; Xinying Gao; Linlin Zhang; Jianjiang Lu (World Journal of Microbiology and Biotechnology, 2024)

New Insights into Fish Diversity in the Yellow and Bohai Seas Based on Environmental DNA Technology - Xiaolin Wang; Li Wang; Aiyong Wang; Linlin Zhao (Fishes, 2024)
Marine biodiversity is increasingly threatened by overfishing and marine pollution. A comprehensive understanding of the biodiversity in the Yellow and Bohai Seas is essential for resource conservation. This study conducted a large-scale survey of fishery resources in the Yellow and Bohai Seas to investigate fish community structure and diversity using eDNA technology. The results showed that 57 and 65 fish species were recorded in spring and summer, respectively, with 46 species identified in both seasons. A total of nine dominant species were identified in spring, mainly belonging to Perciformes, while seven dominant species were identified in summer, primarily from Clupeiformes. In different regions, no significant differences in fish α diversity were observed between spring and summer. However, significant seasonal differences were found in both α and β diversity. At the spatial level, fish species in the Yellow and Bohai Seas occupied similar ecological niches. However, at the temporal level, there are certain differences in the ecological niches of fish communities between seasons. Phylogenetic diversity showed no significant differences at the spatial scale, yet notable seasonal variations were observed at the temporal scale, with spring (661.46) significantly exceeding summer (540.30). The Mantel test indicated that nitrate and salinity were key environmental factors influencing α diversity. RDA analysis revealed that the dominant species in spring were mainly influenced by chlorophyll-a and water temperature, while those in summer were mainly affected by water depth, nitrite, water temperature, and salinity.

Insights into the uptake, accumulation, and metabolism of UV-328 in lettuce (Lactuca sativa L.) and radish (Raphanus sativus L.) - Bingru Li; Zhenzhen Yao; Qi Liu; Linlin Guo; Zhihong Ma; Cheng Li (Chemosphere, 2024)

Decadal variation and temporal stability of the macrobenthic community in the Bohai Sea, China - Shaoyu Jiang; Jiao Wang; Wenzheng Fan; Linlin Chen; Jing Chen; Baoquan Li (Marine Pollution Bulletin, 2024)

Effect of silicon on the distribution and speciation of uranium in sunflower (Helianthus annuus) - Linlin Wang; Yanru Liang; Song Liu; Fan Chen; Yin Ye; Yanlong Chen; Jingjing Wang; David J. Paterson; Peter M. Kopittke; Yuheng Wang; Cui Li (Journal of Hazardous Materials, 2024)

Effects of storage and processing on the residual distribution and behavior of five preservatives and their metabolites in pomegranate - Fajun Tian; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Food Chemistry, 2024)

Multistage regulation of LiMn2O4 electrode for electrochemical lithium extraction from salt-lake - Jun Gu; Linlin Chen; Linjing Fan; Guiling Luo; Xiaowei Li; Xiaojun Chen; Haiyan Ji; Yanhong Chao; Wenshuai Zhu (Desalination, 2024)

3D-printed devices for continuous-flow lithium recovery of brines - Jiangtao Yu; Jie Zhu; Zhuo Han; Peng Cui; Haiying Mi; Anan Zhang; Linlin Chen; Xiaowei Li; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2024)

Source characteristics of the 2006 Pingtung earthquake doublet off southern Taiwan and the possible contribution of submarine landslides to the Tsunami - Gui Hu; Linlin Li; Kenji Satake; Tso-Ren Wu; Peitao Wang; D.J. Doong; Philip L.-F. Liu (Earth and Planetary Science Letters, 2024)

Functional molecules surface segregation engineering in electrospinning: Design, regulation, and applications - Linlin Cao; Chen Qu; Jingchong Liu; Wenhui Li; Lihua Jiang; Boyu Jing; Chuandong Wu; Jiemin Liu (Chemical Engineering Journal, 2024)

Turnover structures in macrobenthic communities rather than nestedness in the Yellow River Delta wetland, China - Jiao Wang; Shaoyu Jiang; Debin Sun; Jing Chen; Baoquan Li; Linlin Chen (Aquatic Sciences, 2024)

Contribution of the TGFβ signaling pathway to growth of Pacific oyster (Crassostrea gigas) - Linlin Yao; Yumeng Liu; Li Li; Xuyang Jiang (Aquaculture, 2024)

Deep-sea mining of massive sulfides: Balancing impacts on biodiversity and ecosystem, technological challenges and law of the sea - Astrid Holzheid; Hongbo Zhao; Tony Cabus; Lei Fan; Thomas Kuhn; Linlin Sun; Chunhui Tao; Matthias Haeckel; Duong Hoang; Norman Kelly; Terue Kihara; Bing Li; et al. (Marine Policy, 2024)

The impact of block morphology on urban microclimates: A case study of three cities in cold regions of China - Linlin Guo; Xiaohua Guo; Baofeng Li; Endong Wang (Urban Climate, 2024)

The recent high occurrence of spring atmospheric droughts over central Hengduan Mountains is unprecedented in 669-year tree-ring records - Linlin Cui; Jinjian Li; Wenling An; Ningsheng Qin; Huiming Song; Yu Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Interaction characteristics and mechanism of Cr(VI)/Cr(III) with microplastics: Influence factor experiment and DFT calculation - Linlin Ma; Tong Liu; Jiaxin Li; Qing Yang (Journal of Hazardous Materials, 2024)

Influence of mountain orientation on precipitation isotopes in the westerly belt of Eurasia - Longhu Chen; Guofeng Zhu; Qin Qin Wang; Linlin Ye; Xinrui Lin; Siyu Lu; Yinying Jiao; Rui Li; Gaojia Meng; Yuhao Wang; Jiangwei Yang; Chen Jia (Global and Planetary Change, 2024)

Intelligent multi-colorimetric cellulose acetate/cobalt-based metal-organic framework antibacterial film and its application to pork preservation - Qianlan Tao; Yewen Xiao; Xuan Hu; Huaiting Pang; Feng Xiao; Linlin Li; Minmin Chen; Hualin Wang (Food Packaging and Shelf Life, 2024)

Spatial diffusion of potentially toxic elements in soils around non-ferrous metal mines - Linlin Li; Yunlong Zhang; Lingyan Zhang; Bo Wu; Xinhong Gan (Environmental Research, 2024)

Constructing efficient lithium salt dissociation solid-state electrolytes with high conductivity and transference number of Li ions for stable all-solid-state lithium batteries - Zengcai Guo; Shimin Liao; Feng Li; Linlin Shi; Bihai Su; Jingbo Mu; Yanming Wang; Zhongkai Huang; Feng Xu; Chaowen Guan (Chemical Engineering Journal, 2024)

Anti-cancer effects of nitazoxanide in epithelial ovarian cancer in-vitro and in-vivo - Xiangqun Yang; Zhenyan Liu; Xin Wang; Wenda Tian; Taoyu Zhao; Qiaoling Yang; Wenliang Li; Linlin Yang; Hongying Yang; Yue Jia (Chemico-Biological Interactions, 2024)

Dietary Potassium and Magnesium Intake with Risk of Type 2 Diabetes Mellitus Among Rural China: the Henan Rural Cohort Study - Jia Li; Yuqian Li; Chongjian Wang; Zhenxing Mao; Tianyu Yang; Yan Li; Wenguo Xing; Zhuoyang Li; Jiaoyan Zhao; Linlin Li (Biological Trace Element Research, 2024)

N-Doped Carbon Dots for Selective Detection of Fe3+ and Degradation of Fe3+/Basic Red 9 Complexes in Water Samples - Caixia Wang; Chengkui Qiao; Fajun Tian; Linlin Guo; Ruiping Wang; Jun Li; Tao Pang; Rongli Pang; Hanzhong Xie (Journal of Fluorescence, 2024)

Determining toxicity of europium oxide nanoparticles in immune cell components and hematopoiesis in dominant organs in mice: Role of lysosomal fluid interaction - Min Li; Jie Gao; Linlin Yao; Liu Zhang; Danyang Li; Zikang Li; Qi Wu; Shunhao Wang; Jie Ding; Yaquan Liu; Minghao Wang; Gang Tang; et al. (Science of The Total Environment, 2024)

The latest activity of the slope fault zone (Pearl River Mouth) in northern South China Sea and implications for earthquake hazard assessments - Liangwei Lv; Zhigang Li; Dawei Wang; Weitao Wang; Xiangming Dai; Fanchang Zeng; Linlin Li; Hao Liang; Gege Hui; Weiwang Long; Peizhen Zhang (Marine and Petroleum Geology, 2024)

Recent Holocene activity and regional tectonic significance of the northern segment of the red river fault zone - Long Guo; Zhongtai He; Zhikun Ren; Linlin Li; Xingao Li; Haomin Ji; Kuan Liang; Xin Tan (Journal of Structural Geology, 2024)

Exploring biomass addition in methanol production: A life cycle analysis of efficiency and environmental impacts - Linlin Liu; Shenghui Li; Yu Zhuang; Jian Du (Journal of Cleaner Production, 2024)

Spatial distribution and regional tectonic significance of the newly discovered Kalawenguquan fault in the interior of the Tian Shan Mountain Range, Western China - Xingao Li; Zhongtai He; Zhikun Ren; Linlin Li; Lei Wang; Haomin Ji; Xiaoxiao Zhu; Long Guo; Liangliang Wu (Journal of Asian Earth Sciences, 2024)

An integrated investigation combining network pharmacology and computer simulation dissects the potential mechanism of anti-obesity of Monascus pigments (MPs) - Jiaxing Li; Huijing Zhang; Linlin Xu; Huiqian Liu; Chenchen Qi; Chengtao Wang; Wei Chen (Food Bioscience, 2024)

Promoting the systematic utilization of reclaimed asphalt pavement (RAP) through waste asphalt-derived carbon in batteries applications - Danqing Li; Xin He; Hu Fu; Wenqi Tan; Shigang Lu; Linlin Wang; Mei Ding; Chunhui Gao; Chuankun Jia (Chemical Engineering Journal, 2024)

A novel multifunctional photocatalytic membrane based on ternary heterojunction TiO2@PDA@BiOBr for biochemical oily wastewater purification - Wei Ji; Yewen Xiao; Feng Xiao; Linlin Li; Minmin Chen; Hualin Wang (Chemical Engineering Journal, 2024)

Intermittent irrigation as a solution for reduced emissions and increased yields in ratoon rice systems - Lang Zhang; Linlin Li; Qiyuan Tang; Huaqin Xu; Huabin Zheng; Faming Wang; Jianwu Tang (Plant and Soil, 2024)

Elevated [CO2] reduces CH4 emissions from rice paddies under in situ straw incorporation - Ting Bao; Ling Wang; Yuanfa Huang; Huixin Li; Lanying Qiu; Jiujie Liu; Linlin Shi; Yunlong Liu; Haoyu Qian; Yanfeng Ding; Yu Jiang (Agriculture, Ecosystems & Environment, 2024)

Dissipation behavior and risk assessment of imidacloprid and its metabolites in apple from field to products - Fajun Tian; Junfeng Lu; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Chemosphere, 2024)

An engineered DNA aptamer-based PROTAC for precise therapy of p53-R175H hotspot mutant-driven cancer - Lingping Kong; Fanlu Meng; Ping Zhou; Ruixin Ge; Xiaoshan Geng; Zhihao Yang; Guo Li; Linlin Zhang; Jing Wang; Jinfeng Ma; Cheng Dong; Jun Zhou; et al. (Science Bulletin, 2024)

Insight into the mechanisms involved in the improved antagonistic efficacy of Pichia caribbica against postharvest black spot of tomato fruits by combined application with oligochitosan - Xiaoyun Zhang; Yu Xin; Qingrong Yue; Esa Abiso Godana; Linlin Gao; Mengge Dou; Hongyao Zhou; Jun Li; Lina Zhao; Hongyin Zhang (Postharvest Biology and Technology, 2024)

Coupling sedimentary records of anthropogenic metal(loid)s in urban waterscape parks with the “Coal to Gas” transition - Shen Yu; Tao Ma; Linlin Zhang; Qi Li; Min Zhou (Journal of Hazardous Materials, 2024)

Rice grain quality traits impacted by rice black-streaked dwarf virus disease - Yue Sun; Jiayuan Zhang; Linlin Du; Chenyang Li; Ying Lan; Tong Zhou; Xin Zhou; Baodong Wei; Feng Lin (Journal of Cereal Science, 2024)

An evaluation on the shrinkage deformation characteristics of Chinese yam during multiphase microwave drying based on digital image processing - Mengmeng Yang; Linlin Li; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Ke Gao; Chung Lim Law; Xu Duan (Innovative Food Science & Emerging Technologies, 2024)

Comparison of nutritional profile between plant-based meat analogues and real meat: A review focusing on ingredients, nutrient contents, bioavailability, and health impacts - Yunting Xie; Linlin Cai; Guanghong Zhou; Chunbao Li (Food Research International, 2024)

Chromium levels in placental tissue and neural tube defects: Association and mechanistic study - Yongyan Chen; Yingnan Guo; Chengrong Wang; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Environmental Pollution, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Correction to: Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2024)

Integrated assessment of trace elements in a marine ranching area based on multi-species and multi-level biomarkers: a case study in China’s national-level marine ranching demonstration area - Mingzhu Li; Zhixu Chen; Ming Li; Jiugang Zhang; Bingqing Xu; Yanyan Yang; Xiangfei Li; Linlin Fan; Baojun Liu; Tao Zheng; Yan Fang; Fan Li (Frontiers in Marine Science, 2024)
The goal of this study was to evaluate the trace element pollution in a marine ranching area in China based on molecular responses (expression of metallothionein and antioxidant enzyme genes), and biochemical biomarkers (metallothionein content, antioxidant enzyme activities, and malonaldehyde level) in four indicator species. We collected samples of two fish ( Lateolabrax maculatus and Sebastes schlegelii ), one crustacean ( Charybdis japonica ), and one gastropod ( Rapana venosa ) from the western Furong Island marine ranching area and from an adjacent area in March 2022 and measured the trace element content in these indicator species as well as in the seawater and sediment. We found that the bioaccumulation characteristics of trace elements and the response patterns of biomarkers were species specific. Moreover, not every biomarker was significantly correlated with environmental trace element content. We then established two biomarker combinations indicative of trace element pollution in seawater and sediment, respectively, based on the correlation between biomarkers and trace element contents. The selected biomarkers were integrated using integrated biomarker response version 2 (IBRv2). IBRv2 values in the studied marine ranching area were lower than those in the adjacent area. Additionally, these values were consistent with the bioaccumulation of trace elements in the indicator species, the integrated trace element pollution index for seawater, and the potential risk index for sediment. These results show that this multi-biomarker and multi-species IBRv2 approach provided a comprehensive diagnosis of trace element pollution in the marine ranching area. Therefore, its application may be beneficial for marine environmental monitoring and management in view of the ecotoxicological impact of pollutants on organisms.

Evidence and causes of recent decreases in nitrogen deposition in temperate forests in Northeast China - Yingying Wang; Feifei Zhu; Jin Li; Geshere Abdisa Gurmesa; Shaonan Huang; Xiaoming Fang; Dongwei Liu; Abubakari Said Mgelwa; Wenchao Wang; Kai Huang; Yihang Duan; Linlin Song; et al. (Science of The Total Environment, 2024)

A critical review of characteristics of domestic wastewater and key treatment techniques in Chinese villages - Jing Zhang; Yungeng Jiang; Heyu Zhang; Dan Feng; Hongling Bu; Linlin Li; Shaoyong Lu (Science of The Total Environment, 2024)

A robust transformer-based pipeline of 3D cell alignment, denoise and instance segmentation on electron microscopy sequence images - Jiazheng Liu; Yafeng Zheng; Limei Lin; Jingyue Guo; Yanan Lv; Jingbin Yuan; Hao Zhai; Xi Chen; Lijun Shen; LinLin Li; Shunong Bai; Hua Han (Journal of Plant Physiology, 2024)

Influence of point bars on nitrogen transport and reaction in riparian zones - Xunchuan Song; Ying Liu; Defu Liu; Jinghong Feng; Linlin Li; Yongsheng Guo; Junxiong Luo; Weiping Jiang (Journal of Hydrology, 2024)

Source-sink relationships of anthropogenic metal(loid)s from urban catchment to waterway in relation to spatial pattern of urban green infrastructures - Juan Li; Linlin Zhang; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Journal of Hazardous Materials, 2024)

Role of microalgae-bacterial consortium in wastewater treatment: A review - Lixin Li; Wei Chai; Caiyu Sun; Linlin Huang; Tao Sheng; Zhiwei Song; Fang Ma (Journal of Environmental Management, 2024)

Influence of mixing uniformity between stabilisation materials and contaminated soil on the stabilisation efficiency of heavy metals - Yunlong Zhang; Lixia Sun; Bo Wu; Meng Zhang; Shuhai Guo; Linlin Li; Shuqi Li; Longlong Qu (Journal of Environmental Chemical Engineering, 2024)

Recent progress in the antidegradation strategies of two-dimensional transition metal carbides (MXenes) - Ying Li; Yudi Li; Linlin Zhao; Siyu Chen; Siren Guo; Xulin Yang; Pan Wang; Kui Li; Fan Lei; Wei Feng; Zihao Mou; Hanjun Wei (Journal of Environmental Chemical Engineering, 2024)

Copper-doped ZIF-67/wood aerogel for effective peroxymonosulfate activation - Linlin Zhao; Wanning Xiong; Ziheng Wang; Jie Ouyang; Mengyao Li; Gonggang Liu; Yongfeng Luo (Journal of Environmental Chemical Engineering, 2024)

Ionospheric behaviors and characteristics in Asian sector during the April 2023 geomagnetic storm with multi-instruments observations - Linlin Li; Shuanggen Jin (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Formation mechanism of polycyclic aromatic hydrocarbons during mineral oil pyrolysis: A ReaxFF molecular dynamics study - Linlin Xu; Gan Wan; Lushi Sun; Li Lin (Fuel, 2024)

Antimicrobial photodynamic inactivation pH-responsive films based on gelatin/chitosan incorporated with aloe-emodin - Linlin Li; Li Xia; Feng Xiao; Yewen Xiao; Wei Ji; Baocai Xu; Hualin Wang (Food Chemistry, 2024)

A novel metal–organic framework based electrochemical immunosensor for the rapid detection of Salmonella typhimurium detection in milk - Ke Zhan; Linlin Chen; Shanshan Li; Qiuying Yu; Zheng Zhao; Junwei Li; Yunrui Xing; Hongtao Ren; Na Wang; Gaiping Zhang (Food Chemistry, 2024)

Determination of chloropropanol esters and glycidyl esters in instant noodles based on solid-phase microextraction with chitosan-β-cyclodextrin coated fiber - Linlin Bian; Xue Ge; Senwei Feng; Guangxuan Chen; Kefeng Li; Xu Wang (Food Chemistry, 2024)

Cellulose-based magnetic nanomaterials immobilized esterases as a reusable and effective detoxification agent for patulin in apple juice - Xiaoshuang Liu; Linlin Gao; Shiqi Li; Leran Wang; Rui Cai; Tianli Yue; Yahong Yuan; Xubo Zhao; Zhouli Wang (Food Control, 2024)

Release characteristics and risk assessment of volatile sulfur compounds in municipal wastewater treatment plants - Linlin Ma; Ruhan Zhao; Jiaxin Li; Qing Yang; Kehua Zou (Environmental Pollution, 2024)

Energetics of eddy-mean flow interactions in the western tropical Pacific Ocean - Yuchao Hui; Linlin Zhang; Xiaomei Yan; Mengmeng Li; Fan Wang; Dunxin Hu (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Activatable theranostic nanoprobes for Fluorescence/MR imaging and microenvironment remodeling of early cartilage degeneration - Xiuli Zhang; Manman Xie; Linlin Li; Wenlou Liu; Peng Xu; Zuohui Zhang; Yue Dai; Dongxu Wang; Li Lu; Kai Xu; Jingjing Li (Chemical Engineering Journal, 2024)

Island-based GNSS-IR network for tsunami detecting and warning - Linlin Li; Qiang Qiu; Mai Ye; Dongju Peng; Ya-Ju Hsu; Peitao Wang; Huabin Shi; Kristine M. Larson; Peizhen Zhang (Coastal Engineering, 2024)

Response of photosynthetic characteristics and antioxidant system in the leaves of safflower to NaCl and NaHCO3 - Linlin Song; Yongliang Yu; Hongzhi Chen; Yuwei Feng; Shuo Chen; Huihui Zhang; Haijia Zhou; Li Meng; Yue Wang (Plant Cell Reports, 2024)

The Observed Near-Surface Energy Exchange Processes over Arctic Glacier in Summer - Libo Zhou; Jinhuan Zhu; Linlin Kong; Peng Li; Shupo Ma; Fei Li; Han Zou; Meigen Zhang; Irina Repina (Journal of Meteorological Research, 2024)

Exploring Seasonal Variations in Fish Communities: A Study of the Yellow River Estuary and Its Adjacent Waters Using eDNA and Trawl Surveys - Xiaoyang Wang; Fan Li; Fei Shao; Hongjun Song; Na Song; Xiaomin Zhang; Linlin Zhao (Fishes, 2024)
The Yellow River Estuary and its adjacent waters serve as crucial spawning, foraging, and nursery areas for marine organisms, possessing abundant biological resources. Monitoring fish communities provides a baseline for implementing the sustainable utilization of marine resources. In this study, data were collected from 15 spring surface and bottom sites and 17 summer surface sites using eDNA and trawl surveys. The results showed that 37, 40, and 35 fish species were detected using eDNA in the spring (surface and bottom) and summer (surface), respectively, with 38 fish species caught during summer trawling. The dominant species mainly belonged to Engraulidae of Clupeiformes in the spring and Gobiidae of Perciformes in the summer, characterized by smaller-sized, short-lived, and pelagic fish species. The summer surface communities exhibited higher diversity than the spring surface and bottom communities. NMDS analysis revealed a degree of seasonal differences in fish communities and that there may be a lack of vertical stratification in the spring communities. The pH and DO were identified as the key environmental factors affecting the fish community. Additionally, the combination of eDNA and trawl surveys was regarded as a superior survey method. Our study provides valuable information for understanding seasonal fish communities in the Yellow River Estuary and its adjacent waters, contributing to fishery resource management and conservation in the region.

Editorial: The response, adaptation, and evolution of marine molluscs - Xiao Liang; Linlin Zhang; Yingxiang Li (Frontiers in Marine Science, 2024)

Airborne ARGs/MGEs from two sewage types during the COVID-21: Population, microbe interactions, cytotoxicity, formation mechanism, and dispersion - Yanjie Wang; Song Zhang; Lin Li; Qiao Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Jian Wu; Linlin Hua (Water Research, 2024)

Spatiotemporal distribution, interactions and toxic effect of microorganisms and ARGs/MGEs from the bioreaction tank in hospital sewage treatment facility - Yanjie Wang; Song Zhang; Liying Yang; Kai Yang; Yang Liu; Haoran Zhu; Bisheng Lai; Lin Li; Linlin Hua (Science of The Total Environment, 2024)

A transferable approach to assessing green infrastructure types (GITs) and their effects on surface urban heat islands with multi-source geospatial data - Linlin Lu; Huadong Guo; Qihao Weng; Carlos Bartesaghi-Koc; Paul Osmond; Qingting Li (Remote Sensing of Environment, 2024)

Control of postharvest soft rot of green peppers by Bacillus subtilis through regulating ROS metabolism - Peipei Feng; Xiaoyun Zhang; Esa Abiso Godana; Guillaume Legrand Ngolong Ngea; Solairaj Dhanasekaran; Linlin Gao; Jun Li; Lina Zhao; Hongyin Zhang (Physiological and Molecular Plant Pathology, 2024)

Change characteristics, bacteria host, and spread risks of bioaerosol ARGs/MGEs from different stages in sewage and sludge treatment process - Yanjie Wang; Kai Yang; Lin Li; Liying Yang; Song Zhang; Fangfang Yu; Linlin Hua (Journal of Hazardous Materials, 2024)

Prenatal exposure to poly/perfluoroalkyl substances and risk for congenital heart disease in offspring - Sainan Li; Chengrong Wang; Chen Yang; Yongyan Chen; Qianhui Cheng; Jufen Liu; Yali Zhang; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2024)

Adsorption-desorption of 241Am(Ⅲ) on montmorillonite colloids and quartz sand: Effects of pH, ionic strength, colloid concentration and grain size - Linlin Zhang; Ling Li; Ke Chen; Qiulan Zhang; Jingli Shao; Yali Cui; Jun Zhu; Aiming Zhang; Song Yang (Journal of Environmental Radioactivity, 2024)

Construction of Ni3S4@ZIS@C3N5 photocatalyst with type II and Z-type heterojunctions by self-assembly for efficient photocatalytic hydrogen evolution - Huixiang Yan; Wei Li; Huixing Yang; Yongzhuo Yu; Chaoyu Lv; Linlin Hou; Wenxu Zhang; Di Lin; Shichao Jiao (Environmental Research, 2024)

Preparation of core-shell structure Ag@TiO2 plasma photocatalysts and reduction of Cr(VI): Size dependent and LSPR effect - Jiwen Li; Yaqian Duan; Linlin Wang; Jingjun Ma (Environmental Research, 2024)

Review on post-combustion CO2 capture by amine blended solvents and aqueous ammonia - Jiaxing Du; Wu Yang; Linlin Xu; Lei Bei; Siyuan Lei; Wei Li; Haitao Liu; Ben Wang; Lushi Sun (Chemical Engineering Journal, 2024)

Promoting denitrification via high electron conversion ratio in the iron valence Cycle: Prospects for Pseudomonas sp. JM-7 application in environmental engineering - Bobo Xing; Ji Li; Linlin Li; Nigel J.D. Graham; Binghao Zhao; Xian Li; Wenzheng Yu (Chemical Engineering Journal, 2024)

Dual-objective control of braced steel frame using asynchronized parallel two-stage yielding BRB - Cantian Yang; Linlin Xie; Qiang Liu; Aiqun Li; Qianmin Liu; Xinyu Wang (Soil Dynamics and Earthquake Engineering, 2024)

Nitrogen isotopic characteristics of aerosol ammonium in a Chinese megacity indicate the reduction from vehicle emissions during the lockdown period - Zhengjie Li; Hongwei Xiao; Wendell W. Walters; Meredith G. Hastings; Juan Min; Linlin Song; Weizhi Lu; Libin Wu; Wende Yan; Shuguang Liu; Yunting Fang (Science of The Total Environment, 2024)

Uptake, accumulation and metabolism of UV-320 in vegetables and its impact on growth and quality - Bingru Li; Zhenzhen Yao; Dizhe Wei; Linlin Guo; Zhihong Ma; Cheng Li (Science of The Total Environment, 2024)

Microdrop-confined synthesis and regulation of porous hollow Ir-based catalysts for the mass transfer-enhanced electrolysis of pure water - Li Liu; Ting Huang; Xiaoliang Yang; Shoujie Liu; Shunsheng Wang; Linlin Xiang; Gongming Wang; Long Kuai (Science Bulletin, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Preparation of PEI/La2O3/Polypropylene fiber filter for household water purifiers and investigation of its phosphate reduction and bacterial control - Linlin Hao; Gewei Feng; Zengli Zhai; Mingxuan Li (Journal of Water Process Engineering, 2024)

Finite strain, kinematic vorticity, rheological behavior and thermochronology of the Diancang Shan complex: Insights into channel flow of the southeastern Tibetan plateau - Xiaofan Li; Han Zheng; Huan Li; Scott A. Whattam; Wei Pi; Linlin Zeng (Journal of Structural Geology, 2024)

Evolution behavior of volatile components of shiitake mushrooms during infrared-assisted spouted bed drying - Yiming Xu; Wenchao Liu; Linlin Li; Weiwei Cao; Guangyue Ren; Houdong Shi; Yike Zhao; Junliang Chen; Xu Duan (Food Control, 2024)

Coagulation-centered three-step approach for removing by-product organic pollutants from tetrabromobisphenol A industrial wastewater: Experimental and theoretic investigations - Linlin Hao; Jingshuang Yan; Mingxuan Li; WeiMin Shao; Ming Zeng (Environmental Research, 2024)

Clinical epidemiology of adenovirus pneumonia among Chinese hospitalized children - Jiao Tian; Xinyu Wang; Qi Li; Linlin Zhang; Junhong Ai; Guoshuang Feng; Yueping Zeng; Ran Wang; Zhengde Xie (Archives of Microbiology, 2024)

Rapid seismic-damage assessment method for buildings on a regional scale based on spectrum-compatible data augmentation and deep learning - Qingle Cheng; Aiqun Li; Haotian Ren; Cheav Por Chea; Wenjie Liao; Linlin Xie (Soil Dynamics and Earthquake Engineering, 2024)

Estimating the methane flux of the Dajiuhu subalpine peatland using machine learning algorithms and the maximal information coefficient technique - Xue Li; Jiwen Ge; Ziwei Liu; Shiyu Yang; Linlin Wang; Ye Liu (Science of The Total Environment, 2024)

Interactive effects of dinotefuran and Nosema ceranae on the survival status and gut microbial community of honey bees - Linlin Liu; Min Shi; Yanyan Wu; Xianbing Xie; Shanshan Li; Pingli Dai; Jing Gao (Pesticide Biochemistry and Physiology, 2024)

Multipath diffusion process and spatial accumulation simulation of Cd in lead-zinc mining areas - Linlin Li; Bo Wu; Shuhai Guo; Enzhu Hu; Yunlong Zhang; Lixia Sun; Shuqi Li (Journal of Hazardous Materials, 2024)

Deterioration of single-use biodegradable plastics in high-humidity air and freshwaters over one year: Significant disparities in surface physicochemical characteristics and degradation rates - Lingling Hu; Linlin He; Li Cai; Yumeng Wang; Gang Wu; Daoyong Zhang; Xiangliang Pan; Yu-Zhong Wang (Journal of Hazardous Materials, 2024)

Quantitative distribution and quantized ecological threat of microplastics in farmland: Shanghai as an example - Zhengwen Li; Zhaofeng Song; Linlin Qiu; Yan Cao; Hairong Gu; Zhenqi Wang; Xiang Liu; Xiaoyong Qian (Journal of Hazardous Materials, 2024)

Release characteristics and risk assessment of volatile sulfur compounds in a municipal wastewater treatment plant with odor collection device - Linlin Ma; Ruhan Zhao; Jiaxin Li; Qing Yang; Yong Liu (Journal of Environmental Management, 2024)

Microbiological hazards in infant and toddler food in China: A comprehensive study between 2004 and 2022 - Lin Teng; Linlin Huang; Haiyang Zhou; Baikui Wang; Min Yue; Yan Li (Food Research International, 2024)

Preparation and characterization of zein-tannic acid nanoparticles/chitosan composite films and application in the preservation of sugar oranges - Shuangjian Li; Xiaoli Liu; Xiaoqian Zhang; Linlin Fan; Fan Wang; Jianzhong Zhou; Hongzhi Zhang (Food Chemistry, 2024)

UV-B application during the aeration process improves the aroma characteristics of oolong tea - Xiaohui Wang; Jingjie Cao; Xin Cheng; Xuyang Liu; Wenfeng Zhu; Yan Li; Xiaochun Wan; Shengkeng Chen; Linlin Liu (Food Chemistry, 2024)

Selective extraction of lithium ions by phosphoroxy-functionalized ionogels from the mother liquor of Li2CO3 - Yuhong Huang; Xiaowei Li; Guiling Luo; Duanjian Tao; Linlin Chen; Jing Sun; Bizuneh Kaleab; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2024)

Piezoelectric effect-assisted Z-scheme heterojunction ZnIn2S4/BaTiO3 for improved photocatalytic reduction of CO2 to CO - Shanyue Lu; Shengwei Zhang; Linlin Li; Cong Liu; Zhou Li; Dan Luo (Chemical Engineering Journal, 2024)

Photocatalytic chitosan-based bactericidal films incorporated with WO3/AgBr/Ag and activated carbon for ethylene removal and application to banana preservation - Feng Xiao; Yewen Xiao; Wei Ji; Linlin Li; Yimeng Zhang; Minmin Chen; Hualin Wang (Carbohydrate Polymers, 2024)

Geomorphic adjustments of channel bars in the braided reach of the lower Yellow river from 1986 to 2018 - Jie Li; Junqiang Xia; Lingzhong Kong; Qingfeng Ji; Linlin Li; Fan chen (CATENA, 2024)

Distribution and influencing factors of macrobenthos on three seagrass beds in the intertidal zone of Shandong province, China - Yinglu Ji; Bo Song; Jiangling Xu; Shaoyu Jiang; Linlin Chen; Baoquan Li (Frontiers in Marine Science, 2024)
Introduction The macrobenthos plays a vital role within the ecosystem of seagrass beds, with its characteristics and spatial distribution serving as indicators of the well-being of the seagrass beds. Methods In August 2018, three seagrass beds located in the Yellow River Estuary of Dongying, the west coast of Yantai, and Swan Lake of Weihai, were investigated to compare the ecological influences of seagrass habitat on the benthic environment and macrobenthic community. Within each seagrass bed, porewater, sediment, and macrobenthos were sampled from three separate stations (center of seagrass bed, edge of seagrass bed and bare area). Results and discussion One-way ANOVA showed significant differences ( p < 0.05) in environmental factors and macrobenthos species, abundance, biomass and diversity indices among the three seagrass beds. The present data did not show significant impacts on habitat and macrobenthos in the different coverage areas of seagrass beds at the investigated spatial scales, though crustacea and some carnivores were relatively more inclined to inhabit areas with higher seagrass densities. Aquaculture and eutrophication may trigger the loss of seagrass bed habitats, that affects macrobenthic biodiversity, and conservation measures are needed to protect seagrass bed habitats.

Analysis of Flow Instability and Mechanical Energy Loss of Fluid Field in Fluid Momentum Wheel - Kedong Zhang; Wenhua Wang; Yihua Liu; Linlin Wang; Yazhen Du; Hongxia Li; Yi Huang (Journal of Marine Science and Engineering, 2024)
A new type of anti-rolling device denoted as a fluid momentum wheel (FMW) is proposed to address the limitations of traditional gyrostabilizers in reducing the roll responses of floating platforms in waves. The proposed device is based on the same gyroscope theorem, which differs from a rigid gyrostabilizer in that the internal fluid generates secondary flow in the cross-section under the combined effects of inertial centrifugal force and a radial pressure gradient, and the streamwise velocity exhibits a non-uniform distribution. These instability phenomena may cause mechanical energy loss in the flow field, which is critical for selecting the driving device and the anti-roll control performance of offshore platforms. In the study, different turbulence models are compared with the results of a Direct Numerical Simulation (DNS) and experiments to ensure the accuracy of the numerical method, and the spatiotemporal distribution characteristics of the flow field in FMW are analyzed. Therein, the SST k-ω model accurately verifies the flow instability phenomenon of the FMW observed in the Particle Image Velocimetry (PIV) experiment. Next, this paper proposes corresponding evaluation parameters to assess the impact of typical parameters on the flow field instability. The results show that the flow instability increases with an increase in the typical parameters of FMWs (such as the pipe diameter, curvature radius, and velocity). Furthermore, the paper discusses the relationship between dimensionless mechanical factors (Reynolds number, curvature ratio) and the spatiotemporal instability of the flow field, revealing the essential effects of the curvature ratio and Reynolds number on the loss coefficient.

A novel method of identifying estuary high-nutrient zones for water quality management - Linlin Wang; Xiaoyu Lei; Guo Yuehua; Yang Zhou; Jing-Cheng Han; Yuefei Huang; Bing Li; Xian-zhong Mao; Zhaozhao Tang (Science of The Total Environment, 2024)

Forward numerical investigation of potential tsunami deposits in the South China sea: A case study of Nan'ao Island - Fating Li; Linlin Li; Fengling Yu; Kangyou Huang; Adam D. Switzer (Marine and Petroleum Geology, 2024)

Multi-sensor integrated mapping of global XCO2 from 2015 to 2021 with a local random forest model - Jiabin Chen; Ruohua Hu; Leyan Chen; Zihao Liao; Linlin Che; Tongwen Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Selective fluoride removal from groundwater using CNT-CeO2 electrodes in capacitive deionization (CDI) - Xun Liu; Danyal Rehman; Yufei Shu; Bei Liu; Li Wang; Li Li; Mengxia Wang; Kunkun Wang; Qi Han; Linlin Zang; John H. Lienhard; Zhongying Wang (Chemical Engineering Journal, 2024)

Alisol A Exerts Neuroprotective Effects Against HFD-Induced Pathological Brain Aging via the SIRT3-NF-κB/MAPK Pathway - Taotao Lu; Linlin Ding; Xiaoqing Zheng; Yongxu Li; Wei Wei; Weilin Liu; Jing Tao; Xiehua Xue (Molecular Neurobiology, 2024)
Chronic consumption of a high-fat diet (HFD) has profound effects on brain aging, which is mainly characterized by cognitive decline, inflammatory responses, and neurovascular damage. Alisol A (AA) is a triterpenoid with therapeutic potential for metabolic diseases, but whether it has a neuroprotective effect against brain aging caused by a HFD has not been investigated. Six-month-old male C57BL6/J mice were exposed to a HFD with or without AA treatment for 12 weeks. Behavioral tasks were used to assess the cognitive abilities of the mice. Neuroinflammation and changes in neurovascular structure in the brains were examined. We further assessed the mechanism by which AA exerts neuroprotective effects against HFD-induced pathological brain aging in vitro and in vivo. Behavioral tests showed that cognitive function was improved in AA-treated animals. AA treatment reduced microglia activation and inflammatory cytokine release induced by a HFD. Furthermore, AA treatment increased the number of hippocampal neurons, the density of dendritic spines, and the expression of tight junction proteins. We also demonstrated that AA attenuated microglial activation by targeting the SIRT3-NF-κB/MAPK pathway and ameliorated microglial activation-induced tight junction degeneration in endothelial cells and apoptosis in hippocampal neurons. The results of this study show that AA may be a promising agent for the treatment of HFD-induced brain aging.

Comprehensive analyses of annexins in naked carp (Gymnocypris przewalskii) unveil their roles in saline-alkaline stress - Linlin A; Yujing Zhang; Baoke Xu; Haichen Zhang; Yixin Li; Le Wang; Jian Liang; Weiguo Zhou; Zhaohui Feng; Hong Zhang (Aquaculture, 2024)

Comparative transcriptome analysis of hybrid Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) and Epinephelus fuscoguttatus under temperature stress - Pengfei Duan; Yongsheng Tian; Zhentong Li; Shuai Chen; Linlin Li; Xinyi Wang; Linna Wang; Yang Liu; Jieming Zhai; Wensheng Li; Qingbin Wang; Wenhui Ma; et al. (Aquaculture, 2024)

How the subsurface wastewater infiltration systems with iron‑carbon micro-electrolytic substrate achieve high pollutants removal: A metabolomic view - Yinghua Li; Linlin Peng; Yiyan Wang; Yue Zhang; Fei Su; Jie Qian (Journal of Water Process Engineering, 2024)

Study on the late quaternary activity of the Jinyang-Ningnan segment of the Lianfeng fault zone - Liangliang Wu; Zhongtai He; Dongsheng Xu; Linlin Li; Long Guo; Xingao Li (Journal of Structural Geology, 2024)

Acid-assisted ultrasonic preparation of nitrogen-doped MXene quantum dots for the efficient fluorescence “off-on-off” detection of Zn(II) in water and oxalic acid in vegetables - Jinwen Yang; Linlin Chen; Jie Qi; Feili Luo; Lin Li; Honghong Wu; Feifei Cao; Jiangjiang Gu (Food Chemistry, 2024)

Performance and mechanism of Al, N co-doped carbon/nano-TiO2 photocatalytic oxidation for the removal of ammonia nitrogen and Ni/Co complexes from ternary precursor wastewater - Peize Li; Yaoguo Huang; Yali Zhang; Linlin Chen (Chemical Engineering Journal, 2024)

Co-seismic ionospheric disturbances characteristics in different azimuths following the 2022 Mexico earthquake from GNSS observations - Linlin Li; Shuanggen Jin; Yi Chai (GPS Solutions, 2024)

One-step, reagent-free construction of nano-enzyme as visual and reusable biosensor for oxidase substrates - Ke Quan; Yuqing Zeng; Wenke Zhang; Fengfeng Li; Mengjiao Li; Zhihe Qing; Linlin Wu (Analytica Chimica Acta, 2024)

Grey matter structural alterations in anxiety disorders: a voxel-based meta-analysis - Han Liu; Zeqi Hao; Shasha Qiu; Qianqian Wang; Linlin Zhan; Lina Huang; Youbin Shao; Qing Wang; Chang Su; Yikang Cao; Jiawei Sun; Chunjie Wang; et al. (Brain Imaging and Behavior, 2023)

Dissipation, residues, and evaluation of processing factor for spirotetramat and its formed metabolites during kiwifruit growing, storing, and processing - Fajun Tian; Chengkui Qiao; Caixia Wang; Tao Pang; Linlin Guo; Jun Li; Rongli Pang; Hanzhong Xie (Environmental Science and Pollution Research, 2023)

2-Methoxyestradiol ameliorates paraquat-induced pulmonary fibrosis by inhibiting the TGF-β1/Smad2/3 signaling pathway - Linlin Hou; Fang Yang; Yan Zhang; Yi Li; Hongyi Yan; Cuicui Meng; Yuqi Du; Huanzhou Zhu; Ding Yuan; Yanxia Gao (Pesticide Biochemistry and Physiology, 2023)

Effect mechanisms of leading-edge tubercle on blade cavitation control in a waterjet pump - Guoshou Zhao; Ning Liang; Qianqian Li; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2023)

S doped g-C3N5 for highly efficient photocatalytic H2O2 production and PPCPs degradation via directional transfer of electrons - Wenjuan Wang; Nan Zhou; Yakun Li; Zhengqiaoruo Zhu; Xiguo Chen; Linlin Zhang (Journal of Environmental Chemical Engineering, 2023)

Plant-based meat analogues enhance the gastrointestinal motility function and appetite of mice by specific volatile compounds and peptides - Yunting Xie; Linlin Cai; Mengzhen Ding; Kai Shan; Di Zhao; Guanghong Zhou; Chunbao Li (Food Research International, 2023)

Advancing ocean subsurface thermal structure estimation in the Pacific Ocean: A multi-model ensemble machine learning approach - Jifeng Qi; Linlin Zhang; Baoshu Yin; Delei Li; Bowen Xie; Guimin Sun (Dynamics of Atmospheres and Oceans, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

Analysis of mRNA and MicroRNA Expression Profiles of Nervous Tissues and Reproductive Tissues in Male Procambarus clarkii After Silencing IAG - Rong Sun; Shaokui Yi; Linlin Shi; Kianann Tan; Ruixue Shi; Siqi Yang; Yanhe Li (Marine Biotechnology, 2023)

Integrated analyses delineate distinctive immunological pathways and diagnostic signatures for Behcet’s disease by leveraging gene microarray data - Haoting Zhan; Linlin Cheng; Haolong Li; Yongmei Liu; Yuan Huang; Xiaomeng Li; Songxin Yan; Yongzhe Li (Immunologic Research, 2023)

Spatio-temporal distribution of macrobenthos and benthic ecological health status in the Bohai Sea and the northern Yellow Sea, China - Shaoyu Jiang; Wenzheng Fan; Linlin Chen; Jing Chen; Baoquan Li (Marine Pollution Bulletin, 2023)

Strategies for the coordinated control of particulate matter and carbon dioxide under multiple combined pollution conditions - Zhenyu Wang; Huan Zhao; Han Xu; Jie Li; Tong Ma; Linlin Zhang; Yinchang Feng; Guoliang Shi (Science of The Total Environment, 2023)

Associations among bisphenol A, its analogs, and chlorinated derivatives in placenta and risk for neural tube defects: A case-control study - Haiyan Zhu; Qianhui Cheng; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Science of The Total Environment, 2023)

Hydrophobic electrospun membrane of peppermint oil loaded zein with coating of methyltriethoxysilane for active packaging - Li Xia; Linlin Li; Yewen Xiao; Feng Xiao; Wei Ji; Min Pang; Hualin Wang (Food Hydrocolloids, 2023)

Structural and gelling properties of whey proteins influenced by various acids: Experimental and computational approaches - Linlin Zhang; Zhuo Zhang; Stephen R. Euston; Bo Li; Erhu Li; Caixia Fu; Guodong Chen (Food Hydrocolloids, 2023)

Biomineralization of uranium by Desulfovibrio desulfuricans A3-21ZLL under various hydrochemical conditions - Bei Zhao; Xin Chen; Hongliang Chen; Linlin Zhang; Jiang Li; Yadan Guo; Haiyan Liu; Zhongkui Zhou; Pingchao Ke; Zhanxue Sun (Environmental Research, 2023)

The effect of commercial β-glucosidase and its immobilization on quality of red wine production - Jun Wang; Linlin Ma; Hengfang Gao; Xia Li; Zhigang Dong (Biocatalysis and Agricultural Biotechnology, 2023)

Frequency specific alterations of the degree centrality in patients with acute basal ganglia ischemic stroke: a resting-state fMRI study - Hao Chen; Linlin Zhan; Qianqian Li; Chaoguo Meng; Xuemei Quan; Xiaoling Chen; Zeqi Hao; Jing Li; Yanyan Gao; Huayun Li; Xize Jia; Mengting Li; et al. (Brain Imaging and Behavior, 2023)
This study intended to investigate the frequency specific brain oscillation activity in patients with acute basal ganglia ischemic stroke (BGIS) by using the degree centrality (DC) method. A total of 34 acute BGIS patients and 44 healthy controls (HCs) underwent resting-state functional magnetic resonance imaging (rs-fMRI) scanning. The DC values in three frequency bands (conventional band: 0.01–0.08 Hz, slow‑4 band: 0.027–0.073 Hz, slow‑5 band: 0.01–0.027 Hz) were calculated. A two-sample t -test was used to explore the between-group differences in the conventional frequency band. A two-way repeated-measures analysis of variance (ANOVA) was used to analyze the DC differences between groups (BGIS patients, HCs) and bands (slow‑4, slow‑5). Moreover, correlations between DC values and clinical indicators were performed. In conventional band, the DC value in the right middle temporal gyrus was decreased in BGIS patients compared with HCs. Significant differences of DC were observed between the two bands mainly in the bilateral cortical brain regions. Compared with the HCs, the BGIS patients showed increased DC in the right superior temporal gyrus and the left precuneus, but decreased mainly in the right inferior temporal gyrus, right inferior occipital gyrus, right precentral, and right supplementary motor area. Furthermore, the decreased DC in the right rolandic operculum in slow-4 band and the right superior temporal gyrus in slow-5 band were found by post hoc two-sample t -test of main effect of group. There was no significant correlation between DC values and clinical scales after Bonferroni correction. Our findings showed that the DC changes in BGIS patients were frequency specific. Functional abnormalities in local brain regions may help us to understand the underlying pathogenesis mechanism of brain functional reorganization of BGIS patients.

A quantitative analysis of the impact of reclamation on the stability of coastal wetlands - Yanhui Chen; Linlin Cui; Guosheng Li; Jiping Liu; Lijuan Li; Dandan Zhao (Ocean & Coastal Management, 2023)

A two-centennial perspective on spatially compounding hydroclimate events in arid and semi-arid north China - Qian Li; Linlin Gao; Yang Deng; Xiang Zhang; Yongkang Duan; Xiaohua Gou (Quaternary Science Reviews, 2023)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

A novel ZnFe2O4 intermediate layer for improving the electrocatalytic performance of Ti/Ce-PbO2 anode toward Levofloxacin removal - Linlin Dong; Zhong Zhuang; Guohua Dong; Hao Zhang; Min Zhu; Zhuanfang Zhang; Ming Zhao; Jinlong Li; Wenzhi Zhang (Journal of Environmental Chemical Engineering, 2023)

Phosphorus and sulfur regulation of ferrum doped carbon nitride for efficient photocatalytic PPCPs degradation under visible-light irradiation - Zhengqiaoruo Zhu; Nan Zhou; Yakun Li; Linlin Zhang (Journal of Environmental Chemical Engineering, 2023)

Engineering effect of oleogels with different structuring mechanisms on the crystallization behavior of cocoa butter - Linlin Li; Guoqin Liu (Food Chemistry, 2023)

The effects of selenium on the growth and bone development in the weaned rats - Hongan Li; Linlin Jia; Zeyuan Deng; Xiaomao Sun; Hui Zhang; Hongyan Li (Food Bioscience, 2023)

Construction of CoTiO3/TiO2/Ti composite catalytic membrane for degradation of tetracycline via peroxymonosulfate activation: Reactive oxygen species and electron transfer pathways - Yi Li; Linlin Wang; Longfei Wang; Weijie Wu; Fangjie Zhang; Haijiao Xie (Chemical Engineering Journal, 2023)

Li-intercalation chemistry of few-layer borophene with ultrahigh capacity and fast kinetics - Linlin Guo; Huili Wang; Zhonghan Wu; Xinru Yang; Ruoxuan Ma; Yanfang Hu; Geng Li; Dongjie Shi; Wei Xie; Wei Zhang; Fujun Lan; Limin Zhou; et al. (Chemical Engineering Journal, 2023)

Gas-pressurized torrefaction of lignocellulosic solid wastes: Low-temperature deoxygenation and chemical structure evolution mechanisms - Liu Shi; Zhenzhong Hu; Xian Li; Shuo Li; Linlin Yi; Xiaohua Wang; Hongyun Hu; Guangqian Luo; Hong Yao (Bioresource Technology, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Expression analysis, clinical significance and potential function of PLXNB2 in acute myeloid leukaemia - Zhibo Guo; Dan Guo; Desheng Kong; Sicheng Bian; Linlin Zhao; Qi Li; Leilei Lin; Jiali Hao; Lili Sun; Yinghua Li (Molecular Biology Reports, 2023)

Exploring the therapeutic mechanism of Banxia Xiexin Decoction in mild cognitive impairment and diabetes mellitus: a network pharmacology approach - Cong Li; Wei Yang; Yubo Meng; Lina Feng; Linlin Sun; Zhenghong Li; Xingfang Liu; Mingquan Li (Metabolic Brain Disease, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Targeted preparation of biochar for the application as composting additive: Influence mechanism of feedstock properties on biochar derived from traditional Chinese herb residue - Haoyu Tang; Aijun Li; Linlin Yi; Yongda Huang; Qian Deng; Yangwei Wu; Hong Yao (Process Safety and Environmental Protection, 2023)

Quadristerols A−G: Seven undescribed ergosterols from Aspergillus quadrilineata - Mengsha Wei; Xiaoxin Li; Hong Liao; Linlin Liu; Qin Li; Weiguang Sun; Chunmei Chen; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2023)

Effect of non-permeable cryoprotectant sucrose on the development of spotted knifejaw (Oplegnathus punctatus) embryos - Linlin Li; Yongsheng Tian; Zhentong Li; Pengfei Duan; Xinyi Wang; Shuai Chen; Linna Wang; Yang Liu; Qingbin Wang; Wensheng Li; Xia Zhao; Wenhui Ma; et al. (Cryobiology, 2023)

Exploration on the reasons for low efficiency of arable land protection policy in China: an evolutionary game theoretic model - Linlin Wang; Zhuo Li; Chengcheng Yuan; Liming Liu (Environment, Development and Sustainability, 2023)

Development of a double-stage-yield dissipative beam-to-column joint: Experimental study and application for structural response control - Cantian Yang; Linlin Xie; Aiqun Li; Xinyu Wang (Soil Dynamics and Earthquake Engineering, 2023)

Identifying the O3 chemical regime inferred from the weekly pattern of atmospheric O3, CO, NOx, and PM10: Five-year observations at a center urban site in Shanghai, China - Gen Zhang; Yifeng Sun; Wanyun Xu; Lingyan Wu; Yuseng Duan; Linlin Liang; Yuan Li (Science of The Total Environment, 2023)

Insights into gas flow behavior in venturi aerator by CFD-PBM model and verification of its efficiency in sludge reduction through O3 aeration - Hongli Li; Qilei Zhang; Ming Zeng; Jingguo Cao; Qingyu Zhao; Linlin Hao (Journal of Water Process Engineering, 2023)

The lysosome-phagosome pathway mediates immune regulatory mechanisms in Mesocentrotus nudus against Vibrio coralliilyticus infection - Yanxia Wang; Quanchao Wang; Linlin Chen; Baoquan Li (Fish & Shellfish Immunology, 2023)

3D-printed titanium-based ionic sieve monolithic adsorbent for selective lithium recovery from salt lakes - Jiangtao Yu; Jie Zhu; Guiling Luo; Linlin Chen; Xiaowei Li; Peng Cui; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2023)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

MiR-590-5p promotes cisplatin resistance via targeting hMSH2 in ovarian cancer - Bing Li; Xuejie Xu; Linlin Zheng; Xiaojie Jiang; Jing Lin; Guoliang Zhang (Molecular Biology Reports, 2023)

Recognize enhanced temporal-spatial-spectral features with a parallel multi-branch CNN and GRU - Linlin Wang; Mingai Li; Liyuan Zhang (Medical & Biological Engineering & Computing, 2023)

On the effects of rheological behavior on landslide motion and tsunami hazard for the Baiyun Slide in the South China Sea - Zhiyuan Ren; Hua Liu; Linlin Li; Yuchen Wang; Qiliang Sun (Landslides, 2023)

Pathogenicity and immune response of the sea urchin Mesocentrotus nudus to Vibrio coralliilyticus infection - Yanxia Wang; Quanchao Wang; Linlin Chen; Ruxin Ding; Zirui Peng; Baoquan Li (Aquaculture, 2023)

Manipulating electron redistribution induced by asymmetric coordination for electrocatalytic water oxidation at a high current density - Sheng Zhao; Feng Hu; Lijie Yin; Linlin Li; Shengjie Peng (Science Bulletin, 2023)

Distinct functions of TIR1 and AFB1 receptors in auxin signaling - Huihuang Chen; Lanxin Li; Minxia Zou; Linlin Qi; Jiří Friml (Molecular Plant, 2023)

Dissipation and movement of soil water in artificial forest in arid oasis areas: Cognition based on stable isotopes - Dongdong Qiu; Guofeng Zhu; Xinrui Lin; Yinying Jiao; Siyu Lu; Jiatong Liu; Jiawei Liu; Wenhao Zhang; Linlin Ye; Rui Li; Qinqin Wang; Longhu Chen (CATENA, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Genetic diversity and population structure of the sea star Asterias amurensis in the northern coast of China - Quanchao Wang; Ying Liu; Zirui Peng; Linlin Chen; Baoquan Li (Journal of Oceanology and Limnology, 2023)

Hair Selenium of Residents in Keshan Disease Endemic and Non-endemic Regions in China - Yuehui Jia; Ruixiang Wang; Guijin Li; Chen Feng; Lei Qi; Yuanyuan Wang; Shengqi Su; Yuanjie Zou; Xu Liu; Yanan Wang; Yiyi Zhang; Linlin Du; et al. (Biological Trace Element Research, 2023)

Spatial response relationship between mining and industrial activities and eco-environmental risks in mineral resource–based areas - Yang Li; Lingyan Zhang; Bo Wu; Linlin Li; Yunlong Zhang (Environmental Science and Pollution Research, 2023)

Defensive Specialized Metabolites from the Latex of Euphorbia jolkinii - Shihong Luo; Chunshuai Huang; Juan Hua; Shuxi Jing; Linlin Teng; Ting Tang; Yan Liu; Shenghong Li (Journal of Chemical Ecology, 2023)

Influence Mechanism of New-type Urbanization on Urban Land Use Efficiency in the Yangtze River Delta, China - Qingke Yang; Linlin Ding; Lei Wang; Chao Liu; Yeting Fan; Ying Li; Yazhu Wang (Chinese Geographical Science, 2023)

Sources and historical records of metal(loid)s in river sediments from an agricultural tributary of Tuojiang river: Evidence from geochemical analyses and Pb isotope - Fen Xu; Rui Yang; Hong Wang; Xiaoxia He; Weiwei Li; Yao Wei; Linlin Bao; Jianfei Yuan; Hongjin Tong (Chemosphere, 2023)

Efficient and selective removal of Hg(II) from water using recyclable hierarchical MoS2/Fe3O4 nanocomposites - Shiyu Li; Lin Yang; Jialong Wu; Linlin Yao; Deming Han; Yong Liang; Yongguang Yin; Ligang Hu; Jianbo Shi; Guibin Jiang (Water Research, 2023)

Exploring the seasonality of surface urban heat islands using enhanced land surface temperature in a semi-arid city - Liying Han; Linlin Lu; Peng Fu; Chao Ren; Meng Cai; Qingting Li (Urban Climate, 2023)

Contrasting determinants of land surface temperature in three megacities: Implications to cool tropical metropolitan regions - Linlin Lu; Peng Fu; Ashraf Dewan; Qingting Li (Sustainable Cities and Society, 2023)

Analysing the factors affecting medical waste generation in China - Yanhong Hou; Linlin Jia; Wenting Ma; Jian Li Hao (Sustainable Chemistry and Pharmacy, 2023)

Atomic-level chemical reaction promoting external quantum efficiency of organic photomultiplication photodetector exceeding 108% for weak-light detection - Linlin Shi; Yizhi Zhu; Guohui Li; Ting Ji; Wenyan Wang; Ye Zhang; Yukun Wu; Yuying Hao; Kaiying Wang; Jun Yuan; Yingping Zou; Beng S. Ong; et al. (Science Bulletin, 2023)

Cloning and expression of the mitochondrial cytochrome c oxidase subunit II gene in Sitophilus zeamais and interaction mechanism with allyl isothiocyanate - Linlin Jiang; Yue Li; Weilin Shi; Wei Chen; Zhiqing Ma; Juntao Feng; Ahmed S. Hashem; Hua Wu (Pesticide Biochemistry and Physiology, 2023)

Buckling failure mechanism and critical buckling load prediction method of super-long piles in soft-clay ground in deep water - Linlin He; Zhisong Li; Yuanshi Xie; Yang Liu; Mingwei Liu (Ocean Engineering, 2023)

Biosynthesis of pectic oligosaccharide-based amphiphiles as novel stabilizers of nanoemulsions by coupling enzymatic depolymerization with alkyl/alkenyl succinylation - Linlin Li; Ziqian Li; Thomas Balle; Guoqin Liu; Zheng Guo (Food Hydrocolloids, 2023)

Self-powered energy harvesting and implantable storage system based on hydrogel-enabled all-solid-state supercapacitor and triboelectric nanogenerator - Zhuo Wang; Shuncheng Yao; Shaobo Wang; Zhirong Liu; Xingyi Wan; Quanhong Hu; Yunchao Zhao; Cheng Xiong; Linlin Li (Chemical Engineering Journal, 2023)

Citrate-enhanced leaching of arsenic from coal with simulated flue gas under UV irradiation - Shun Qiu; Zhenzhen Lu; Wenshou Sun; Linlin Tao; Jin Li; Jintong Li (Chemical Engineering Journal, 2023)

Applying correlation analysis to electrode optimization in source domain - Yuxin Dong; Linlin Wang; Mingai Li (Medical & Biological Engineering & Computing, 2023)

Singlet oxygen generation in light-assisted peroxymonosulfate activation by carbon nitride: Role of elevated crystallinity - Beizhao Chen; Xun Liu; Bei Liu; Qi Han; Li Li; Li Wang; Yufei Shu; Linlin Zang; Wenlei Zhu; Zhongying Wang (Chemosphere, 2023)

Accumulation and speciation of arsenic in Eisenia fetida in sodium arsenite spiked soils - A dynamic interaction between soil and earthworms - Weiqin Xing; Hongpei Geng; Yali Wang; Linlin Zhao; Yongqiang Yang; Yale Wang; Shuhang Tian; Yongxin Cao; Zhe Zhang; Liping Li (Chemosphere, 2023)

Environmental DNA metabarcoding reveals the influence of human activities on microeukaryotic plankton along the Chinese coastline - Zheng Zhang; Jiang Li; Hongjun Li; Linlin Wang; Yuqi Zhou; Shuzhen Li; Zhaojing Zhang; Kai Feng; Ye Deng (Water Research, 2023)

Global analysis of gene expression profiles and gout symptoms in goslings infected with goose astrovirus - Chenggang Liu; Linlin Li; Jiawen Dong; Junqin Zhang; Yunzhen Huang; Qi Zhai; Yong Xiang; Jin Jin; Xianshe Huang; Gang Wang; Minhua Sun; Ming Liao (Veterinary Microbiology, 2023)

Source apportionment of heavy metals in the soil at the regional scale based on soil-forming processes - Bo Wu; Linlin Li; Shuhai Guo; Yang Li (Journal of Hazardous Materials, 2023)

Simultaneous oxidation and absorption of nitric oxide and sulfur dioxide by peroxymonosulfate activated by bimetallic metal-organic frameworks - Zhaoxin Wan; Xiude Hu; Chengbo Li; Jiawei Zhang; Qi Wang; Long Fang; Linlin Zhang; Qingjie Guo; Deshuai Sun (Journal of Environmental Chemical Engineering, 2023)

Bimetal Cu and Fe modified g-C3N4 sheets grown on carbon skeleton for efficient and selective photocatalytic reduction of CO2 to CO - Songyuan Bian; Xueyan Li; Long Zhang; Libin Wang; Jingzhen Wang; Qing Xu; Linlin Zang; Yanhong Zhang; Liguo Sun (Journal of Environmental Chemical Engineering, 2023)

Water/acid/reductive biomass leaching of Cr(VI) in chromium ore processing residue (CORP) for safe discharge of effluent and to recover Cr(III) and gypsum - Zhenan Jin; Baoren Wang; Feixian Zheng; Linlin Tong; Jiafeng Li; Qianfei Zhao; Liuhan Jin (Hydrometallurgy, 2023)

Mineralogical characteristics and recovery process optimization analysis of a refractory gold ore with gold particles mainly encapsulated in pyrite and Arsenopyrite - Jiafeng Li; Hongying Yang; Rongxin Zhao; Linlin Tong; Qiao Chen (Geochemistry, 2023)

Interactions between zein and anthocyanins at different pH: Structural characterization, binding mechanism and stability - Shuangjian Li; Xiang Wang; Xiaoqian Zhang; Hui Zhang; Siyuan Li; Jianzhong Zhou; Linlin Fan (Food Research International, 2023)

The structural characterization of polysaccharides from three cultivars of Moringa oleifera Lam. root and their effects on human intestinal microflora - Linlin Jia; Xiaoqiang Peng; Zeyuan Deng; Bing Zhang; Hongyan Li (Food Bioscience, 2023)

Spatial distribution patterns across multiple microbial taxonomic groups - Xiongfeng Du; Songsong Gu; Zheng Zhang; Shuzhen Li; Yuqi Zhou; Zhaojing Zhang; Qi Zhang; Linlin Wang; Zhicheng Ju; Chengliang Yan; Tong Li; Danrui Wang; et al. (Environmental Research, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

A Tiered Ecological Risk Assessment of Caffeine by Using Species Sensitivity Distribution Method in the Nansi Lake Basin - Lei Zheng; Juan Zhang; Yinan Wu; Linlin Li; Junhong Ling; Sai Wang; Wenlong Yang; Yezhu Yin; Liang Dong; Yizhang Zhang (Bulletin of Environmental Contamination and Toxicology, 2023)

Performance of wetland applied to ecological remediation of abandoned fish ponds: A case study in Gonghu Bay, Tai lake - Linlin Li; Jing Zhang; Shaoyong Lu; Hongbin Lu; Zhichao Du; Bin Bi; Fengmei Cao; Weijing Kong (Chemosphere, 2023)

Relationships between denitrification rates and functional gene abundance in a wetland: The roles of single- and multiple-species plant communities - Yushuang Kong; Haikuo Zhang; Linlin Tian; Junji Yuan; Youchao Chen; Yan Li; Jian Chen; Scott X. Chang; Yunying Fang; Ehsan Tavakkoli; Yanjiang Cai (Science of The Total Environment, 2023)

Bioimmobilization and transformation of chromium and cadmium in the fungi-microalgae symbiotic system - Junjun Wang; Qinghua Tian; Linlin Cui; Jinju Cheng; Hao Zhou; Yejuan Zhang; Anan Peng; Li Shen (Journal of Hazardous Materials, 2023)

High Fischer ratio peptide of hemp seed: Preparation and anti-fatigue evaluation in vivo and in vitro - Zhu Ying; Huang Yuyang; Li Meiying; Sun Bingyu; Liu Linlin; Lv Mingshou; Qu Min; Guan Huanan; Zhu Xiuqing (Food Research International, 2023)

Colorimetric active carboxymethyl chitosan/oxidized sodium alginate-Oxalis triangularis ssp. papilionacea anthocyanins film@gelatin/zein-linalool membrane for milk freshness monitoring and preservation - Linlin Li; Li Xia; Feng Xiao; Yewen Xiao; Lanhua Liu; Shaotong Jiang; Hualin Wang (Food Chemistry, 2023)

Enhanced antihypertensive potential of fermented pomegranate juice: The contribution of phenolic compounds biotransformation and the resultant angiotensin-I-converting enzyme inhibition mechanism - Li Chen; Linlin Wang; Guowei Shu; Jiaojiao Yuan; Jiying Zhang; Shan Qin; Jianke Li (Food Chemistry, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

Development of Zein/tannic acid nanoparticles as antioxidants for oxidation inhibition of blackberry seed oil emulsions - Shuangjian Li; Siyuan Li; Minhui Gong; Hongzhi Zhang; Linlin Fan; Xiaoli Liu; Jianzhong Zhou (Food Chemistry, 2023)

Preparation of PLGA/ε-polylysine nanofibers and their application for pork preservation - Minmin Chen; Linlin Li; Li Xia; Yaqiong Kong; Suwei Jiang; Xiaoju Chen; Hualin Wang (Food Packaging and Shelf Life, 2023)

Arsenic Exposure, Periconceptional Folic Acid Supplementation, and the Risk for Neural Tube Defects: A Case–Control Study - Xin Pi; Chengrong Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Jufen Liu; Yali Zhang; Aiguo Ren (Exposure and Health, 2023)

A High Concentration of Polycyclic Aromatic Hydrocarbons in Umbilical Cord Tissue is Associated with an Increased Risk for Fetal Neural Tube Defects - Shengju Yin; Ying Sun; Jinhui Yu; Zaiming Su; Mingkun Tong; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2023)

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Contribution of the TGFβ signaling pathway to pigmentation in sea cucumber (Apostichopus japonicus) - Linlin Yao; Bin Zhao; Qi Wang; Xuyang Jiang; Sha Han; Wei Hu; Chenglin Li (Frontiers in Marine Science, 2023)
Pigmentation mediated by the transforming growth factor β (TGFβ) signaling pathway is a key trait for understanding environmental adaptability and species stability. In this study, TGFβ signaling pathway members and their expression patterns in different color morphs of the sea cucumber Apostichopus japonicus were evaluated. Using a bioinformatics approach, 22 protein sequences of TGFβ signaling pathway members in A. japonicus were classified, including 14 that were identified for the first time in the species, including 7 ligands, 6 receptors, and 1 R-Smad. We further evaluated mRNA expression data for different color morphs and pigmentation periods. These results support the hypothesis that both subfamilies of the TGFβ superfamily, i.e., the TGFβ/activin/Nodal and BMP/GDF/AMH subfamilies, are involved in the regulation of pigmentation in A. japonicus . The former subfamily was complete and contributes to the different color morphs. The BMP/GDF/AMH subfamily was incomplete. BMP2/4-induced differentiation of white adipocytes was regulated by the BMP2/4–ACVR2A–Smad1 signaling pathway. These findings provide insight into the TGFβ family in early chordate evolution as well as the molecular basis of color variation in an economically valuable species.

Comparison of nitrogen removal performance and mechanism from low-polluted wastewater by constructed wetlands with two oxygen supply strategies: Tidal flow and intermittent aeration - Linlin Li; Jing Zhang; Qiuyue Shi; Shaoyong Lu (Chemosphere, 2023)

Crop type mapping in the central part of the North China Plain using Sentinel-2 time series and machine learning - Ke Luo; Linlin Lu; Yanhua Xie; Fang Chen; Fang Yin; Qingting Li (Computers and Electronics in Agriculture, 2023)

Spatial effects of urban green infrastructure on instream water quality assessed by chemical and sensory indicators - Juan Li; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Linlin Zhang; Tao Lin; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Science of The Total Environment, 2023)

Understanding the N-acylated homoserine lactones(AHLs)-based quorum sensing for the stability of aerobic granular sludge in the aspect of substrate hydrolysis enhancement - Zhiming Zhang; Linlin Wang; Yatong Ji; Runjuan Cao; Jiaheng Zhou; Mengyan Li; Liang Zhu; Xiangyang Xu (Science of The Total Environment, 2023)

Comprehensively investigating performance and potential mechanism of anammox-based nitrogen removal process with different microbial morphologies under mainstream conditions - Shuang Liu; Xinxin Xu; Hongli Li; Ming Zeng; Linlin Hao; Ruihua Zhao; Jingguo Cao; Nan Wu; Zongpeng Zhang (Journal of Environmental Chemical Engineering, 2023)

Insight into the design and construction of Cr substituted Co-based columnar activated coke catalysts for effective and reliable removal of methylbenzene and Hg0 concurrently - Lei Gao; Lei Yi; Dong Xie; Hanqing Wang; Caiting Li; Linlin Li; Yijin Liu; Jinke Xie; Yihui Zhou; Yingyun Liu (Fuel, 2023)

Study on antibacterial mechanism of electron beam radiation on Aspergillus flavus - Linlin Fan; Lili Li; Feifei Shang; Yuhua Xie; Zhenhua Duan; Qianwei Cheng; Yuqiao Zhang (Food Bioscience, 2023)

Air pollution exposure and ovarian reserve impairment in Shandong province, China: The effects of particulate matter size and exposure window - Lihong Pang; Wenhao Yu; Jiale Lv; Yunde Dou; Han Zhao; Shanshan Li; Yuming Guo; Gongbo Chen; Linlin Cui; Jingmei Hu; Yueran Zhao; Qi Zhao; et al. (Environmental Research, 2023)

Electrochemical lithium ion pumps for lithium recovery: A systematic review and influencing factors analysis - Guiling Luo; Xiaowei Li; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Desalination, 2023)

Preparation of high hydrophilic H2TiO3 ion sieve for lithium recovery from liquid lithium resources - Jing Sun; Xiaowei Li; Yuhong Huang; Guiling Luo; Duanjian Tao; Jiangtao Yu; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2023)

Cenozoic plants from Tibet: An extraordinary decade of discovery, understanding and implications - Zhekun Zhou; Jia Liu; Linlin Chen; Robert A. Spicer; Shufeng Li; Jian Huang; Shitao Zhang; Yongjiang Huang; Linbo Jia; Jinjin Hu; Tao Su (Science China Earth Sciences, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

microRNA-29b-3p/sirtuin-1/peroxisome proliferator–activated receptor γ suppress osteogenic differentiation - Huanxin Xie; Lei Cao; Linlin Ye; Qiang Li; Yaohua Zhang; Hongyue Zhang; Huaqing Yang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Otus scops adenovirus: the complete genome sequence of a novel aviadenovirus discovered in a wild owl - Weibo Zheng; Tingshu Jiang; Zhe Zhang; Dong Pan; Wenli Tang; Youzhi Li; Linlin Jiang; Hongwei Zhu; Xin Yu; Guozhong Chen; Jiao Wang; Jianlong Zhang; et al. (Archives of Virology, 2023)

Heterosis in growth and low temperature tolerance in Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) - Shuai Chen; Yongsheng Tian; Zhentong Li; Yang Liu; Ziqi Li; Pengfei Duan; Linlin Li; Xinyi Wang; Linna Wang; Xinlei He; Xia Zhao; Wensheng Li; et al. (Aquaculture, 2023)

RETRACTED: Study on the effect of SDBS and SDS on deep coal seam water injection - Lianman Xu; Yajing Li; Linlin Du; Fengshuo Yang; Runjie Zhang; Hao Wei; Gang Wang; Zhe Hao (Science of The Total Environment, 2023)

Interaction mechanisms of fouling and cleaning protocol for A/O-MBR treatment of coal⁃to⁃hydrogen wastewater - Fang Gao; Lingyun Li; Yanwei Shi; Xiaofei Xue; Jianhua Mao; Linlin Xing; Xiaoyan Yao (Process Safety and Environmental Protection, 2023)

Methylmercury promotes oxidative stress and autophagy in rat cerebral cortex: Involvement of PI3K/AKT/mTOR or AMPK/TSC2/mTOR pathways and attenuation by N-acetyl-L-cysteine - Yanfeng Wei; Linlin Ni; Jingjing Pan; Xiaoyang Li; Yu Deng; Bin Xu; Tianyao Yang; Jingyi Sun; Wei Liu (Neurotoxicology and Teratology, 2023)

Responses and tolerance mechanisms of microalgae to heavy metal stress: A review - Xinfeng Xiao; Wenfang Li; Meng Jin; Linlin Zhang; Liguo Qin; Weiwei Geng (Marine Environmental Research, 2023)

Different nitrogen fertilizer application in the field affects the morphology and structure of protein and starch in rice during cooking - Shijie Shi; Gaoyu Zhang; Linlin Chen; Wenhui Zhang; Xiaodong Wang; Keqiang Pan; Lina Li; Jing Wang; Juan Liu; Cougui Cao; Yang Jiang (Food Research International, 2023)

Alkylsuccinylated oxidized cellulose-based amphiphiles as a novel multi-purpose ingredient for stabilizing O/W emulsions - Ziqian Li; Sampson Anankanbil; Linlin Li; Jiabao Lyu; Marcin Nadzieja; Zheng Guo (Food Hydrocolloids, 2023)

CuO nanosheets incorporated scrap steel slag coupled with persulfate catalysts for high-efficient degradation of sulfonamide from water - Keke Yin; Linlin Hao; Guiju Li (Environmental Research, 2023)

Pseudo-isotopic substituted (Co0.5Ni0.5)S2 anchoring on V4C3T MXene as an efficient anode for full sodium-ions batteries - Yilin Li; J.M. Cao; Linlin Li; Zeyu Yuan; Dongdong Li; Junzhi Li; Yuming Zhang; Hao Xu; Wei Han; Lili Wang (Chemical Engineering Journal, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Flexible and highly piezoelectric nanofibers with organic–inorganic coaxial structure for self-powered physiological multimodal sensing - Xingyi Wan; Zhuo Wang; Xinyang Zhao; Quanhong Hu; Zhou Li; Zhong Lin Wang; Linlin Li (Chemical Engineering Journal, 2023)

Ethylene-vinyl alcohol copolymer/gelatin/cellulose acetate bionic trilayer fibrous membrane for moisture-adjusting - Li Xia; Linlin Li; Yewen Xiao; Feng Xiao; Wei Ji; Shaotong Jiang; Hualin Wang (Carbohydrate Polymers, 2023)

TRIM11, a new target of p53, facilitates the migration and invasion of nasopharyngeal carcinoma cells - Ziyi Zhao; Jinkuang Deng; Ming Lu; Jun Yang; Linlin Chen; DianYuan Li; Yi Sang (Molecular Biology Reports, 2023)
Background Although tripartite motif-containing protein 11 (TRIM11) is known to be associated with a variety of cancers, its role in nasopharyngeal carcinoma (NPC) is unclear. Methods and results To investigate the role of TRIM11 in NPC, TRIM11 was stably overexpressed in 6–10B and CNE2 cells with lentiviral vectors and knocked down in S18 and 5–8F cells using the CRISPR/Cas9 system. Transwell assays and wound-healing assays revealed that TRIM11 facilitated the migration and invasion of NPC cells. Mechanistically, we found that p53 inhibits TRIM11 expression by binding to its promoter. Conclusions TRIM11 may serve as a potential diagnostic marker for NPC and has a certain therapeutic value.

Investigation of the mechanism of copy number variations involving the α-globin gene cluster on chromosome 16: two case reports and literature review - Dina Zhu; Linlin Xu; Yanxia Zhang; Guanxia Liang; Xiaofeng Wei; Liyan Li; Wangjie Jin; Xuan Shang (Molecular Genetics and Genomics, 2023)

Fluoride-Induced Sperm Damage and HuR-Mediated Excessive Apoptosis and Autophagy in Spermatocytes - Yanyan Li; Jianbin Zhang; Linlin Sun; Hongyu Zhao; Xiaohan Jia; Yingri Zhang; Yuanbin Li (Biological Trace Element Research, 2023)

High-quality chromosome-level genome assembly of Pacific cod, Gadus macrocephalus - Yiqing Ma; Yuan Li; Chen Jiang; Li Zheng; Shenghao Liu; Linlin Zhao (Frontiers in Marine Science, 2022)

Golden 2-like transcription factor contributes to the major QTL against rice black-streaked dwarf virus disease - Xuejuan Li; Feng Lin; Chenyang Li; Linlin Du; Zhiyang Liu; Wenjuan Shi; Jianying Lv; Xiaoyan Cao; Ying Lan; Yongjian Fan; Yijun Zhou; Tong Zhou (Theoretical and Applied Genetics, 2022)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Talaromyces marneffei Infections in 8 Chinese Children with Inborn Errors of Immunity - Linlin Wang; Ying Luo; Xiaolin Li; Yixian Li; Yu Xia; Tingyan He; Yanyan Huang; Yongbin Xu; Zhi Yang; Jiayun Ling; Ruohang Weng; Xiaona Zhu; et al. (Mycopathologia, 2022)
Purpose Talaromyces marneffei (TM) is an opportunistic fungus leading to multi-organ damages and poor prognosis in immunocompromised individuals. TM infections in children are rare and our knowledge to TM infection is insufficient. To investigate the clinical characteristics of TM-infected children and to explore the underlying mechanisms for host against TM, we analysed TM-infected patients diagnosed in our hospital. Methods Eight patients with TM infections have been identified in Shenzhen Children’s Hospital during 2017–2021. Clinical data were collected from medical records. Immunological features were evaluated by flow cytometry. Literatures were also reviewed to summarize the reported inborn errors of immunity (IEIs) with TM infections. Results All 8 children were HIV-negative. The most common symptom of TM infections was fever (8/8), followed by weight loss (7/8), pneumonia (7/8), hepatomegaly (7/8), splenomegaly (6/8), anemia (6/8), lymphadenopathy (5/8), thrombocytopenia (3/8), diarrhea (3/8), rashes or skin lesions (3/8), and osteolytic lesions (1/8). Five children died during the follow-ups. CD3+ T cells were decreased in 6 patients. Eight patients had reduced natural killer cells. All patients went gene sequencing and were finally diagnosed as IEIs, including STAT1 gain-of-function, IL-2 receptor common gamma chain deficiency, adenosine deaminase deficiency, CD40 ligand deficiency, and STAT3 deficiency. Another 4 types of IEIs (CARD9, IFN- γ receptor 1, RelB, and NFKB2 deficiency), have been reported with TM infections based on literature review. Conclusion TM infections resulted in systemic injuries and high mortality. The spectrum of IEIs underlying TM infections indicated that T cell-mediated immunity, IFN- γ , IL-17 signalings and NF-κB pathways were important for host responses against TM infection. In reverse, for HIV-negative children without other secondary immunodeficiencies, IEIs should be considered in TM-infected children.

Increased Expression of CD95 in CD4+ Effector Memory T Cells Promotes Th17 Response in Patients with Myasthenia Gravis - Xiaoyu Huang; Jie Zhu; Tan Liu; Fengzhan Li; Tingting Yang; Hao Li; Fei Chen; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; Deqin Geng (Journal of Neuroimmune Pharmacology, 2022)

The atypical functional connectivity of Broca’s area at multiple frequency bands in autism spectrum disorder - Lulu Cheng; Linlin Zhan; Lina Huang; Hongqiang Zhang; Jiawei Sun; Guofeng Huang; Yadan Wang; Mengting Li; Huayun Li; Yanyan Gao; Xize Jia (Brain Imaging and Behavior, 2022)

Core rhizosphere microbiome of Panax notoginseng and its associations with belowground biomass and saponin contents - Guangfei Wei; Guozhuang Zhang; Mengzhi Li; Congsheng Liu; Fugang Wei; Yong Wang; Zhixin Huang; Zhongjian Chen; Yuqing Zheng; Shilin Chen; Linlin Dong (Environmental Microbiology, 2022)
The core rhizosphere microbiome is critical for plant fitness. However, its contribution to the belowground biomass and saponin contents of Panax notoginseng remains unclear. High‐throughput sequencing of amplicon and metagenome was performed to obtain the microbiome profiles and functional traits in P. notoginseng rhizosphere across a large spatial scale. We obtained 639 bacterial and 310 fungal core OTUs, which were mainly affected by soil pH and organic matter (OM). The core taxa were grouped into four ecological clusters (i.e. high pH, low pH, high OM and low OM) for sharing similar habitat preferences. Furthermore, structural equation modelling (SEM) and correlation analyses revealed that the diversity and composition of core microbiomes, as well as the metagenome‐derived microbial functions, were related to belowground biomass and saponin contents. Key microbial genera related to the two plant indicators were also identified. In short, this study explored the main driving environmental factors of core microbiomes in the P. notoginseng rhizosphere and revealed that the core microbiomes and microbial functions potentially contributed to the belowground biomass and saponin contents of the plant. This work may enhance our understanding of interactions between microbes and perennial plants and improve our ability to manage root microbiota for the sustainable production of herbal medicine.

Prenatal exposure to silver is associated with an elevated risk for neural tube defects: a case–control study - Xin Pi; Chengrong Wang; Di Wang; Shengju Yin; Lei Jin; Zhiwen Li; Linlin Wang; Wentao Yue; Chenghong Yin; Aiguo Ren (Environmental Science and Pollution Research, 2022)

LaeA regulates morphological development and ochratoxin A biosynthesis in Aspergillus niger - Mengwei Zhang; Yan Yang; Linlin Li; Shuwen Liu; Xianli Xue; Qiang Gao; Depei Wang; Ying Zhang; Jian Zhang (Mycotoxin Research, 2022)

High levels of serum IL-10 indicate disease progression, extramedullary involvement, and poor prognosis in multiple myeloma - Xiaoyan Yue; Linlin Huang; Yang Yang; Yi Zhao; Donghua He; Xiaoyan Han; Gaofeng Zheng; Yi Li; Enfan Zhang; Zhen Cai; Xin Huang; Jingsong He (Journal of Zhejiang University-SCIENCE B, 2022)

Tumor necrosis factor-α coordinates with transforming growth factor-β1 to induce epithelial-mesenchymal transition and migration via the NF-κB/NOX4 pathway in bronchial epithelial cells - Ke Li; Rong Zhou; Mingze Ma; Chaomei Jin; Linlin Jiao; Siyu Zhang; Mei Tian; Fang Zhou (Molecular Biology Reports, 2022)

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Taxonomic Composition and Spatial Distribution of Meiofauna Community from a Sandy Intertidal Zone in Sishili Bay, Yellow Sea Coast (Northern China) - Olga N. Pavlyuk; Yulia A. Trebukhova; Ilya A. Shcherbakov; Tatiana S. Tarasova; Konstantin A. Lutaenko; Linlin Chen; Bo Song; Xiaojing Li; Baoquan Li (Journal of Ocean University of China, 2022)

Identification and Characterization of the Homeobox Gene Family in Fusarium pseudograminearum Reveal Their Roles in Pathogenicity - Yuming Ma; Jingya Zhao; Wenbo Chen; Xuejing Geng; Tianli He; Shengli Ding; Bingjian Sun; Honglian Li; Linlin Chen (Biochemical Genetics, 2022)

The Structure and Function of Microbial Community in Rhizospheric Soil of American Ginseng (Panax quinquefolius L.) Changed with Planting Years - Guozhong Chen; Ying Xue; Xin Yu; Chongwei Li; Yuping Hou; Hongwei Zhu; Linlin Jiang; Weibo Zheng; Zhibin Feng; Youzhi Li; Wenli Tang; Xiaoyu Zhao; et al. (Current Microbiology, 2022)

The Paleogene to Neogene climate evolution and driving factors on the Qinghai-Tibetan Plateau - Jiagang Zhao; Shufeng Li; Alexander Farnsworth; Paul J. Valdes; Tammo Reichgelt; Linlin Chen; Zhekun Zhou; Tao Su (Science China Earth Sciences, 2022)

Deep-Sea-Derived Fungi as Valuable Producers of Cytotoxic Secondary Metabolites and Their Leads Potential - Guangrong Zhao; Wenli Tang; Jianlong Zhang; Peimin Shi; Youzhi Li; Jiao Wang; Qingqin Shen; Haixia Si; Linlin Jiang; Xin Yu; Hongwei Zhu; Guozhong Chen; et al. (Frontiers in Marine Science, 2022)
Cancer is the leading lethal disease worldwide. Natural products have contributed significantly to the development of approved therapeutic agents. Therefore, research into new bioactive naturally sourced metabolites with lead potential is urgently needed. It is well-known that marine microorganisms are by far one of the most notable and prolific sources of bioactive natural products. Among them, deep-sea-derived fungi are extraordinarily adapted and metabolically active under extreme environmental conditions, which enable them to produce a large number of novel secondary metabolites. Chemical examination of deep-sea-derived fungi has yielded enormous amounts of cytotoxic natural products and potential drug leads. This review summarizes a total of 229 cytotoxic compounds isolated from deep-sea-derived fungi from 2010 to 2021. The emphasis is on the unique chemical diversity of these metabolic products, together with their relevant cytotoxic properties. Among the isolated metabolites, 82 compounds have been found to possess moderate to potent cytotoxic activities. Meanwhile, we also highlight some compounds with potent cytotoxicities (namely “star molecules”) considering their high drug lead potential. This review reveals deep-sea-derived fungi as considerable resources for the development of new drugs and the potential of the newly discovered secondary metabolites as valuable antitumor lead compounds.

Genomic analysis of a recombinant coxsackievirus A19 identified in Xinxiang, China, in 2019 - Liang Yi; Li Zhang; Linlin Feng; Xubo Luan; Qian Zhao; Pengwei Xu; Yinbiao Wang; Ling Tao; Weidong Wu (Archives of Virology, 2022)

Metabolism and pharmacokinetics of mebendazole in Japanese pufferfish ( Takifugu rubripes ) - Lei Men; Yuhan Zhang; Keke Li; Zhongyu Li; Chunbin Li; Xueyuan Zhang; Xiaojie Gong; Linlin Fang (Food Additives & Contaminants: Part A, 2022)

Tsunami hazard assessment in the South China Sea: A review of recent progress and research gaps - Linlin Li; Qiang Qiu; Zhigang Li; Peizhen Zhang (Science China Earth Sciences, 2022)

Lower activity time constraint on the ore-controlling Erdaogou fault in the Qingchengzi orefield of the Liaodong Peninsula, NE China - Yan Zhao; Yuewen Feng; Peng Zhang; Linlin Kou; Zhongzhu Yang; Shenghui Li; Wei Wang (Acta Geochimica, 2022)

Traditional fermented soybean products: processing, flavor formation, nutritional and biological activities - Libo Liu; Xiaoqian Chen; Linlin Hao; Guofang Zhang; Zhao Jin; Chun Li; Yuzhuo Yang; Jiajia Rao; Bingcan Chen (Critical Reviews in Food Science and Nutrition, 2022)

The lag effect of 24-year tobacco consumption on lung cancer mortality in Henan Province, China, 1992 to 2016 - Linlin Li; Jie Lu; Xin Dai; Li Ma; Chongjian Wang; Liyun Feng (Environmental Science and Pollution Research, 2022)

Full-Length Transcriptome of the Whale Shark (Rhincodon typus) Facilitates the Genome Information - Fangrui Lou; Li Wang; Zhiyang Wang; Lei Wang; Linlin Zhao; Qingjie Zhou; Zhichuang Lu; Yongzheng Tang (Frontiers in Marine Science, 2022)
Rhincodon typus is a keystone and indicator species in marine ecosystems. Meanwhile, R. typus has been listed on the IUCN red list of vulnerable species. Here we used ONT platform to determine the full-length (FL) transcriptome of R. typus and obtained 14,930 FL transcripts. Among all FL transcripts, 14,915 transcripts were covered 11,892 genetic loci and 1,642 novel genetic loci were further found. Meanwhile, we identified 714 novel transcripts by compared FL transcripts with the R. typus genome. Based on FL transcripts, we also predicted the distribution patterns of ASs, LncRNAs, polyAs, CDSs and methylation sites on FL transcriptome of R. typus . Furthermore, a total of 31,021 (97.86%) CDSs can obtained annotation information. Overall, our work firstly provided the FL transcriptome and these sequences complete the annotated R. typus genome information. Furthermore, these information are a potential resource to study biological processes of R. typus .

Characterizing the Semi-Volatile Organic Compounds in Runoff from Roads and Other Impervious Surfaces in a Suburban Area of Beijing - Liang Zhang; Haiyan Li; Youshu Wang; Zhichao Yang; Ziyang Zhang; Fei Liu; Linlin Tong; Ying Wang; Yongwei Gong; Hua Yang (Archives of Environmental Contamination and Toxicology, 2022)

Effects of Smooth Cordgrass Spartina alterniflora Invasion on Macrobenthic Fauna in the Yellow River Delta - Shaoyu Jiang; Chuanxin Zhang; Linlin Chen; Chunyun Liu; Lang Yan; Baoquan Li (Wetlands, 2022)

Taxonomy and regeneration of a newly recorded Polychaete Capitella teleta (Annelida, Capitellidae) in the coastal water of Shandong, China - Qian Li; Yongnan Li; Yue Wang; Xuwen Wu; Linlin Zhang (Journal of Oceanology and Limnology, 2022)

Deep convolutional neural network with random field model for lake ice mapping from Sentinel-1 imagery - Zhiguo Ma; Zihao Liu; Jiabin Pu; Linlin Xu; Kui Li; Linglong Wangqu; Rui Wu; Yiyi Ma; Ye Chen; Claude Duguay (International Journal of Remote Sensing, 2021)

Correction to: Synthesis and evaluation of iridium(III) complexes on antineoplastic activity against human gastric carcinoma SGC‑7901 cells - Li Tian; Yuanyuan Zhang; Huiwen Zhang; Yi Zhou; Wenlong Li; Yuhan Yuan; Jing Hao; Linlin Yang; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Atmospheric Structure Observed over the Antarctic Plateau and Its Response to a Prominent Blocking High Event - Jinhuan Zhu; Libo Zhou; Han Zou; Peng Li; Fei Li; Shupo Ma; Linlin Kong (Journal of Meteorological Research, 2021)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Late Eocene sclerophyllous oak from Markam Basin, Tibet, and its biogeographic implications - Linlin Chen; Weiyudong Deng; Tao Su; Shufeng Li; Zhekun Zhou (Science China Earth Sciences, 2021)

Retraction Note to: Rock and soil reconstruction of mountain slope based on embedded Internet of things and evaluation of college students’ physical health - Linlin Li (Arabian Journal of Geosciences, 2021)

Characteristics of Plastic Pollution in the Environment: A Review - Penghui Li; Xiaodan Wang; Min Su; Xiaoyan Zou; Linlin Duan; Hongwu Zhang (Bulletin of Environmental Contamination and Toxicology, 2021)

Decoupling between Oxygen and Radiogenic Isotopes: Evidence for Generation of Juvenile Continental Crust by Partial Melting of Subducted Oceanic Crust - Xuan-Ce Wang; Qiuli Li; Simon A. Wilde; Zheng-Xiang Li; Chaofeng Li; Kai Lei; Shao-Jie Li; Linlin Li; Manoj K. Pandit (Journal of Earth Science, 2021)

Climate change impacts on China’s marine ecosystems - Bin Kang; Gretta T. Pecl; Longshan Lin; Peng Sun; Peidong Zhang; Yuan Li; Linlin Zhao; Xin Peng; Yunrong Yan; Chunyan Shen; Wentao Niu (Reviews in Fish Biology and Fisheries, 2021)

Synthesis and evaluation of iridium(III) complexes on antineoplastic activity against human gastric carcinoma SGC-7901 cells - Li Tian; Yuanyuan Zhang; Huiwen Zhang; Yi Zhou; Wenlong Li; Yuhan Yuan; Jing Hao; Linlin Yang; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2021)

A leucoanthocyanidin dioxygenase gene (RtLDOX2) from the feral forage plant Reaumuria trigyna promotes the accumulation of flavonoids and improves tolerance to abiotic stresses - Ningning Li; Xue Wang; Binjie Ma; Zhigang Wu; Linlin Zheng; Zhi Qi; Yingchun Wang (Journal of Plant Research, 2021)

RETRACTED ARTICLE: Rock and soil reconstruction of mountain slope based on embedded Internet of things and evaluation of college students’ physical health - Linlin Li (Arabian Journal of Geosciences, 2021)

Estimation of the SARS-CoV-2 transmission probability in confined traffic space and evaluation of the mitigation strategies - Linlin Chen; Guangze Ban; Enshen Long; Gretchen Kalonji; Zhu Cheng; Li Zhang; Shurui Guo (Environmental Science and Pollution Research, 2021)

Genome-wide association study of grain shapes in Aegilops tauschii - Xinpeng Zhao; Linlin Lv; Jiahui Li; Feifei Ma; Shenglong Bai; Yun Zhou; Dale Zhang; Suoping Li; Chun-peng Song (Euphytica, 2021)

Biochar Derived from Treated Lotus Stem and Adsorption of Phthalic Acid Esters - Ruiling Zhang; Linlin Chen; Binbin Qiu; Xiaojing Sun; Songyan Qin; Bo Wang; Feiyue Li; Lixin Zhao; Zhe Zhu (Water, Air, & Soil Pollution, 2021)

A July-August relative humidity record in North China since 1765 AD reconstructed from tree-ring cellulose δ18O - Linlin Cui; Yu Liu; Qiang Li; Huiming Song; Congxi Fang (International Journal of Biometeorology, 2021)

Occurrence, spatial distribution, source, and ecological risk assessment of organochlorine pesticides in Dongting Lake, China - Fengmei Cao; Zhaozhao Li; Qi He; Shaoyong Lu; Pan Qin; Linlin Li (Environmental Science and Pollution Research, 2021)

The behavioral and antioxidant response of the bivalve Gomphina veneriformis to sediment burial effect - Xiaojing Li; Linlin Chen; Zhengquan Zhou; Baoquan Li; Xin Liu (Acta Oceanologica Sinica, 2021)

A Role for Transmembrane Protein 16C/Slack Impairment in Excitatory Nociceptive Synaptic Plasticity in the Pathogenesis of Remifentanil-induced Hyperalgesia in Rats - Yize Li; Linlin Zhang; Jing Li; Chunyan Wang; Yi Chen; Yuan Yuan; Keliang Xie; Guolin Wang; Yonghao Yu (Neuroscience Bulletin, 2021)

Effect of divalent manganese (Mn2+) concentration on the growth and nitrate nitrogen content of lettuce during aeroponic intercropping with cherry radish - Lei Zhang; Linlin Wang; Faqinwei Li; Fei Xiao; Haiye Yu (Horticulture, Environment, and Biotechnology, 2021)

Comparison of Class 2 Integron Integrase Activities - Xiaotong Wang; Nana Kong; Mei Cao; Long Zhang; Muzhen Sun; Linlin Xiao; Gang Li; Quhao Wei (Current Microbiology, 2021)

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

Removal of ammonia nitrogen from water by mesoporous carbon electrode–based membrane capacitance deionization - Guiju Li; Yaning Cao; Zhen Zhang; Linlin Hao (Environmental Science and Pollution Research, 2021)

Long non-coding RNA HCG18 promotes M1 macrophage polarization through regulating the miR-146a/TRAF6 axis, facilitating the progression of diabetic peripheral neuropathy - Wei Ren; Guangxia Xi; Xing Li; Lingxia Zhao; Kun Yang; Xuemei Fan; Linlin Gao; Hongmei Xu; Jianjin Guo (Molecular and Cellular Biochemistry, 2021)

Seasonal variation of net ecosystem CO2 exchange and its influencing factors in an apple orchard in the Loess Plateau - Jianfeng Yang; Yumin Duan; Linlin Wang; Dan Kang; Mukesh Kumar Awasthi; Huike Li; Linsen Zhang (Environmental Science and Pollution Research, 2020)

Three dimensional convolutional neural network-based classification of conduct disorder with structural MRI - Jianing Zhang; Xuechen Li; Yuexiang Li; Mingyu Wang; Bingsheng Huang; Shuqiao Yao; Linlin Shen (Brain Imaging and Behavior, 2020)

Do Supercontinent-Superplume Cycles Control the Growth and Evolution of Continental Crust? - Xuan-Ce Wang; Simon A. Wilde; Zheng-Xiang Li; Shaojie Li; Linlin Li (Journal of Earth Science, 2020)

Correction to: Reassessment of the 1907 Sumatra “Tsunami Earthquake” Based on Macroseismic, Seismological, and Tsunami Observations, and Modeling - Stacey Servito Martin; Linlin Li; Emile A. Okal; Julie Morin; Alexander E. G. Tetteroo; Adam D. Switzer; Kerry E. Sieh (Pure and Applied Geophysics, 2020)

Spatio-temporal variation of subtidal macrobenthic fauna and the ecological assessment of Longkou Artificial Island construction in Bohai Sea, China - Xiaojing Li; Linlin Chen; Zhengquan Zhou; Baoquan Li; Xin Liu; Lufei Yang; Bo Liu; Bo Song (Journal of Oceanology and Limnology, 2020)

Enhanced mass transfer and service time of mesh Ti/Sb-SnO2 electrode for electro-catalytic oxidation of phenol - Linlin Huang; Da Li; Junfeng Liu; Lisha Yang; Changchao Dai; Nanqi Ren; Yujie Feng (Environmental Science and Pollution Research, 2020)

The immune response to a recombinant Lactococcus lactis oral vaccine against foot-and-mouth disease virus in mice - Xinsheng Liu; Linlin Qi; Jianliang Lv; Zhongwang Zhang; Peng Zhou; Zhongyuan Ma; Yonglu Wang; Yongguang Zhang; Li Pan (Biotechnology Letters, 2020)

A benchmark city for seismic resilience assessment - Qingxue Shang; Xiaodong Guo; Quanwang Li; Zhen Xu; Linlin Xie; Chaofeng Liu; Jichao Li; Tao Wang (Earthquake Engineering and Engineering Vibration, 2020)

Resilience-based retrofitting of existing urban RC-frame buildings using seismic isolation - Cantian Yang; Linlin Xie; Aiqun Li; Demin Zeng; Junbo Jia; Xi Chen; Min Chen (Earthquake Engineering and Engineering Vibration, 2020)

DNA Methylation Analysis of the NR3C1 Gene in Patients with Schizophrenia - Linlin Liu; Jian Wu; Lili Qing; Jiajue Li; Hao Yang; Aicen Ji; Ming Yan; Liping Hu; Shengjie Nie (Journal of Molecular Neuroscience, 2020)

Evaluation and spatiotemporal characteristics of glacier service value in the Qilian Mountains - Meiping Sun; Weiqian Ma; Xiaojun Yao; Linlin Zhao; Zhongqin Li; Dahe Qin (Journal of Geographical Sciences, 2020)

Correction to: Microbial synergy and stoichiometry in heap biooxidation of low-grade porphyry arsenic-bearing gold ore - Jiafeng Li; Linlin Tong; Yu Xia; Hongying Yang; Wolfgang Sand; Hongzhen Xie; Bibo Lan; Shuiping Zhong; Ali Auwalu (Extremophiles, 2020)

Microbial synergy and stoichiometry in heap biooxidation of low-grade porphyry arsenic-bearing gold ore - Jiafeng Li; Linlin Tong; Yu Xia; Hongying Yang; Wolfgang Sand; Hongzhen Xie; Bibo Lan; Shuiping Zhong; Ali Auwalu (Extremophiles, 2020)

Variability of voriconazole concentrations in patients with hematopoietic stem cell transplantation and hematological malignancies: influence of loading dose, procalcitonin, and pregnane X receptor polymorphisms - Guangting Zeng; Linlin Wang; Lihong Shi; Huilan Li; Miaomiao Zhu; Jia Luo; Zanling Zhang (European Journal of Clinical Pharmacology, 2020)

Controlled synchronization of prolactin/STAT5 and AKT1/mTOR in bovine mammary epithelial cells - Baosheng Wang; Linlin Shi; Jingjing Men; Qingzhang Li; Xiaoming Hou; Chunmei Wang; Feng Zhao (In Vitro Cellular & Developmental Biology - Animal, 2020)

Cutibacterium acnes Type II strains are associated with acne in Chinese patients - Shuyang Zhao; Jiayu Ci; Jinhui Xue; Yaofeng Wang; Xuelong Li; Linlin Hao; Liu Tian; Haiyan Guo; Chengqi Xin; Yujie Zhao (Antonie van Leeuwenhoek, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Physiological responses of yellow-horn seedlings to high temperatures under drought condition - Hua Jin; Jixiang Zou; Linlin Li; Xinlei Bai; Tong Zhu; Junbao Li; Bingcheng Xu; Zhi Wang (Plant Biotechnology Reports, 2020)

Riverbed armoring and sediment exchange process in a sand–gravel bed reach after the Three Gorges Project operation - Linlin Li; Junqiang Xia; Meirong Zhou; Shanshan Deng (Acta Geophysica, 2020)

Identification of Fusarium graminearum-responsive miRNAs and their targets in wheat by sRNA sequencing and degradome analysis - Xiaojie Jin; Linlin Jia; Yongxia Wang; Baoquan Li; Dongfa Sun; Xueyan Chen (Functional & Integrative Genomics, 2020)

Effects of Vitamin E and Selenium on Growth Performance, Antioxidant Capacity, and Metabolic Parameters in Growing Furring Blue Foxes (Alopex lagopus) - Keyuan Liu; Hanlu Liu; Ting Zhang; Linlin Mu; Xueqing Liu; Guangyu Li (Biological Trace Element Research, 2019)

Wheat methionine sulfoxide reductase A4.1 interacts with heme oxygenase 1 to enhance seedling tolerance to salinity or drought stress - Pengcheng Ding; Linlin Fang; Guangling Wang; Xiang Li; Shu Huang; Yankun Gao; Jiantang Zhu; Langtao Xiao; Jianhua Tong; Fanguo Chen; Guangmin Xia (Plant Molecular Biology, 2019)

A reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay for detecting the pathogen of maize rough dwarf disease in China - Linlin Du; Wenjuan Shi; Xuejuan Li; Ying Lan; Feng Sun; Yongjian Fan; Tong Zhou; Yijun Zhou (Australasian Plant Pathology, 2019)

Effects of key species mud snail Bullacta exarata (Gastropoda) on oxygen and nutrient fluxes at the sediment-water interface in the Huanghe River Delta, China - Baoquan Li; Tjeerd J. Bouma; Quanchao Wang; Laura M. Soissons; Francesco Cozzoli; Guanghai Feng; Xiaojing Li; Zhengquan Zhou; Linlin Chen (Acta Oceanologica Sinica, 2019)

Diversity of the Fusarium pathogens associated with crown rot in the Huanghuai wheat‐growing region of China - Haifeng Zhou; Xiaolun He; Shuo Wang; Qingzhou Ma; Bingjian Sun; Shengli Ding; Linlin Chen; Meng Zhang; Honglian Li (Environmental Microbiology, 2019)
Summary To investigate the distribution and diversity of the pathogens associated with Fusarium crown rot in the Huanghuai wheat‐growing region (HHWGR) of China, we collected wheat samples with symptomatic stem bases from seven provinces in the HHWGR between 2013 and 2016. A total of 1196 isolates obtained from 222 locations were identified as 9 Fusarium species based on morphological and molecular identification. Of these pathogen species, F. pseudograminearum was the dominant species. Furthermore, F. sinensis was isolated from the disease specimens and tested for virulence to wheat. The result of the pathogenicity revealed that an intraspecific differentiation existed in F. pseudograminearum ; sequence analysis of the EF‐1α gene showed that 194 F. pseudograminearum isolates were differentiated into two distinct clades which closed to the strains from Australia and China respectively, but neither pathogenicity nor EF‐1α sequence was related to the geographic origins of these isolates. However, universal rice primers‐polymerase chain reaction showed a correlation with the geographical origins of the 194 isolates, which were divided into eight subclusters, the level of genetic diversity was higher within a geographical population than among the different populations. The results of these analyses can be directly used to facilitate disease monitoring and development of control strategies.

Reassessment of the 1907 Sumatra “Tsunami Earthquake” Based on Macroseismic, Seismological, and Tsunami Observations, and Modeling - Stacey Servito Martin; Linlin Li; Emile A. Okal; Julie Morin; Alexander E. G. Tetteroo; Adam D. Switzer; Kerry E. Sieh (Pure and Applied Geophysics, 2019)

An overview of tubulin modulators deposited in protein data bank - Haowei Guo; Xingcong Li; Ya Guo; Linlin Zhen (Medicinal Chemistry Research, 2019)

Optimizing cold storage of the ectoparasitic mite Pyemotes zhonghuajia (Acari: Pyemotidae), an efficient biological control agent of stem borers - Limin He; Litao Li; Lichen Yu; Xiong Z. He; Rui Jiao; Changxin Xu; Linlin Zhang; Jinli Liu (Experimental and Applied Acarology, 2019)

Geochemical characteristics of dust aerosol availability in northwestern China - Xunming Wang; Jimin Sun; Mingrui Qiang; Caixia Zhang; Danfeng Li; Ting Hua; Hui Li; Lili Lang; Linlin Jiao; Diwen Cai; Wenyong Ma (Arabian Journal of Geosciences, 2019)

Luteolin decreases the yield of influenza A virus in vitro by interfering with the coat protein I complex expression - Haiyan Yan; Linlin Ma; Huiqiang Wang; Shuo Wu; Hua Huang; Zhengyi Gu; Jiandong Jiang; Yuhuan Li (Journal of Natural Medicines, 2019)

Expression analysis of And4 during fin regeneration in Misgurnus anguillicaudatus provides insights into its function - Li Li; Qian Xiao; Linlin Wang; Zhongjie Chang (Fish Physiology and Biochemistry, 2019)

Electrosorptive removal of salt ions from water by membrane capacitive deionization (MCDI): characterization, adsorption equilibrium, and kinetics - Guiju Li; Wenbo Cai; Ruihua Zhao; Linlin Hao (Environmental Science and Pollution Research, 2019)

Major ion and dissolved heavy metal geochemistry, distribution, and relationship in the overlying water of Dongting Lake, China - Yan Chen; Lingqing Wang; Tao Liang; Jun Xiao; Jing Li; Haicheng Wei; Linlin Dong (Environmental Geochemistry and Health, 2019)

Classification and characterization of bound water in marine mucky silty clay - Shuo Li; Changming Wang; Xianwei Zhang; Linlin Zou; Zhenxue Dai (Journal of Soils and Sediments, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Sodium Fluoride (NaF) Induces Inflammatory Responses Via Activating MAPKs/NF-κB Signaling Pathway and Reducing Anti-inflammatory Cytokine Expression in the Mouse Liver - Linlin Chen; Ping Kuang; Huan Liu; Qin Wei; Hengmin Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Yinglun Li; Xun Wang; Ling Zhao (Biological Trace Element Research, 2019)

Xylitol Production by Candida tropicalis 31949 from Sugarcane Bagasse Hydrolysate - Linlin Xu; Lei Liu; Sijia Li; Wenjing Zheng; Yuanyuan Cui; Rong Liu; Weidong Sun (Sugar Tech, 2019)

Formula of bed-load transport based on the total threshold probability - Linlin Li; Genguang Zhang; Jiajun Zhang (Environmental Fluid Mechanics, 2019)

Application of GNSS interferometric reflectometry for detecting storm surges - Dongju Peng; Emma M. Hill; Linlin Li; Adam D. Switzer; Kristine M. Larson (GPS Solutions, 2019)

Role of Exogenous Glutathione in Alleviating Abiotic Stress in Maize (Zea mays L.) - Laming Pei; Ronghui Che; Linlin He; Xingxing Gao; Weijun Li; Hui Li (Journal of Plant Growth Regulation, 2019)

Ascorbic acid induces cardiac differentiation of white adipose tissue-derived stem cells - Wenhui Liu; Huan Liu; Yinghui Wang; Linlin Zhang; Chunhui Wang; Haifang Li (Molecular and Cellular Biochemistry, 2019)

Relative trajectory-driven virtual dynamic occlusal adjustment for dental restorations - Sukun Tian; Ning Dai; Xiaosheng Cheng; Linlin Li; Yuchun Sun; Haihua Cui (Medical & Biological Engineering & Computing, 2019)

A novel long non-coding RNA, lncKBTBD10, involved in bovine skeletal muscle myogenesis - Mingming Chen; Xin Li; Xiaojuan Zhang; Yan Li; Junxing Zhang; Minhui Liu; Linlin Zhang; Xiangbin Ding; Xinfeng Liu; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2019)

Lateral Circulation in a Partially Stratified Tidal Inlet - Linlin Cui; Haosheng Huang; Chunyan Li; Dubravko Justic (Journal of Marine Science and Engineering, 2018)
Using a three-dimensional, hydrostatic, primitive-equation ocean model, this study investigates the dynamics of lateral circulation in a partially stratified tidal inlet, the Barataria Pass in the Gulf of Mexico, over a 25.6 h diurnal tidal cycle. Model performance is assessed against observational data. During flood tide, the lateral circulation exhibits the characteristics similar to those induced by differential advection, i.e., lateral flow consists of two counter-rotating cells and is convergent at the surface. The analysis of momentum balance indicates that, in addition to the pressure gradient and vertical stress divergence, nonlinear advection and horizontal stress divergence are also important contributors. During ebb phase, the lateral circulation is mostly toward the right shoal (when looking into the estuary) for the whole water column and persisting for almost the whole period. The surface divergence suggested by the differential advection mechanism lasts for a very short period, if it ever exists. The main momentum balance across most of the transect during ebb is between the along-channel advection of cross-channel momentum and pressure gradient. The sectional averaged lateral velocity magnitude during ebb is comparable to that during flood, which is different from the idealized numerical experiment result.

Spirillospora tritici sp. nov., a Novel Actinomycete Isolated from Rhizosphere Soil of Triticum aestivum L. - Jing Song; Jiabin Wang; Tianyu Sun; Chuang Li; Hairong He; Linlin Shi; Xiaowei Guo; Junwei Zhao; Wensheng Xiang (Current Microbiology, 2018)

Genome survey sequencing of red swamp crayfish Procambarus clarkii - Linlin Shi; Shaokui Yi; Yanhe Li (Molecular Biology Reports, 2018)

Contribution of heterotrophic bacterioplankton to cyanobacterial bloom formation in a tributary backwater area of the Three Gorges Reservoir, China - Lunhui Lu; Linlin Xu; Jixiang Yang; Zhe Li; Jinsong Guo; Yan Xiao; Juanjuan Yao (Environmental Science and Pollution Research, 2018)

The expression and role of lncRNA AX800134 in hepatitis B virus-related hepatocellular carcinoma - Kai Zuo; Li Kong; Dong Xue; Yanyan Yang; Linlin Xie (Virus Genes, 2018)

Analyzing Coastal Wetland Degradation and its Key Restoration Technologies in the Coastal Area of Jiangsu, China - Linlin Cui; Guosheng Li; Ninglei Ouyang; Fengyun Mu; Fu Yan; Youtian Zhang; Xiaoyang Huang (Wetlands, 2018)

Tissue Distribution and Gender-Specific Protein Expression of Cytochrome P450 in five Mouse Genotypes with a Background of FVB - Jiamei M. Chen; Qisong S. Zhang; Xiaoyan Y. Li; Xia Gong; Yanjiao J. Ruan; Sijing J. Zeng; Linlin L. Lu; Xiaoxiao X. Qi; Ying Wang; Ming Hu; Lijun J. Zhu; Zhongqiu Q. Liu (Pharmaceutical Research, 2018)

Prevalence and trend of isolated and complicated congenital hydrocephalus and preventive effect of folic acid in northern China, 2005–2015 - Jufen Liu; Lei Jin; Zhiwen Li; Yali Zhang; Le Zhang; Linlin Wang; Aiguo Ren (Metabolic Brain Disease, 2018)

The impact of urbanization on wind speed and surface aerodynamic characteristics in Beijing during 1991–2011 - Junkai Liu; Zhiqiu Gao; Linlin Wang; Yubin Li; Chloe Y. Gao (Meteorology and Atmospheric Physics, 2018)

The potential effects of aeolian processes on the vegetation in a semiarid area: geochemical evidence from plants and soils - Junpeng Lou; Xunming Wang; Bingqi Zhu; Danfeng Li; Linlin Jiao; Wenyong Ma; Diwen Cai (Arabian Journal of Geosciences, 2018)

Size distribution of individuals in the population of Asterias amurensis (Echinodermata: Asteroidea) and its reproductive cycle in China - Baoquan Li; Zhengquan Zhou; Bingjun Li; Quanchao Wang; Xiaojing Li; Linlin Chen (Acta Oceanologica Sinica, 2018)

Synaptobrevin-2 facilitates the trafficking and function of atrial SK2 channel - Tao Li; Xuehui Fan; Yiyan Yu; Linlin Chen; Wenjun Huang; Yan Yang; Jimin Cao; Xiaorong Zeng; Xiaoqiu Tan (Science China Life Sciences, 2018)

Macrobenthic assemblage characteristics under stressed waters and ecological health assessment using AMBI and M-AMBI: a case study at the Xin’an River Estuary, Yantai, China - Zhengquan Zhou; Xiaojing Li; Linlin Chen; Baoquan Li; Tiantian Liu; Binghua Ai; Lufei Yang; Bo Liu; Qiao Chen (Acta Oceanologica Sinica, 2018)

Main Features and Problems of Modern Evolution Process of Coastal Wetlands in North Jiangsu, China - Ninglei Ouyang; Guosheng Li; Linlin Cui; Huajun Liao (Journal of the Indian Society of Remote Sensing, 2018)

Investigation on mining subsidence over Appin–West Cliff Colliery using time-series SAR interferometry - Zheyuan Du; Linlin Ge; Alex Hay-Man Ng; Xiaojing Li (International Journal of Remote Sensing, 2018)

The role of Ustilaginoidea virens sclerotia in increasing incidence of rice false smut disease in the subtropical zone in China - Mingli Yong; Qide Deng; Linlin Fan; Jiankun Miao; Chaohui Lai; Hongming Chen; Xiujuan Yang; Shu Wang; Furu Chen; Li Jin; Binghui Yang; Yuanjun Bai; et al. (European Journal of Plant Pathology, 2018)

Reduced deep regional cerebral venous oxygen saturation in hemodialysis patients using quantitative susceptibility mapping - Chao Chai; Saifeng Liu; Linlin Fan; Lei Liu; Jinping Li; Chao Zuo; Tianyi Qian; E. Mark Haacke; Wen Shen; Shuang Xia (Metabolic Brain Disease, 2018)

Plantactinospora solaniradicis sp. nov., a novel actinomycete isolated from the root of a tomato plant (Solanum lycopersicum L.) - Wenchao Li; Xiaowei Guo; Linlin Shi; Junwei Zhao; Liangliang Yan; Xiaotong Zhong; Chen Zhang; Yufei Chen; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Co-Delivery of Doxorubicin and Survivin shRNA-Expressing Plasmid Via Microenvironment-Responsive Dendritic Mesoporous Silica Nanoparticles for Synergistic Cancer Therapy - Zhengxiong Li; Linlin Zhang; Cui Tang; Chunhua Yin (Pharmaceutical Research, 2017)

MicroRNA-192 regulates hypertrophic scar fibrosis by targeting SIP1 - Yan Li; Julei Zhang; Wei Zhang; Yang Liu; Yuehua Li; Kejia Wang; Yijie Zhang; Chen Yang; Xiaoqiang Li; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Integrated space geodesy for mapping land deformation over Choushui River Fluvial Plain, Taiwan - Linlin Ge; Alex Hay-Man Ng; Zheyuan Du; Horng-Yue Chen; Xiaojing Li (International Journal of Remote Sensing, 2017)

Identification and Functional Analysis of Two Cotton Orthologs of MAX2 Which Control Shoot Lateral Branching - Linlin Zhao; Jingjing Fang; Jin Xing; Weina Liu; Peng Peng; Haixin Long; Jinfeng Zhao; Wenhui Zhang; Xueyong Li (Plant Molecular Biology Reporter, 2017)

MiR-125a regulates mitochondrial homeostasis through targeting mitofusin 1 to control hypoxic pulmonary vascular remodeling - Cui Ma; Chen Zhang; Mingfei Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Yingli Chen; Fangyuan Cao; Minghui Li; Guangtian Wang; Tingting Shen; Hongmin Yao; et al. (Journal of Molecular Medicine, 2017)

The analgesic effect of trans-resveratrol is regulated by calcium channels in the hippocampus of mice - Weijie Wang; Yingcong Yu; Jing Li; Lin Wang; Zhi Li; Chong Zhang; Linlin Zhen; Lianshu Ding; Gang Wang; Xiaoyang Sun; Ying Xu (Metabolic Brain Disease, 2017)

Staphylococcus enterotoxin profile of China isolates and the superantigenicity of some novel enterotoxins - Menglu Shen; Yi Li; Linlin Zhang; Songbao Dai; Jiashun Wang; Yongqing Li; Lei Zhang; Jinhai Huang (Archives of Microbiology, 2017)

Occurrence of diazepam and its metabolites in wastewater and surface waters in Beijing - Congcong Wang; Linlin Hou; Jing Li; Zeqiong Xu; Tingting Gao; Jun Yang; Huafang Zhang; Xiqing Li; Peng Du (Environmental Science and Pollution Research, 2017)

Carboniferous Alaskan-type complex along the Sino–Mongolian boundary, southern margin of the Central Asian Orogenic Belt - Yuruo Shi; Linlin Li; Alfred Kröner; Jing Ding; Wei Zhang; Zengbao Huang; Ping Jian (Acta Geochimica, 2017)

The death of the circulatory system diseases in China: provincial socioeconomic and environmental perspective - Haixia Pu; Jiatian Li; Pin Wang; Linlin Cui; Huaxin Wang (Environmental Science and Pollution Research, 2017)

A Selenium-Enriched Ziyang Green Tea Polysaccharide Induces Bax-Dependent Mitochondrial Apoptosis and Inhibits TGF-β1-Stimulated Collagen Expression in Human Keloid Fibroblasts via NG2 Inactivation - Lele Lu; Linlin Chai; Wenping Wang; Xi Yuan; Shirong Li; Chuan Cao (Biological Trace Element Research, 2017)

Late Quaternary lake evolution in the Gaxun Nur basin, central Gobi Desert, China, based on quartz OSL and K‐feldspar pIRIR dating of paleoshorelines - Guoqiang Li; Fangliang Li; Ming Jin; Linlin She; Yanwu Duan; David Madsen; Leibin Wang; Fahu Chen (Journal of Quaternary Science, 2017)
Paleoenvironmental changes in the Gobi Desert of Mongolia are of global significance because fluvial and lacustrine deposits in the region constitute one of the dominant sources of Northern Hemisphere dust. A series of well‐preserved geomorphic shoreline features at different elevations around the Gaxun Nur basin, central Gobi Desert, indicate past fluctuations of the basin's terminal lake. We measured the exact elevation of shorelines in the basin using a Differential Global Positioning System, and found six shorelines at ∼24, ∼20, ∼18, ∼16, ∼15 m and ∼8 m above the modern basin floor. Quartz optically stimulated luminescence and K‐feldspar post‐infrared infrared stimulated luminescence methods were used to date these shoreline features. The reliability of the dates was confirmed using internal checks of luminescence characteristics and by comparing the quartz and K‐feldspar ages. Our results suggest a lake developed in the Gaxun Nur basin by at least ∼121 ka. Lake levels increased from ∼8 to ∼24 m from ∼121 to ∼85 ka. A 20–13‐m‐deep lake again formed in the basin between ∼8.4 and 0.8 ka. Monsoonal precipitation and temperature variations during Marine Isotope Stage 5 and the mid–late Holocene were the likely causes of paleolake formation and lake level fluctuations.

Estimate of Boundary-Layer Depth Over Beijing, China, Using Doppler Lidar Data During SURF-2015 - Meng Huang; Zhiqiu Gao; Shiguang Miao; Fei Chen; Margaret A. LeMone; Ju Li; Fei Hu; Linlin Wang (Boundary-Layer Meteorology, 2017)

Effect of LA on the Growth and Development of the Main Organs in Female Mice - Xiuyuan He; Feng Lin; Yongtao Li; Yuxia Chen; Jing Li; Linlin Guo; Xuelei Han; Huan Song (Biological Trace Element Research, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Short communication: antiviral activity of porcine IFN-λ3 against porcine epidemic diarrhea virus in vitro - Haiyan Shen; Chunhong Zhang; Pengju Guo; Zhicheng Liu; Minhua Sun; Junying Sun; Linlin Li; Jiawen Dong; Jianfeng Zhang (Virus Genes, 2016)

Genome-Wide Analysis of Alternative Splicing Provides Insights into Stress Adaptation of the Pacific Oyster - Baoyu Huang; Linlin Zhang; Xueying Tang; Guofan Zhang; Li Li (Marine Biotechnology, 2016)

Critical nutrient thresholds needed to control eutrophication and synergistic interactions between phosphorus and different nitrogen sources - Qinghui Zeng; Lihuan Qin; Linlin Bao; Yayong Li; Xuyong Li (Environmental Science and Pollution Research, 2016)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

Antiviral effects of Stichopus japonicus acid mucopolysaccharide on hepatitis B virus transgenic mice - Yongning Xin; Wei Li; Linlin Lu; Li Zhou; David W. Victor; Shiying Xuan (Journal of Ocean University of China, 2016)

Phosphatidylinositol 3-phosphate, an essential lipid in Phytophthora sojae, enriches in the haustoria during infection - Linlin Chen; Wen Wang; Ying Hou; Yuren Wu; Honglian Li; Daolong Dou (Australasian Plant Pathology, 2016)

Reactive oxygen species effect PASMCs apoptosis via regulation of dynamin-related protein 1 in hypoxic pulmonary hypertension - Lixin Zhang; Cui Ma; Chen Zhang; Mingfei Ma; Fengying Zhang; Linlin Zhang; Yingli Chen; Fangyuan Cao; Shuzhen Li; Daling Zhu (Histochemistry and Cell Biology, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

Zircon ages and Hf isotopic compositions of Permian and Triassic A-type granites from central Inner Mongolia and their significance for late Palaeozoic and early Mesozoic evolution of the Central Asian Orogenic Belt - Yuruo Shi; J. Lawford Anderson; Linlin Li; Jing Ding; Cui Liu; Wei Zhang; Chonghui Shen (International Geology Review, 2016)

Characterization of chromophoric dissolved organic matter and relationships among PARAFAC components and water quality parameters in Heilongjiang, China - Hongyang Cui; Jianhong Shi; Linlin Qiu; Yue Zhao; Zimin Wei; Xinglei Wang; Liming Jia; Jiming Li (Environmental Science and Pollution Research, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Expression of HIV-encoded microRNA-TAR and its inhibitory effect on viral replication in human primary macrophages - Li Li; Haimin Feng; Qin Da; Honglin Jiang; Lang Chen; Linlin Xie; Qiuling Huang; Hairong Xiong; Fan Luo; Lei Kang; Yan Zeng; Haitao Hu; et al. (Archives of Virology, 2016)

Expression Characterization of Stress Genes Under High and Low Temperature Stresses in the Pacific Oyster, Crassostrea gigas - Qihui Zhu; Linlin Zhang; Li Li; Huayong Que; Guofan Zhang (Marine Biotechnology, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

NF45 overexpression is associated with poor prognosis and enhanced cell proliferation of pancreatic ductal adenocarcinoma - Chunhua Wan; Chen Gong; Li Ji; Xiaorong Liu; Yayun Wang; Liang Wang; Mengting Shao; Linlin Yang; Shaoqing Fan; Yin Xiao; Xiaotong Wang; Manhua Li; et al. (Molecular and Cellular Biochemistry, 2015)

Induction of forkhead box M1 (FoxM1) by EGF through ERK signaling pathway promotes trophoblast cell invasion - Yunpeng Xie; Dan Cui; Linlin Sui; Yuefei Xu; Ningning Zhang; Yanni Ma; Yinghua Li; Ying Kong (Cell and Tissue Research, 2015)

Evaluation of MODIS Spectral Indices for Monitoring Hydrological Dynamics of a Small, Seasonally-Flooded Wetland in Southern Spain - Linlin Li; Anton Vrieling; Andrew Skidmore; Tiejun Wang; Antonio-Román Muñoz; Eren Turak (Wetlands, 2015)

MRP1 knockdown down-regulates the deposition of collagen and leads to a reduced hypertrophic scar fibrosis - Yan Li; Longlong Yang; Zhao Zheng; Jihong Shi; Xue Wu; Hao Guan; Yanhui Jia; Ke Tao; Hongtao Wang; Shichao Han; Jianxin Gao; Bin Zhao; et al. (Journal of Molecular Histology, 2015)

Seasonal and interannual variations of carbon exchange over a rice-wheat rotation system on the North China Plain - Chen Chen; Dan Li; Zhiqiu Gao; Jianwu Tang; Xiaofeng Guo; Linlin Wang; Bingcheng Wan (Advances in Atmospheric Sciences, 2015)

Analysis of the temporal and spatial distribution of water quality in China’s major river basins, and trends between 2005 and 2010 - Jinjian Li; Xiaojie Meng; Yan Zhang; Juan Li; Linlin Xia; Hongmei Zheng (Frontiers of Earth Science, 2015)

Pygo2 siRNA Inhibit the Growth and Increase Apoptosis of U251 Cell by Suppressing Histone H3K4 Trimethylation - Mingcong Li; Linlin Chao; Jian Wu; Hao Xu; Shanghan Shen; Sifang Chen; Xin Gao; Ning Yu; Zhanxiang Wang (Journal of Molecular Neuroscience, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

A gyrovirus infecting a sea bird - Linlin Li; Patricia A. Pesavento; Anne M. Gaynor; Rebecca S. Duerr; Tung Gia Phan; Wen Zhang; Xutao Deng; Eric Delwart (Archives of Virology, 2015)

Structural control on pore-fracture characteristics of coals from Xinjing coal mine, northeastern Qinshui basin, China - Jiegang Liu; Bo Jiang; Ming Li; Zhenghui Qu; Linlin Wang; Lei Li (Arabian Journal of Geosciences, 2015)

Heavy mineral assemblage characteristics and the Cenozoic paleogeographic evolution in southwestern Qaidam Basin - LinLin Li; ZhaoJie Guo; ShuWei Guan; SuPing Zhou; MingZhen Wang; YaNan Fang; ChenChen Zhang (Science China Earth Sciences, 2015)

Stromal cell-derived factor 1 (SDF-1) accelerated skin wound healing by promoting the migration and proliferation of epidermal stem cells - Rui Guo; Linlin Chai; Liang Chen; Wenguang Chen; Liangpeng Ge; Xiaoge Li; Hongli Li; Shirong Li; Chuan Cao (In Vitro Cellular & Developmental Biology - Animal, 2015)

Triple Recycling Processes Impact Systemic and Local Bioavailability of Orally Administered Flavonoids - Peimin Dai; Lijun Zhu; Feifei Luo; Linlin Lu; Qiang Li; Liping Wang; Ying Wang; Xinchun Wang; Ming Hu; Zhongqiu Liu (The AAPS Journal, 2015)

Highly sensitive fluorescence biosensors for sparfloxacin detection at nanogram level based on electron transfer mechanism of cadmium telluride quantum dots - Wanjun Liang; Shaopu Liu; Jing Song; Chenxia Hao; Linlin Wang; Dan Li; Youqiu He (Biotechnology Letters, 2015)

Integrated Approach Based on a Regional Habitat Succession Model to Assess Wetland Landscape Ecological Degradation - Linlin Cui; Guosheng Li; Huajun Liao; Ninglei Ouyang; Yue Zhang (Wetlands, 2015)

Erratum to: Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Variants in maternal COMT and MTHFR genes and risk of neural tube defects in offspring - Jufen Liu; Yali Zhang; Lei Jin; Guoxing Li; Linlin Wang; Yanping Bao; Yunting Fu; Zhiwen Li; Le Zhang; Rongwei Ye; Aiguo Ren (Metabolic Brain Disease, 2015)

Decreased expression and activation of Stat3 in severe preeclampsia - Zhan Zhang; Xiaoqian Yang; Linlin Zhang; Zhenfeng Duan; Liting Jia; Peng Wang; Ying Shi; Ying Li; Junjun Gao (Journal of Molecular Histology, 2015)

Expression of neuropeptides and bone remodeling-related factors during periodontal tissue regeneration in denervated rats - Xijiao Yu; Linlin Lv; Jing Zhang; Ting Zhang; Changjie Xiao; Shu Li (Journal of Molecular Histology, 2015)

Generation of bi-transgenic pigs overexpressing human lactoferrin and lysozyme in milk - Dan Cui; Jia Li; Linlin Zhang; Shen Liu; Xiao Wen; Qiuyan Li; Yaofeng Zhao; Xiaoxiang Hu; Ran Zhang; Ning Li (Transgenic Research, 2015)

Contrasting characteristics of the surface energy balance between the urban and rural areas of Beijing - Linlin Wang; Zhiqiu Gao; Shiguang Miao; Xiaofeng Guo; Ting Sun; Maofeng Liu; Dan Li (Advances in Atmospheric Sciences, 2015)

Identification and characteristics of imipenem-resistant Acinetobacter baumannii in surgical wards in a Chinese university hospital - Dalin Wang; Linlin Ma; Zhenyu Wu; Mingcheng Li; Xiaohan Li; Wei Zhang; Kun Chen (Infectious Diseases, 2015)

Genetic manipulation of a high-affinity PHR1 target cis-element to improve phosphorous uptake in Oryza sativa L. - Wenyuan Ruan; Meina Guo; Linlin Cai; Hongtao Hu; Changying Li; Yu Liu; Zhongchang Wu; Chuanzao Mao; Keke Yi; Ping Wu; Xiaorong Mo (Plant Molecular Biology, 2015)

Significantly Decreased and More Variable Expression of Major CYPs and UGTs in Liver Microsomes Prepared from HBV-Positive Human Hepatocellular Carcinoma and Matched Pericarcinomatous Tissues Determined Using an Isotope Label-free UPLC-MS/MS Method - Tongmeng Yan; Song Gao; Xiaojuan Peng; Jian Shi; Cong Xie; Qiang Li; Linlin Lu; Ying Wang; Fuyuan Zhou; Zhongqiu Liu; Ming Hu (Pharmaceutical Research, 2015)

Modified Nonparametric Weighted Feature Extraction Algorithm - Linlin Cui; Guosheng Li; Huiru Ren; Lei He; Huajun Liao (Journal of the Indian Society of Remote Sensing, 2015)

Full and ideal mixing behavior between Zr–Wd (K2ZrSi3O9) and Ti–Wd (K2TiSi3O9): evidences from mineral chemistry, X-ray diffraction pattern and Raman spectrum - Linlin Chang; Xi Liu; Chunming Wu; Xiaoyang Liu; Guowu Li (Physics and Chemistry of Minerals, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Multi-scale variability of water discharge and sediment load into the Bohai Sea from 1950 to 2011 - Huiru Ren; Guosheng Li; Linlin Cui; Lei He (Journal of Geographical Sciences, 2015)

Comparative analysis of oyster ( Crassostrea gigas ) immune responses under challenge by different Vibrio strains and conditions - Jie Meng; Linlin Zhang; Baoyu Huang; Li Li; Guofan Zhang (Molluscan Research, 2015)

Expression and Localization of Estrogen Receptor in Human Breast Cancer and Its Clinical Significance - Lv Li; Qimin Wang; Xiupeng Lv; Lin Sha; Huamin Qin; Lifen Wang; Linlin Li (Cell Biochemistry and Biophysics, 2015)

Distribution of enterovirus 71 RNA in inflammatory cells infiltrating different tissues in fatal cases of hand, foot, and mouth disease - Pin Yu; Zifen Gao; Yuanyuan Zong; Linlin Bao; Lili Xu; Wei Deng; Yanfeng Xu; Zhancheng Gao; Yanfeng Yao; Fengdi Li; Qi Lv; Chuan Qin (Archives of Virology, 2015)

Numerical simulation of erosion and deposition at the Thailand Khao Lak coast during the 2004 Indian Ocean tsunami - Linlin Li; Zhenhua Huang; Qiang Qiu (Natural Hazards, 2014)

Study on Evolution Features and Spatial Distribution Patterns of Coastal Wetlands in North Jiangsu Province, China - Huajun Liao; Guosheng Li; Linlin Cui; Ninglei Ouyang; Yue Zhang; Shaohua Wang (Wetlands, 2014)

Alternative splicing and immune response of Crassostrea gigas tumor necrosis factor receptor-associated factor 3 - Baoyu Huang; Linlin Zhang; Yishuai Du; Li Li; Tao Qu; Jie Meng; Guofan Zhang (Molecular Biology Reports, 2014)

Overexpression of the PLAP-1 gene inhibits the differentiation of BMSCs into osteoblast-like cells - Jing Sun; Ting Zhang; Panpan Zhang; Linlin Lv; Yanzhi Wang; Jing Zhang; Shu Li (Journal of Molecular Histology, 2014)

Mesoaccumbens dopamine signaling alteration underlies behavioral transition from tolerance to sensitization to morphine rewarding properties during morphine withdrawal - Linlin Sun; Ling Hu; Yijing Li; Cailian Cui (Brain Structure and Function, 2014)

A KPCA texture feature model for efficient segmentation of RADARSAT-2 SAR sea ice imagery - Linlin Xu; Jonathan Li; Alexander Wong; Cheng Wang (International Journal of Remote Sensing, 2014)

Healing of periodontal defects and calcitonin gene related peptide expression following inferior alveolar nerve transection in rats - Linlin Lv; Yanzhi Wang; Jing Zhang; Ting Zhang; Shu Li (Journal of Molecular Histology, 2014)

Transcriptomic analysis reveals key regulators of mammogenesis and the pregnancy-lactation cycle - YuanYuan Zhou; Wei Gong; JingFa Xiao; JiaYan Wu; LinLin Pan; XiaoNuan Li; XuMin Wang; WeiWei Wang; SongNian Hu; Jun Yu (Science China Life Sciences, 2014)

Erratum to: Turbulent Transport of Momentum and Scalars Above an Urban Canopy - Linlin Wang; Dan Li; Zhiqiu Gao; Ting Sun; Xiaofeng Guo; Elie Bou-Zeid (Boundary-Layer Meteorology, 2014)

Turbulent Transport of Momentum and Scalars Above an Urban Canopy - Linlin Wang; Dan Li; Zhiqiu Gao; Ting Sun; Xiaofeng Guo; Elie Bou-Zeid (Boundary-Layer Meteorology, 2014)

Transcriptome Analysis Reveals a Rich Gene Set Related to Innate Immunity in the Eastern Oyster (Crassostrea virginica) - Linlin Zhang; Li Li; Yabing Zhu; Guofan Zhang; Ximing Guo (Marine Biotechnology, 2014)

The characteristics of epithelial cell rests of Malassez during tooth eruption of development mice - Yanzhi Wang; Linlin Lv; Xijiao Yu; Ting Zhang; Shu Li (Journal of Molecular Histology, 2014)

Isolation and characterization of a Δ1-pyrroline-5-carboxylate synthetase (NtP5CS) from Nitraria tangutorum Bobr. and functional comparison with its Arabidopsis homologue - Linlin Zheng; Zhenhua Dang; Haoyu Li; Huirong Zhang; Shubiao Wu; Yingchun Wang (Molecular Biology Reports, 2014)

Investigation and integrated molecular diagnosis of root-knot nematodes in Panax notoginseng root in the field - Linlin Dong; Hui Yao; Qiushi Li; Jingyuan Song; Ying Li; Hongmei Luo; Shilin Chen (European Journal of Plant Pathology, 2013)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

Reducing basal salicylic acid enhances Arabidopsis tolerance to lead or cadmium - Siyuan Tao; Lihong Sun; Chunyan Ma; Linlin Li; Guangzhe Li; Lin Hao (Plant and Soil, 2013)

A robust regression-based linear model adjustment method for SAR interferogram stacking techniques - Kui Zhang; Linlin Ge; Xiaojing Li; Alex Hay-Man Ng (International Journal of Remote Sensing, 2013)

Assessment of the SeaWinds scatterometer for vegetation phenology monitoring across China - Linlin Lu; Huadong Guo; Cuizhen Wang; Qingting Li (International Journal of Remote Sensing, 2013)

Decreased expression of the DBC2 gene and its clinicopathological significance in breast cancer: correlation with aberrant DNA methylation - Linlin Han; Lin Hou; Jinlian Song; Dongliang Lin; Li Wu; Yinlin Ge; Zhongliang Ma (Biotechnology Letters, 2013)

High-Level Expression of Sporamin in Transgenic Chinese Cabbage Enhances Resistance Against Diamondback Moth - Lin Qiu; Tingting Wu; Heng Dong; Linlin Wu; Jiashu Cao; Li Huang (Plant Molecular Biology Reporter, 2013)

Monitoring ground surface deformation over the North China Plain using coherent ALOS PALSAR differential interferograms - Kui Zhang; Linlin Ge; Xiaojing Li; Alex Hay-Man Ng (Journal of Geodesy, 2013)

Fosmid library construction and end sequences analysis of the Pacific oyster, Crassostrea gigas - Linlin Zhang; Li Li; Fei Xu; Haigang Qi; Xiaotong Wang; Huayong Que; Guofan Zhang (Molluscan Research, 2013)

Overexpression of GbWRKY1 positively regulates the Pi starvation response by alteration of auxin sensitivity in Arabidopsis - Li Xu; Li Jin; Lu Long; Linlin Liu; Xin He; Wei Gao; Longfu Zhu; Xianlong Zhang (Plant Cell Reports, 2012)

Numerical modeling of the morphological change in Lhok Nga, west Banda Aceh, during the 2004 Indian Ocean tsunami: understanding tsunami deposits using a forward modeling method - Linlin Li; Qiang Qiu; Zhenhua Huang (Natural Hazards, 2012)

Identification and genomic analysis of two duck-origin Tembusu virus strains in southern China - Linlin Li; Hejia An; Minhua Sun; Jiawen Dong; Jianfeng Yuan; Qilin Hu (Virus Genes, 2012)

Purification and characterization of an extracellular poly(3-hydroxybutyrate-co-3-hydroxyvalerate) depolymerase from Acidovorax sp. HB01 - Zhanyong Wang; Jia Gao; Linlin Li; Husheng Jiang (World Journal of Microbiology and Biotechnology, 2012)

Monitoring ground deformation in Beijing, China with persistent scatterer SAR interferometry - Alex Hay-Man Ng; Linlin Ge; Xiaojing Li; Kui Zhang (Journal of Geodesy, 2012)

PTEN inhibits proliferation and functions of hypertrophic scar fibroblasts - Liang Guo; Liang Chen; Sheng Bi; Linlin Chai; Zengxiang Wang; Chuan Cao; Ling Tao; Shirong Li (Molecular and Cellular Biochemistry, 2012)

Effects of Aluminum Exposure on Serum Sex Hormones and Androgen Receptor Expression in Male Rats - Hao Sun; Chongwei Hu; Linlin Jia; Yanzhu Zhu; Hansong Zhao; Bing Shao; Nan Wang; Zhigang Zhang; Yanfei Li (Biological Trace Element Research, 2011)

Deformation mapping in three dimensions for underground mining using InSAR – Southern highland coalfield in New South Wales, Australia - Alex Hay-Man Ng; Linlin Ge; Kui Zhang; Hsing-Chung Chang; Xiaojing Li; Chris Rizos; Makoto Omura (International Journal of Remote Sensing, 2011)

Variable length LMS adaptive filter for carrier phase multipath mitigation - Huicui Liu; Xiaojing Li; Linlin Ge; Chris Rizos; Feixue Wang (GPS Solutions, 2011)

Left ventricular hypertrophy induced by abdominal aortic banding and its prevention by angiotensin receptor blocker telmisartan—a proteomic analysis - Li Liu; Wen Wang; Xianmin Meng; Jiuming Gao; Haiying Wu; Peihe Wang; Weichun Wu; Linlin Wang; Liyuan Ma; Weiguo Zhang (Journal of Physiology and Biochemistry, 2010)

FaRE1: a transcriptionally active Ty1-copia retrotransposon in strawberry - Ping He; Yue Ma; Guiling Zhao; Hongyan Dai; He Li; Linlin Chang; Zhihong Zhang (Journal of Plant Research, 2010)

Ice phase as an important factor on the seasonal variation of polycyclic aromatic hydrocarbons in the Tumen River, Northeastern of China - Linlin Cong; Yingyu Fang; Miao He; Xinshun Wang; Narayanan Kannan; Donghao Li (Environmental Science and Pollution Research, 2010)

Determination of Phthalate Esters in Soil Samples by Microwave Assisted Extraction and High Performance Liquid Chromatography - Pei Liang; Linlin Zhang; Lili Peng; Qian Li; Ehong Zhao (Bulletin of Environmental Contamination and Toxicology, 2010)

Fibronectin and asialoglyprotein receptor mediate hepatitis B surface antigen binding to the cell surface - Jing Yang; Feng Wang; Linlin Tian; Jing Su; Xiangqian Zhu; Li Lin; Xiaoran Ding; Xuejun Wang; Shengqi Wang (Archives of Virology, 2010)

Regulation of Cell Division and Growth in Roots of Lactuca sativa L. Seedlings by the Ent-Kaurene Diterpenoid Rabdosin B - Lan Ding; Hongwei Jing; Bo Qin; Linlin Qi; Jing Li; Tao Wang; Guoan Liu (Journal of Chemical Ecology, 2010)

Isolation of DNA-methyltransferase genes from strawberry (Fragaria × ananassa Duch.) and their expression in relation to micropropagation - Linlin Chang; Zhihong Zhang; Baiming Han; He Li; Hongyan Dai; Ping He; Hongzhe Tian (Plant Cell Reports, 2009)

MicroRNA expression profiles in conventional and micropropagated strawberry (Fragaria × ananassa Duch.) plants - He Li; Zhihong Zhang; Feifei Huang; Linlin Chang; Yue Ma (Plant Cell Reports, 2009)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)

Phytotoxic Effects of Leukamenin E (an ent-kaurene diterpenoid) on Root Growth and Root Hair Development in Lactuca sativa L. seedlings - Lan Ding; Linlin Qi; Hongwei Jing; Juan Li; Wei Wang; Tao Wang (Journal of Chemical Ecology, 2008)

Full-scale structural monitoring using an integrated GPS and accelerometer system - Xiaojing Li; Linlin Ge; Eliathamby Ambikairajah; Chris Rizos; Yukio Tamura; Akihito Yoshida (GPS Solutions, 2006)

Inhibitory connections among rostral medullary expiratory neurones detected with cross-correlation in the decerebrate rat* - Linlin Shen; Yan-Mei Li; James Duffin (Pflügers Archiv - European Journal of Physiology, 2003)